Effects of chronic salinity stress on muscle inflammatory immunity, glycolipid metabolism, proliferation and differentiation in freshwater drum (Aplodinotus grunniens) - Miaomiao Xue; Hang Wang; Pao Xu; Haibo Wen; Jiyan He; Jianxiang Chen; Hongxia Li; Changyou Song (Aquaculture, 2027)

A Self-floating hydrogel with Fe/C-doped MoS2 for simultaneous solar evaporation and purification of phenol - Xinge Li; Jing Li; Peng Li; Wen Song; Xuguang Li; Yanxia Zhao; Tao Yan; Liangguo Yan (Water Research, 2026)

Comparative structural, colloidal, and kinetic evaluation of yeast, soy, and whey proteins: uncovering the modification needs of yeast protein - Siliang Wu; Kewei Chen; Wen Li; Xueying Song; Yihan Mu; Mouming Zhao; Guowan Su (Food Hydrocolloids, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

LSTM-powered prediction and symbolic regression for p-y curves of offshore monopiles in sand - Biao Li; Ben He; Qing-Kai Song; Guo-Hu Xie; Wen-Gang Qi (Computers and Geotechnics, 2026)

Icaritin improves pregnancy outcomes in endometriosis by inhibiting ovarian granulosa cell senescence - Yalun He; Jie Ding; Yangshuo Li; Ji Sun; Cuiping Wei; Na Sun; Runnan Jiang; Ziming Zhao; Xiaolan Liang; Yiming Chen; Wen Cheng; Litai Zhang; et al. (Molecular Biology Reports, 2026)

Yam glycoprotein mediated the immunomodulation of macrophages by targeting TLR4 - Yuzhi Luo; Siqi Wang; Lingyi Liu; Ruisi Zhu; Xiaoyue Wang; Yajing Ma; Huixin Song; Sha Wen; Lingli Li; Songyuan Xia; Weifeng Li; Xiaofeng Niu (Molecular Biology Reports, 2026)

Cane water content regulates grapevine (Vitis vinifera L.) winter bud dormancy via ros homeostasis and antioxidant enzyme system - Wen-Qin Hua; Song-Yu Li; You-Mei Li; Zhao-Sen Xie (Molecular Biology Reports, 2026)

Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Metasomatism of zircon by alkali-bearing fluids during deposition of Au deposits - Zihao Wen; Daniel E. Harlov; Bo Xu; Lin Li; Yingxin Song; Shengrong Li (Lithos, 2026)

Gradient-engineered PDMS/CuS/PDA-PVDF hollow-fiber membrane for decoupled interfacial heating and robust anti-wetting in solar desalination - Qin Yuan; Liu Wang; Xin Sun; Riquan Song; Xiaowen Wen; Huipeng Li (Desalination, 2026)

A flexible Micro-spinous MXene/P(VDF-TrFE) composite triboelectric sensor for self-powered identity authentication and tactile perception - Kexin Chen; Wei Li; Hongji Guan; Dexin Song; Licheng Wei; Hanbin Ding; Xinbo Wang; Shuyan Chen; Xuejuan Kang; Wen Ouyang; Wenchao Zhai; Xuan Peng; et al. (Chemical Engineering Journal, 2026)

A conditional generative diffusion model enables joint retrieval of rice LAI and LCC - Heguang Sun; Huanming Mai; Bo Han; Yi Zhang; Zhongyu Jin; Changsheng Li; Wenqian Tang; Zifan Shen; Ziheng Feng; Xiaoyu Song; Yubin Lan; Wen Du; et al. (Computers and Electronics in Agriculture, 2026)

Muscle-specific genes validation and their functional analysis under starvation and hypothermia stress in freshwater drum (Aplodinotus grunniens) - Miaomiao Xue; Changxin Kong; Pao Xu; Haibo Wen; Jiyan He; Jianxiang Chen; Hongxia Li; Changyou Song (Aquaculture, 2026)

Divergent molecular strategies underlie bovine blastocyst hatching and cryopreservation stress adaptation revealed by integrated multi-omics - Wen-Long Lei; Wei Sun; Yaxin Guo; Di Cao; Zhanpeng Liu; Jian Song; Qing-Yuan Sun; Qian Zhou; Xihe Li (Theriogenology, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

Long-term increases in tree water-use efficiency across China are associated with CO2 and hydroclimatic variation - Yali Ding; Li Wen; Jingzhi Zhang; Wei Zhang; Hongsong Chen; Shanshan Song; Zongrui Lai; Jinxing Zhou; Guanghui Lin (Journal of Hydrology, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Liupao tea alleviates high-fat diet-induced obesity by re-establishing metabolic homeostasis of short-chain fatty acids and chenodeoxycholic acid - Yuru Tan; Xuancheng Wang; Anlong Song; Song Xu; Xueting Lin; Bao Yang; Jichu Luo; Ying Tong; Mingsen Wen; Xuan Guan; Peiting Li; Zhe Luo; et al. (Food Research International, 2026)

Enhanced transformation of sulfonamide antibiotics via chloride-enhanced catalytic polymerization in a NH2/MWCNT/PMS system - Yi Song; Yue Wang; Xiaona Liu; Bo Li; Wenjun Li; Wen Liu; Tianwei Qian; Dongye Zhao (Chemical Engineering Journal, 2026)

An AB2X5-type oxidizer by multi-ionic assembly for high-energy solid propellants - Hongyu Lv; Xiaoyu Feng; Xin Li; Te Ning; Hui Li; Wen Ao; Hongqi Nie; Siwei Song; Yi Wang; Qinghua Zhang (Chemical Engineering Journal, 2026)

Efficient directional conversion of chemical energy contained in organic matter into cellular biomass energy induced by different terminal electron acceptors during activated sludge process - Rui Liu; Wen-Jing Li; Shao-Yang Liu; Jin-Song Guo; Fang Fang; You-Peng Chen; Peng Yan (Chemical Engineering Journal, 2026)

Metal Bi-coupled chiral nanoscale structures enhance spin-polarized electrons to promote photocatalytic CO2 reduction - Dan Wu; Yanni Lang; Liang Xu; Qiyuexin Wang; Qiu Fu; Bingli Li; Xinye Zhao; Zhaoyi Yin; Yongjin Li; Dacheng Zhou; Yangke Cun; Zhiguo Song; et al. (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Real-time safety-critical obstacle avoidance and tracking control for UUV via NMPC-RCBF and ECBF-QP backstepping - Jingfei Ren; Yuanbao Chen; Hongjian Wang; Wen Yan; Xinyang Li; Shaozheng Song (Ocean Engineering, 2026)

Multi-omics revealed ecologically significant bisphenol A induces aberrant lipid metabolism in the marine clam - Xiaotian Wang; Zhengjia Wei; Jun Wang; Ruixin Ma; Wen Song; Futian Li; Pengfei Chu; Yufeng Shen; Long Zhu (Marine Environmental Research, 2026)

A review of machine learning applications in inland and nearshore water color remote sensing: from preprocessing to object detection and parameter estimation - Jiarui Shi; Zuchuan Li; Ge Liu; Chong Fang; Zhidan Wen; Yingxin Shang; Hui Tao; Sijia Li; Qiang Wang; Zijin Wang; Kaishan Song (Journal of Hydrology, 2026)

Deciphering the carrier potential of microplastics aged in freeze-thaw soils: Multiscale insights into mechanisms for antibiotic adsorption amplification - Wen-hao Yang; Jian-yong Wu; Kong-yan Luo; Ling-li Ma; Bin Yan; Jin-song Guo; Jie Zeng; Yi-zhi Pei; Jun-min Gao (Journal of Hazardous Materials, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Sex differences in the association between air pollution and obesity: a systematic review and meta-analysis - Xunziyin Wan; Wen Li; Edward Mullins; Fujian Song; Mark Woodward; Ana-Catarina Pinho-Gomes (Environmental Research, 2026)

Multiscale spatial heterogeneity of sedimentary organic carbon in the intertidal zone of the Yellow River Estuary - Jun Ma; Zihe Zang; Yinyin Feng; Xiao Liu; Ludan Zhao; Xuegang Li; Lilian Wen; Jiajia Dai; Jianwei Xing; Baoxiao Qu; Huamao Yuan; Liqin Duan; et al. (Estuarine, Coastal and Shelf Science, 2026)

All-inorganic perovskite CsPb2Br5/CdS heterojunction for photoelectrochemical dopamine detection - Yuting Zheng; Gang Zhao; Shanshan Liu; Yingli Guo; Baoshuai Liu; Wen Lu; Zhan Tao; Congping Song; Junhui Liu; Ruoping Li; Mingju Huang (Chemical Engineering Journal, 2026)

Multiphysics CFD analysis of packed bed adsorption of Ni(II) using MnO2-modified Hypericum rhizome-derived biochar: Batch and column approaches - Sheng Qian; Xiang Ao; Wei Zhang; Chenhao Song; Kaihong Wen; Dona Souliyathai; Xingyong Li; Na Liu; Liping Ma; Longlong Ma; Shijie Liu; Yubao Chen (Biomass and Bioenergy, 2026)

Lacticaseibacillus rhamnosus GR-1 Alleviates Escherichia coli-induced Autophagy-dependent Ferroptosis in Bovine Endometrial Epithelial Cells via FOXO1 Signaling - Xiangfu Wen; Mengsen Wang; Deyuan Song; Xiaohan Li; Meiyi Ren; Jinshang Song; Guowei Liang; Jing Chang; Ziyan Wang; Hao Li; Jia Cheng; Mingchao Liu (Probiotics and Antimicrobial Proteins, 2026)

Thermal-fluid-structure coupling analysis on plate-type fuel elements of high-flux reactors cooled by LBE under vibration and thermal loads - Yanming Jiang; Xiaochang Li; Bangyang Xia; Haisong Wang; Chong Chen; Ruifeng Tian; Zhiguang Song; Jiming Wen; Minyang Gui; Sichao Tan (Annals of Nuclear Energy, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Menaquinone-4 protects CD8+ T cells from ferroptosis to enhance anti-tumor immunity - Jiarong Wang; Wen Wang; Simiao Fan; Liyun Liang; Huaibin Hu; Zenqing Song; Yu Zhang; Jiamei Zhang; Wanying Xiao; Biyu Zhang; Yaxin Li; Liang Luo; et al. (Science China Life Sciences, 2026)

Effects of encapsulation length and grout stiffness on the load-bearing mechanics of rock bolts - Xinzhi Yang; Murat Karakus; Guangcheng Zhang; Guangqin Tong; Lian Wen; Ke Li; Minggang Song; Li Jiang (Journal of Mountain Science, 2026)

Wild Tibetan macaques employ a social sleep strategy to balance sleep needs and ecological pressures - Pei-pei Yang; Pritish Chakravarty; Wen-bo Li; Zi-tan Song; Xi Wang; Margaret C. Crofoot; Jin-hua Li (Animal Behaviour, 2026)

Particle size-dependent structure–activity relationship governing radical and electron-transfer pathways in peroxymonosulfate activation - Renjie Zhao; Xing Xu; Chunyi Sun; Xuguang Li; Beibei Liu; Wen Song; Tao Yan; Liangguo Yan; Yanxia Zhao (Water Research, 2026)

Dynamic embeddedness within the structural connectome characterizes macroscale functional organization of the human brain - Weiyang Shi; Congying Chu; Wen Li; Lingzhong Fan; Siyang Li; Luqi Cheng; Ming Song; Haiyan Wang; Zhenwei Dong; Shiqi Di; Yuejia Zhong; Yawei Ma; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Sediment heterogeneity shapes benthic microbial community assembly and co-occurrence network organization in the East China Sea - Lilian Wen; Jiajia Dai; Jinming Song; Xuegang Li; Huamao Yuan; Liqin Duan; Jun Ma (Marine Environmental Research, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Enhanced glyphosate biodegradation by heavy metal-tolerant microbial consortium QLBS in co-contaminated environment: Kinetics and metabolic pathways - Zeren Li; Mengyi Chen; Ziye Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Haoran Song; Huijie Zhou; Zhenyu Zhang; Bin Liang; Sandhya Mishra; Mohamed A. Ghorab; et al. (Journal of Cleaner Production, 2026)

Petrology and geochemistry of monzogranite and porphyritic granite in Laowan ore field of Qinling orogenic belt, China: Implications for gold and molybdenum mineralization - Ying-nan Chen; Cheng Xu; Wen-lei Song; Wei Fu; Ze-bang Yi; Zhi-xuan Han; Chengyu Zou; Jian-li Chen (Journal of Asian Earth Sciences, 2026)

Low-viscosity alginate-based hollow salt: A strategy for salty taste intensification and high-salt adverse effect reduction in vivo - Jingjing Li; Qian Jiang; Xinyi Jin; Fanhua Kong; Chengrong Wen; Xiaomeng Ren; Shuang Song (Food Research International, 2026)

Novel antioxidant peptides from jellyfish (Nemopilema nomurai) hydrolysate: identification, activity, and potential mechanisms - Wen Shen; Xueqin Wang; Xiaoxiao Liu; Rongfeng Li; Song Liu; Ronge Xing; Huahua Yu (Food Chemistry, 2026)

Effects of organic material addition on yield, nitrogen use efficiency, soil properties and physiological traits of grain crops: A meta-analysis - Feiyang He; Yaru Pang; Yueshan Song; Ran Xu; Daoyin Shi; Yisha Yang; Yapeng Li; Jiali Yang; Guorui Li; Weiyan Wang; Pengfei Shen; Xiaoxia Wen (European Journal of Agronomy, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Singlet oxygen-mediated water purification by Cu0 anchored amorphous FeOOH via oxygen activation - Yuwei Yang; Dong Li; Xiaoyu Zheng; Xuguang Li; Haiqiang Qi; Wen Song; Yunhui Zhang; Liangguo Yan (ENGINEERING Environment, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Sulfur-based mixotrophic denitrification with PCL/corncob for low C/N mariculture wastewater: Kinetics, microbial mechanism, machine learning optimization and continuous-flow validation - Liwei Wang; Haowei Wen; Xiefa Song; Weimin Yu; Teng Ma; Zuoliang Sun; Zheng Zhou; Huilin Wang; Dengpan Dong; Xueshu Han; Meng Li (Aquaculture, 2026)

Legacy effects of river floods intensify coastal water quality degradation - Chenmin Guo; Xuena Yang; Wen Wu; Xiuren Li; Zhaopeng Ren; Shengkang Liang; Xiaoxia Yu; Dehai Song (Ocean & Coastal Management, 2026)

Plant and microbial pathways driving soil carbon sequestration in dryland leguminous shrublands - Zi-Qiang Yuan; Chao Fang; Xin Song; Yi Wu; Feng Zhang; Xiang-Wen Fang; Guang-Qian Yao; Kevin Van Sundert; Feng-Min Li (Soil and Tillage Research, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

K-feldspar oscillatory zoning constraining efficient crystal fractionation in high-silica magma: A case study of the Dacaowu pluton, eastern China - De-Zhou Chen; Jian Li; Ming-Chun Song; Wen-Yan Cai; Chao Zhang; Zheng-Yang Zhang; Xu-Yan Bian (Journal of Geochemical Exploration, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

The role of water in REE mineralization of carbonatite systems: constraints from apatite and biotite volatiles - Jian-Hui Su; Xin-Fu Zhao; Johannes Hammerli; Sheng-Ren Chang; Xiao-Chun Li; Wen-Lei Song; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Causal discovery in urban data with temporal empirical dynamic modeling: The R package tEDM - Wenbo Lyu; Yangyang Lei; Wen Yi; Yongze Song; Xiao Li; Shaoqing Dai; Yiming Qin; Wufan Zhao (Computers, Environment and Urban Systems, 2026)

Emerging point-of-care technologies for bacterial pathogen detection - Wen Zhang; Yundong Hang; Sisi Zhan; Weiyao Song; Binxiao Li; Nan Chen; Min Lv (Journal of Zhejiang University-SCIENCE B, 2026)

ATP-dependent binding cassette transporter ClABCI6 promotes the expression of citrus yellow vein clearing virus via inhibiting salicylic acid pathway - Yaqin Song; Wen Ge; Cuiyun Lei; Yijie Li; Yang Han; Jiedan Xiao; Xinghua Qiao; Shixue Hu; Yan Zhou; Binghai Lou (Journal of Plant Research, 2026)

A calculation model on the minimum safe thickness of water-resisting rock mass for tunnel crossing active fault considering the fractal dimension and seismicity - Fan-meng Kong; Bing-hua Zhou; Xin Li; Zhao-di Han; Wen-song Wang (Applied Geophysics, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

Self-powered electron transfer on single-atom dual-reaction center: Achieving high-efficiency catalysis in oxidant-free systems - Wen Song; Enyu Zhao; Qinyi Wang; Pijun Duan; Xuguang Li; Tao Yan; Yanxia Zhao; Rui Feng; Yunhui Zhang; Yuanyuan Qu; Xing Xu; Liangguo Yan (Water Research, 2026)

Multiscale quantification of LNAPL redistribution processes in multiphase systems under groundwater table fluctuation influences - Zhijiang Yuan; Xiaosi Su; Hang Lyu; Chao Wang; Ningfei Li; Haiting Liang; Yazhi Song; Xiaofang Shen; Weihong Dong; Tiejun Song; Wen Yao (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

In situ reduction and recovery of Rh(III) from low-concentration solutions using iron-electrocoagulation flocs - Guofu Dai; Chao Peng; Chen Wang; Ying Cui; Song Wen; Jie Jiang; Chenlong Duan; Peng Li (Minerals Engineering, 2026)

Unraveling molecular interactions in coal-derived phenolic–aromatic systems: A decoupling principle governing assembly - Lan Yi; Dandan Luo; Miaomiao Feng; Li Guo; Hongming Fang; Yuncai Song; Yi Huang; Xiaoqin Wu; Wen-Ying Li (Fuel, 2026)

Collaria spinifila sp. nov.: A new species of myxomycete from the urban environment of Shanghai, China - Wen-Long Song; Min-Li Cai; Shuang-Lin Chen (European Journal of Protistology, 2026)

Morpho-molecular taxonomy and systematics of Suctoria (Ciliophora, Phyllopharyngea), with descriptions of four species from wetland habitats in China - Mingzhen Ma; Yiwen Wang; Wen Song; Honggang Ma; Ya Wang; Khaled A.S. Al-Rasheid; Weibo Song; Alan Warren; Zhe Wang; Lifang Li; Xiangrui Chen (European Journal of Protistology, 2026)

Multifunctional immune activators for effective antitumor immunotherapy of renal cell carcinoma - Ping Yan; Wenda Zhong; Shuangfeng Qin; Yiran Xu; Kailu Feng; Wangqin Chen; Xinyi Wang; Jiajin Wang; Zhengbo Li; Xudong Wang; Guangzhao Xu; Wen Sun; et al. (Chemical Engineering Journal, 2026)

Gliding arc plasma oxidative nitrogen fixation: A wide window of the optimal O2 content and non-monotonic dependences of NOx energy cost upon specific energy input - Ming Li; Xiao-Song Li; Xiao-Qiong Wen; Yong Xu; Jing-Lin Liu; Xiaobing Zhu; Ai-Min Zhu (Chemical Engineering Journal, 2026)

Quantifying scale effects in pile scour depth prediction for field applications via interpretable machine learning - Yang-Xin Zhou; Qing-Kai Song; Wen-Gang Qi; Li-Jing Yang; Xiao-Bing Lu; Fu-Ping Gao (Coastal Engineering, 2026)

Data-driven optimization of coagulation process for high-organic sea cucumber aquaculture wastewater: Interpretable ML modeling and robust TSS soft sensor development - Liwei Wang; Haowei Wen; Xiang Feng; Xiefa Song; Zuoliang Sun; Huilin Wang; Dengpan Dong; Meng Li (Aquacultural Engineering, 2026)

Sympathetic and Vagal Distribution in Hepatic Alveolar Echinococcosis and Its Clinical Correlation - Rongdong He; Zongding Wang; Zhihao Song; Lijiao Li; Li Sun; Hao Wen (Acta Parasitologica, 2026)

Terpenes from Platycladus orientalis and the evaluation of their potential anti-inflammatory activity - Yi-Fan Xie; Song-Xue Yang; Xue-Wen Wu; Bo Li; Si-Chen Song; Qiong Wei; Xing-Jie Zhang; Xiao-Li Li; Wei-Lie Xiao (Natural Product Research, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Analysis of the mechanism of MKK4 participating in heat stress response in Mytilus coruscus - Sisi Wei; Zhenqi Xin; Huajian Lin; Shiyong Huang; Lifang wen; Li Wu; Mingshan Song; Weifeng Wang; Baoying Guo (Marine Environmental Research, 2026)

Sulfonylurea receptor integrates calcium homeostasis and insulin-like peptide signaling to regulate energy metabolism and larval development in Hyphantria cunea - Yue-Cheng Zhao; Rong-Man Gou; Haneef Tariq; Xi-Lin Li; Lian-Sheng Zang; Li-Wen Song (Insect Biochemistry and Molecular Biology, 2026)

Converting low-quality construction waste into tough pavement material via biomimetic mineralization - Long Wen; Zhi Zhao; Yang Li; Yiran Wang; Jiaran Han; Chuan Qiu; Hui Yao; Runhua Guo; Kai Li; Xiaoyan Song (Chemical Engineering Journal, 2026)

Long-term succession and driving mechanisms of soil microbial communities in reclaimed farmland - Shuangjiao Liu; Xiangyu Min; Junying Li; Wen Song; Zhaoxinyu Liu; Xinju Li; Zhaozhen Cui; Jiale Zhang (CATENA, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

Microstructure and corrosion behavior of steel blades with powder copper inlay: Rediscovering a traditional chinese technique - Chaoqun Bu; Haotian Li; Xiaocen Li; Chunhui Zou; Difei Song; Zhongming Wen; Yue Zhou (Archaeological and Anthropological Sciences, 2026)

Effects of dietary emodin supplementation on the growth performance, serum biochemical parameters, and intestinal health of Pengze crucian carp (Carassius auratus var. Pengze) fed with high plant-protein diets - Jingen Xu; Song Zhang; Kaikai Shen; Jingjie Zhang; Luyao Xu; Shiqiang Du; Jianqin Li; Chungen Wen; Vikas Kumar; Mo Peng; Gang Yang (Frontiers in Marine Science, 2026)
Emodin supplementation could relieve the adverse impacts induced by a high plant-protein diet on intestinal health and growth performance of fish, while its application in Pengze crucian carp ( Carassius auratus var. Pengze) is lacking. Pengze crucian carp, an omnivorous fish, belongs to the freshwater Cyprinidae family. In this study, Pengze crucian carp were fed with a normal fishmeal diet (18% fishmeal, FM), a high plant-protein diet (4% fishmeal, HP), and four different emodin supplementation diets (HP diet supplemented with 25, 50, 75, and 100 mg kg −1 emodin); the feeding trial lasted 8 weeks. Compared with the FM group, the HP diet dramatically inhibited the growth performance of carp, while an appropriate addition of emodin could restore its growth performance. Emodin could improve carp morphology in terms of a higher value of the hepatosomatic index (HSI), the viserosomatic index (VSI), and the condition factor (CF), and increase the crude protein content concurrent with a lower crude lipid content in body compared with HP and FM groups. The HP diet induced the oxidative stress of carp, whereas emodin supplementation enhanced antioxidant parameters in serum and intestinal tissues together with a remarkable reduction of malondialdehyde content, thereby improving antioxidant status. The antioxidant property of emodin triggered the keap1-nrf2 signal pathway and then induced the overexpression of antioxidant genes ( cuznsod, cat , and gpx ) in intestinal tissue. Additionally, emodin attenuated the intestinal inflammation induced by the HP diet by suppressing the expression of pro-inflammatory-related factors ( tlr4, myd88, tnf-α, il-1β , and ifn-γ ) and upregulating anti-inflammatory-related factors ( tlr2, tgf-β , and il-10 ), followed by an improvement of the intestinal barrier function. Moreover, emodin supplementation could induce the transcriptional level of intestinal alkaline phosphatase ( iap ) through the pparγ-klf4 signal pathway and enhance IAP activity ultimately. In summary, a suitable amount of emodin can elevate the growth performance and improve the intestinal health of Pengze crucian carp fed a high plant-protein diet.

Notes on the life cycle of a new marine ciliate, Metafolliculina songi n. sp. (Protozoa, Ciliophora, Heterotrichea), with description of its infraciliature and phylogeny - Tingting Ye; Mingzhen Ma; Jemin Park; Mann Kyoon Shin; Yaohan Jiang; Wen Song; Lifang Li; Yong Chi; Xiangrui Chen (Marine Life Science & Technology, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

Impact of air pollutants on PDGFs mRNA in platelets and association of PDGFs mRNA expression level with acute myocardial infarction and major adverse cardiovascular events - Jichao Xie; Hankun Xie; Liang Xu; Fangyuan Liu; Qian Zhuang; Xianghai Zhao; Junxiang Sun; Pengfei Wei; Yunjie Yin; Yanchun Chen; Feifan Wang; Xu Han; et al. (Journal of Hazardous Materials, 2026)

Nutrient accumulation and redox conditions shape lake bacterial communities: A dual-medium assessment of closed coal-mining subsidence versus natural lakes - Shuo Li; Lei Zhang; Wen Ge; Yijie An; Ting Song; Feng Xu; Hua Cai (Journal of Environmental Chemical Engineering, 2026)

Insights into microscopic mechanisms of quaternary ammonium rosin-based amide resin in removing hexose alkaline degradation pigments - Xiao-Song Tang; Wei Wei; Yan-Hong Wei; Yu-Huan Lu; Xiang-Yi Tang; Wen Li; Fu-Hou Lei (Journal of Environmental Chemical Engineering, 2026)

Carbon quantum dots-loaded potassium titanate nanotubes efficiently activate peracetic acid through radical and non-radical pathways for pefloxacin degradation - Ruopu Bai; Chaofan Song; Li Ma; Jie Zhao; Guangcan Zhu; Hongyang Wang; Weiliang Sun; Wen Liu (Journal of Environmental Chemical Engineering, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

An experimental, theoretical and kinetic modeling study of ammonia borane combustion - Mengmeng Jia; Jiaxin Xie; Frederick Nii Ofei Bruce; Fei Qin; Yiwen Hu; Chong-Wen Zhou; Henry Curran; Taufiq Yap Yun Hin; Song Cheng; Yang Li (Fuel, 2026)

In situ generating gold nanosol SERS detection of pymetrozine with molecularly imprinted piezoelectric nanoprobes - Yuhao Song; Dan Li; Zhuxing Chen; Chongning Li; Guiqing Wen; Zhiliang Jiang (Food Bioscience, 2026)

Mechanistic insights into high-pressure-induced structural and thermal changes of wheat starch in flour and dough systems - Yung-Jia Chan; Ping-Hsiu Huang; Xiao-Song Huang; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Hydrocolloids, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Pioneering MXene membranes for next-generation desalination: A review of functionalization, hybridization, and chemical modifications - Aqsa Kanwal; Song Luo; Kaiyang Li; Solomon-Oshioke Agbedor; Xiaohe Tian; Bo Liu; Cuie Wen; Hong Wu (Desalination, 2026)

Umbilical Cord Mesenchymal Stem Cells and Wnt Pathway Modulation: A Novel Therapy for Liver Cirrhosis and Steatosis - Yanxuan Wen; Nouman Amjad; Omar Mukamab; Obed Boadi Amissah; Wei Xie; Peng Zhou; Aishi Song; Lan Wang; Jiaxing Li; Rongqi Huang; Sihao Deng; Zhiyuan Li (Tissue Engineering and Regenerative Medicine, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

The effect of hibernation on reproduction performance of Alligator sinensis, Chinese Alligator is not limited to maintenance of matural follicle, but also involves the fundamental resource of germ cells - Haitao Nie; Fuyong You; Shi Wang; Yunlu Xu; Shaofan Li; Jixiang Zhan; Yuan Zhang; Peng Liu; Yue Wen; Yongkang Zhou; Song Zhang; Xiaobing Wu (Animal Reproduction Science, 2026)

Tailoring plant protein-polysaccharide emulsions: Unveiling mechanisms from structure to function for advanced food systems - Qinqiu Zhang; Qing Zhang; Yijie Ren; Jingming Li; Song Miao; Wen Qin (Trends in Food Science & Technology, 2026)

The key predictive factors of arbuscular mycorrhizal fungi community spatial distribution in saline-alkaline meadow soils: Abiotic variables or hosts? - Lin Zhang; Yuqiang Wen; Mengmeng Zhang; Kun Li; Ruotong Wu; Ning Sun; Fuqiang Song; Tianle Xu (Rhizosphere, 2026)

Subspecies-specific epigenetic remodeling drives differential cold adaptation in geng/xian rice - Dong-Ao Li; Xiao-Long Xu; Yu-Hong Luo; Zu-Wen Zhou; Yong-Qing Qian; Qian Tang; Xi-Tong Zhu; Jia-Ming Song; Ling-Ling Chen (Plant Science, 2026)

Gibberellic acid enhances cadmium tolerance and metabolic resilience in Chlorella sp.: Physiological and untargeted metabolomic evidence - Fengyi Chang; Yingzhi Song; Yifei Leng; Xi Zou; Wen Xiong; Zhu Li (Journal of Environmental Sciences, 2026)

A molecular-level insight into the synergistic separation of acidic and basic heteroatoms from coal tar: A strategy for fuel upgrading - Dandan Luo; Lan Yi; Jialing Chen; Hao Luo; Yuncai Song; Yi Huang; Xiaoqin Wu; Wen-Ying Li (Fuel, 2026)

Sheep milk protects while cow milk exacerbates DSS-induced colitis by differentially modulating the Akkermansia–short chain fatty acids–barrier axis - Naseer Ahmad; Zhongshi Zhu; Fu Xingwei; Li Danni; Wen Qinghua; Lei Zhang; Hao Yuan; Yuxuan Song (Food Bioscience, 2026)

Multi-objective optimization of solid-liquid stirred tank with fractal impeller and baffle for food processing - Deyin Gu; Tao Peng; Changshu Li; Li Wen; Yinghua Song; Haifeng Gong (Food and Bioproducts Processing, 2026)

Ecotoxicological insights into UV-P-induced immunotoxicity and bacterial infection risk in marine medaka (Oryzias melastigma) - Li Wu; Mingshan Song; Lifang Wen; Sisi Wei; Zhenqi Xin; Pengzhi Qi; Xiaojun Yan; Yongjiu Xu; Baoying Guo; Weifeng Wang (Environmental Research, 2026)

Allocation equality of battery replacement subsidy for electric buses: Evidence from provinces and cities in China - Yanyan Tang; Zongguo Wen; Song Hu; Yaoming Li; Minyan Lu (Energy Policy, 2026)

Behaviorally inspired by blue-whale throat-pleats during filter feeding: A thermoresponsive hydrogel for achieving efficient solar-driven cyclic water release and purification - Yan-Shu Xiong; Mei Li; Tanli Lu; You-Ya Sun; Hai-Qin Lu; Wen Li; He Liu; Zhanqian Song (Chemical Engineering Journal, 2026)

Adaptation and enhanced removal of moxifloxacin stress in Chlorella sp. under gibberellin regulation: physiological and metabolomic evidence - Yingzhi Song; Wen Xiong; Zhu Li; Fengyi Chang (Bioresource Technology, 2026)

Low-temperature mineral engineering stabilizes anchored cobalt sites for ultrafast antibiotic destruction via electron transfer-driven radical/nonradical synergy - Liyao Ren; Ran Liu; Runbin Zeng; Lingling Cao; Wenyu Wang; Xuguang Li; Xing Xu; Yanxia Zhao; Liangguo Yan; Yanfei Li; Wen Song (ENGINEERING Environment, 2026)

The combined effects of drought and defoliation on non-structural carbohydrates in different organs of Chinese pine - Citian Li; Yihang Zhu; Xiangmin Liang; Xinyi Guo; Changhui Peng; Tong Li; Jiayi Tang; Cong Liu; Xin Li; Xiaolu Zhou; Hanxiong Song; Zelin Liu; et al. (Journal of Plant Research, 2026)

Synergistic virulence of H9N2 AIV and APEC co-infection in laying hens involves a critical role for macrophage-mediated hyper-inflammation via the MAPK/NF-κB axis - Jinjie Han; Wenchi Chang; Zhaoyue Jing; Dong Xiao; Tiantian Ji; Junyang Fang; Mengzhao Song; Wei Li; Jingyu Wang; Wen Deng (Veterinary Microbiology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

Potential impact of seamount on the mild oxygen minimum zone (OMZ) in the Western Pacific - Jun Ma; Lilian Wen; Xuegang Li; Kuidong Xu; Jiajia Dai; Yi Sun; Guorong Zhong; Detong Tian; Huamao Yuan; Liqin Duan; Jinming Song (Progress in Oceanography, 2026)

Dysregulation of hepatopancreatic microRNAs in Penaeus vannamei in response to Ecytonucleospora hepatopenaei (EHP) infection: Implications for innate immunity and metabolic function - Li-Guo Yang; Lei Feng; Li-Yan Ma; Xue-Feng Song; Jia-Yuan Xu; Bian-Bian Zhang; Wen-Hong Fang; Xin-Cang Li (Journal of Invertebrate Pathology, 2026)

A wind energy-biomass-coal synergistic system for producing multiple products based on the carbon and nitrogen cycles and its optimization - Yipeng Zhang; Zhongwen Song; Shuo Wen; Ran Li; Guilian Liu (Journal of Cleaner Production, 2026)

Experimental and numerical study on oxygen-enriched NH3/H2/CO/air premixed combustion at elevated temperature and pressure - Ningning Li; Haoxin Deng; Xiaoping Wen; Fahui Wang; Jun Song; Guoyan Chen (Journal of Cleaner Production, 2026)

Enhanced water decontamination by goethite-Cu0 activating oxygen: The dominance of valence state in reactive oxygen species generation - Xinyi An; Haiqiang Qi; Wen Song; Xuguang Li; Rongyao Wang; Yanxia Zhao; Liangguo Yan (Journal of Environmental Chemical Engineering, 2026)

Satellite images reveal reduced lake chlorophyll concentration and eutrophication in China - Sijia Li; Xiangming Xiao; Ge Liu; Zhidan Wen; Chong Fang; Yingxin Shang; Hui Tao; Lele Zhang; Yong Li; Qiang Wang; Haoyun Zhou; Kaishan Song (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Unraveling the thermal decomposition kinetics of triethyl phosphite - Frederick Nii Ofei Bruce; Xin Wang; Xin Bai; Minjie Wen; Dongping Chen; Song Cheng; Henry Curran; Yang Li (Fuel, 2026)

Efficient solar desalination and Li+ adsorption by topological aerogel network of cellulose nanofiber skeleton with poly(vinyl alcohol) chains and carbon nanotube - Jing Li; Yujuan Ma; Yanfei Li; Wen Song; Xuguang Li; Liangguo Yan (Desalination, 2026)

A hepatocyte targeted and hypoxia responsive host-guest drug delivery system for the treatment of liver ischemia reperfusion injury - Jiansen Lu; Juanjuan Li; Hao Pan; Hongliang Liang; Tian Han; Weiye Zhang; Meng Fan; Song Zhang; Dongsheng Guo; Kerang Wang; Wen Hou; Zhongyang Shen (Chemical Engineering Journal, 2026)

Characteristics and driving factors of oceanic oxygen minimum zone (OMZ) in the context of global change - Jun Ma; Jinming Song; Xuegang Li; Huamao Yuan; Liqin Duan; Jiajia Dai; Lilian Wen (Science China Earth Sciences, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Numerical investigation of excitation mechanism and response behavior of flow-induced vibration in plate-type fuel elements of high-flux reactors cooled by LBE - Yanming Jiang; Bangyang Xia; Chong Chen; Xiaochang Li; Hai Zhao; Ruifeng Tian; Zhiguang Song; Jiming Wen; Sichao Tan (Annals of Nuclear Energy, 2026)

Changes in soil multifunctionality under different grazing intensities in spring are mainly influenced by the stability of soil biota networks - Hansen Gao; Rui Wang; Yali Yin; Wen Zhao; Wenxian Zheng; Xueao Song; Haiqiang Liu; Shixiong Li (Agriculture, Ecosystems & Environment, 2026)

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Dietary α-ketoglutarate improves the feed efficiency and growth performance of Chinese mitten crab (Eriocheir sinensis) fed low-protein diets by modulating protein metabolism and intestinal health - Jinping Li; Long He; Song Wang; Wen Li; Xiaodan Wang; Erchao Li; Jianguang Qin; Liqiao Chen (Aquaculture, 2026)

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Oxalate-tailored microenvironment engineering of zero-valent copper for enhanced molecular oxygen activation - Wen Song; Yuwei Yang; Xuguang Li; Liangguo Yan; Haiqiang Qi; Xing Xu; Yunhui Zhang; Yanxia Zhao (Water Research, 2026)

Long-term recovery of aggregate-associated organic carbon in reclaimed mine soil - Wen Song; Zhaoxinyu Liu; Xinju Li; Xiangyu Min; David O'Connor; Junying Li (Soil and Tillage Research, 2026)

Functional analysis of heat shock protein 70 genes in Tetranychus truncatus reveals their critical role in cross-tolerance to heat and acaricide stress - Qin-Zhe Sun; Lei Liu; Huan Liu; Xing Xiang; Li-Wen Song; Sen-Shan Wang (Pesticide Biochemistry and Physiology, 2026)

From AI modelling to validation: A 10-day pipeline for potential lead compounds validation - Bin Chen; Yuan Hu; Wen He; Guo Li; Ruiqi Liu; Jiawei Li; Xiujuan Li; Lingling Wei; Aiguo Gu; Song Yang; Changyang Chen; Xiushi Song; et al. (Pesticide Biochemistry and Physiology, 2026)

Cleavage of Beclin 1 by metacaspase 1 activates antiviral autophagy in plants - Rujian Hu; Qinglin Pi; Meng Yang; Wen Song; Zhihao Jiang; Chenchen Zhong; Huanxi Han; Cheng-Gui Han; Yongliang Zhang; Dawei Li (Molecular Plant, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Iron-manganese inputs shape the coupling between deposit morphology and microbiome during the early-stage corrosion on cement mortar-lined pipe walls under drinking-water conditions - Weiying Li; Xin Song; Yue Wang; Duo Wen; Yu Zhou; Dawei Zhang (Journal of Environmental Management, 2026)

A novel method for remote sensing phycocyanin leveraging optical classification and an integrated machine learning algorithm - Shizhuo Liu; Chong Fang; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Sijia Li; Hui Tao; Zhaojiang Yan; Lili Lyu; Yunfeng Lyu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

Insight of catalytic desorption of CO2-rich amine solution over dealuminated HZSM-5 modified with metal oxides - Wenqian Song; Yuxin Wen; Guojun Kang; Wenqing Lv; Dekang Li; Haoquan Hu; Lijun Jin; Shijian Lu; Zhong Yan; Pengfei Liu (Fuel, 2026)

Do green tax policies shape China's household consumption structure? A production-side perspective - Feng Wen; Kun Wu; Wenfu Wang; Xue-Li Chen; Dandan Liu; Malin Song (Energy Policy, 2026)

All-in-one self-floating cellulose aerogels for simultaneous solar interfacial evaporation and catalytic degradation - Yanli Fu; Wen Song; Jing Li; Xuguang Li; Liangguo Yan (Chemical Engineering Journal, 2026)

Novel senescence inducer ICA-11c, a derivative of icaritin, YAP-dependently suppresses hepatocellular carcinoma cells - Hong-fei Chen; Shuai Shen; Shuang-li Wang; Li Ye; Ji-chong Li; Wen-li Cao; Zi-lin Hou; Jian-huan Jia; Qing-bo Liu; Guo-dong Yao; Shao-jiang Song (Chemico-Biological Interactions, 2026)

A meta-analysis of impacts of mulching under different agricultural environments on soil aggregates and organic carbon - Feiyang He; Hongtao Zhang; Daoyin Shi; Guorui Li; Yueshan Song; Yaru Pang; Yuqing Meng; Pengfei Shen; Xiaoxia Wen (Plant and Soil, 2026)

Distinct mechanisms of soil organic carbon formation in natural and legume-based grasslands on the Loess Plateau, China - Zi-Qiang Yuan; Chao Fang; Tian Ma; Jiu-Ying Pei; Xin Song; Guang-Qian Yao; Jordi Sardans; Josep Penuelas; Xiang-Wen Fang; Feng-Min Li (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Fast estimation of the carbon footprint for shipbuilding based on compensated gross tonnage - Wen-Cai Tang; De-Ning Song; Jing-Hua Li; Yu-Guang Zhong (Regional Studies in Marine Science, 2025)

A plasma membrane receptor complex mediates early heat-responsive signaling to trigger nuclear transcriptomic reprogramming in Arabidopsis - Jing Li; Shifeng Wu; Kun Wang; Yang Xu; Xiaoyan Zhang; Xinru Li; Wen Song; Jian-Min Zhou; Zhizhong Gong; Shuhua Yang; Yanglin Ding (Molecular Plant, 2025)

Seasonal and diurnal variations of pCO2 from reservoirs and lakes in Northeast China - Shiwei Liu; Zhidan Wen; Ge Liu; Yingxin Shang; Junbin Hou; Hui Tao; Chong Fang; Sijia Li; Xiangfei Yu; Jiarui Han; Jiping Liu; Kaishan Song (Journal of Hydrology, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Binder-free in situ construction of an asymmetric sandwich membrane–electrode integrated structure for efficient alkaline water electrolysis - Junqiang Wu; Wen Song; Wenlei Liu; Xi Du; Kunmei Su; Haifeng Shi; Zhenhuan Li (Journal of Environmental Chemical Engineering, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Low-temperature efficient catalytic combustion of toluene over Ce-doped α-MnO2: Synergistic Ce-Mn dual redox cycling for enhanced adsorption, oxidation, and CO2 desorption - Weina Song; Xinglong Li; Chuanbiao Zhu; Yongli Dong; Zichao Li; Zhibin Wen; Xiaotong Wang; Wei Li (Journal of Environmental Chemical Engineering, 2025)

Joint influences of ENSO and East Asian winter monsoon on the Hadley circulation in the Asian monsoon domain - Mengying Du; Yan Li; Juan Feng; Qi Wen; Wenjun Song; Zhilan Wang (Global and Planetary Change, 2025)

Tracing antibiotics in food through dual-mode ratiometric luminescence core-shell nanoparticles - Xin Gao; Qi Li; Hanxiang Wu; Srushti Gadiyaram; Hongli Wen; Abdur Raheem Aleem; Wei Song; Lin Yu; Deshmukh Abdul Hakeem (Food Chemistry, 2025)

The characteristic changes of bovine casein hydrolyzed by Bacillus velezensis DB219 and its mutant E361I milk-clotting enzyme - Yao Zhang; Chanchan Wen; Jingna Yang; Yuanfeng Wu; Xiaofeng Liu; Manfei Li; Xinjie Song; Luhua Zheng (Food Bioscience, 2025)

Comprehensive profiling of quinolone antibiotics in the Bohai Sea: Occurrence, source apportionment, and environmental risks - Lilian Wen; Jiajia Dai; Jun Ma; Xuegang Li; Huamao Yuan; Liqin Duan; Chuanting Zhao; Jinming Song (Environmental Pollution, 2025)

Sulfonamides as emerging contaminants in China's marginal seas: Distribution, Usage, and Residues - Jiajia Dai; Jinming Song; Lilian Wen; Jun Ma; Huamao Yuan; Xuegang Li; Liqin Duan; Qidong Wang (Continental Shelf Research, 2025)

Fatigue-resistant, self-healing and antibacterial poly(ionic liquid) gel multichannel sensors for underwater early warning and deep learning-assisted infant monitoring - Xiaoli Liang; Longzhang Niu; Jinhan Song; Zhoujing Chen; Hongwang Qu; Didi Wen; Yuqi Li; Lina Niu; Yongkang Bai (Chemical Engineering Journal, 2025)

Gradient lithiophilic metal foam via magnetic sputtering deposition in dendrite free lithium metal anodes - Wenlong Liu; Jianzong Man; Xiaodong Sun; Ning Zhang; Haibang Zhang; Kun Liu; Zhongsheng Wen; Song Li; Juncai Sun (Chemical Engineering Journal, 2025)

Study on the effects of peppermint and dry ginger odor environments on human thermal sensation - Yulong Song; Zhen Tong; Xinran Wen; Mengwei Li; Hongyu Guan; Songtao Hu (Building and Environment, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Partial wool organic fertilizer substitution mitigate ammonia and nitrous oxide emissions and facilitate savoy cabbage growth - Jiahui Wang; Cun Sun; Shuyan Li; Yixun Shi; Hui Li; Jingchen Song; Jing Yuan; Wenhai Luo; Guoxue Li; Wen Liu; Guoxiang Bu; Hongbin Wang; et al. (Applied Soil Ecology, 2025)

Illuminating Fe3+ spatiotemporal dynamics in Alzheimer's disease via a lipid-activated ultrasensitive probe - Ruixi Li; Meixue Wang; Qiuyi Song; Donghui Liu; Liangmeng Jiang; Yuanhui Wen; Lei Chen; Shuaishuai Chen; Dingyan Lu; Jinrong Zheng; Ting Liu (Analytica Chimica Acta, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Measuring the spatial structure of cold island and carbon sequestration networks and their interactions in urban agglomerations: a motif and multilayer network analysis perspective - Chen Qu; Jia Xu; Wen Li; Song Shi; YuCen Zhai (Sustainable Cities and Society, 2025)

Corrigendum to “Susceptibility, resistance risk and sublethal effect to fenmezoditiaz, a novel mesoionic insecticide, in the brown planthopper, Nilaparvata lugens” [ Pesticide Biochemistry and Physiology 213 (2025) 106540] - Yan-Chao Zhang; Xiao-Yan Song; Yu Li; Zi-Xin Zhuang; Wen-Nan Ye; Zhao-Yu Liu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

Hydrochemical characteristics and circulation pattern of fault-type geothermal water in karst region: A case study in western Yunnan, China - Chuan Wen; Wenping Mu; Qiang Wu; Zhen Yang; Rong Li; Yubing Song; Hui Tan (Geothermics, 2025)

Impact-induced magnetite is widespread on the near and far sides of the moon - Ronghua Pang; Chen Li; Yang Li; Zhuang Guo; Dongsheng Song; Haifeng Du; Luyang Wang; Sizhe Zhao; Yuanyun Wen; Xiang Li; Junhu Wang; Xiongyao Li; et al. (Earth and Planetary Science Letters, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Biotransformation of oleanonic acid by circinella muscae to produce novel 11,12-epoxy-13,28-lactonized derivatives and their anti-neuroinflammatory activity - Wei Liu; Li Yang; Liu-Tong Guan; Jia-Hui Wang; Yao-Yu Liu; Yan Song; Jian-Lin Li; Wen-Li Wang; Bo-Yi Fan; Guang-Tong Chen (Natural Product Research, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

High efficacy of (Z)-ligustilide in inhibiting postharvest apple ring rot and its antifungal mechanism against Botryosphaeria dothidea - Xiao-Yi Tong; Li-Li Song; Hui-Fang Du; Ya-Hui Zhang; Jia-Wen Shou; Cai-Juan Zheng; Wen-Bin Gao; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu; Fei Cao (Postharvest Biology and Technology, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Interfacial electron transfer in Co Fe catalysts drives self-sustained tetracycline degradation and radical enhancement in low-oxidant system - Wen Song; Lingling Cao; Runbin Zeng; Wei Hong; Liangguo Yan; Haiqiang Qi; Yanfei Li; Xin Tan; Xuguang Li (Journal of Water Process Engineering, 2025)

Determination of site-specific natural background values for soil potentially toxic elements supported by partial least squares regression method - Li-Mei Cai; Ao Wang; Song He; Yi-Meng Fan; Han-Hui Wen; Jie Luo; Lai-Guo Chen (Journal of Hazardous Materials, 2025)

Heavy metal exposure and cognitive impairment: An umbrella review of meta-analyses - Yueqing Song; Yantong Chen; Zhushan Fu; Yi Wen; Weiyue Zhao; Jia Li; Haocheng Wang; Yinke Du; Yu Deng (Journal of Hazardous Materials, 2025)

Hierarchical janus membranes via interfacial engineering: Dual anti-fouling and anti-wetting for sustainable desulfurization wastewater reclamation - Wen Wang; Zixuan Xu; Silan Li; Song Han; Liqiang Qi (Journal of Environmental Chemical Engineering, 2025)

Cr-induced built-in electric field engineering in Ni3S2/VS heterojunctions: Achieving a catalytic leap for oxygen evolution reaction - Yu Zhong; Yijun Wu; Yongmin Ying; Jiang Wu; Huanan Wang; Le Chen; Jili Wen; Chaoen Li; Jian Song; Yan Li (Journal of Environmental Chemical Engineering, 2025)

Novel construction of Z–scheme g–C3N4/PDI organic photocatalyst for excellent sulfamethoxazole degradation rate in water - Yali Song; Ziyan Li; Cairong Yang; Xiaoyu Wen; Long Huang; Xiaojing Zhang; Yongpeng Ma; Qiong Wang; Hongzhong Zhang (Journal of Environmental Chemical Engineering, 2025)

Odor emissions and humification during composting of pig manure and cornstalks: Role of mixing proportions - Yixun Shi; Xuhan Gu; Jingchen Song; Hui Li; Cun Sun; Jiahui Wang; Jijin Li; Wen Liu; Guoxiang Bu; Hongbin Wang; Shuyan Li (Journal of Environmental Chemical Engineering, 2025)

Myxomycetes in urban green space in subtropical China: Spatiotemporal patterns override forest type effects - Wen-Long Song; Di Lin; Min-Li Cai; Xia Chen; Qun Dai; Shuang-Lin Chen (Fungal Biology, 2025)

Network pharmacology and molecular docking reveal the potential mechanisms of edible Fritillariae cirrhosae bulbus in alleviating asthma-related symptoms: A transcriptomics-supported study - Lingyi Liu; Ruisi Zhu; Yuzhi Luo; Lingli Li; Sha Wen; Songyuan Xia; Yajing Ma; Huixin Song; Weifeng Li; Xiaofeng Niu (Food Bioscience, 2025)

D-tagatose biotransformation from lactose by lactase and recombinant Bacillus subtilis expressing l-arabinose isomerase, and the product separation, purification and crystallization - Xin Wen; Huibin Lin; Guangwen Liu; Yuhang Ning; Yilin Ren; Can Li; Chengjia Zhang; Nannan Dong; Jianqiang Lin; Xin Song; Guoqiang Zhuang; Jianqun Lin (Food Microbiology, 2025)

Corncob-inspired synthesis of carbon fiber/PO43− intercalated NiFe-LDH hybrid for simultaneously improving flame retardancy and mechanical properties of epoxy resin composites - Yuanmeng Lou; Zhaotian Ba; Zhaodi Yuan; Jian Li; Cui Li; Lili Ma; Xiujuan Wang; Xin Wen; Pingan Song (Chemical Engineering Journal, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Tailoring key intermediates and interfacial water at Ag92Ru8 aerogel toward sustainable ammonia synthesis from nitrate - Junjie Chen; Xiaomei Xing; Sisi Wen; Mengyuan Li; Di Liu; Wenji Jiang; Xinyi Shao; Ruikai Qi; Yumei Yang; Ming Mu; Zheng-jie Chen; Bing Zhao; et al. (Chemical Engineering Journal, 2025)

N deposition affects litter decomposition in evergreen broad-leaf forests by reducing soil enzyme activities and altering the structure of microbial communities - Jinmei Xing; Wen Chen; Chenggong Song; Xiaodong Li; Qian Wang; Yali Song (Plant and Soil, 2025)

Association Between Primary Dysmenorrhea and Mental Health Traits: A Study Based on Multi-Phenotype Correlation Network and Mendelian Randomization Analysis in Female College Students - Huiting Jiangzhou; Hanpeng Xu; Yanqin Wen; Zeyi Guan; Yang Zheng; Xuemin Jian; Weichen Song; Aamir Fahira; Jinmai Zhang; Qing Zhang; Ying Zhao; Manfei Zhang; et al. (Phenomics, 2025)

Linking two types of breccias to sediment-hosted stratiform copper (SSC) and iron oxide-copper-gold (IOCG) deposits in the Kangdian metallogenic belt, SW China - Xue-Qing Yin; Xin-Fu Zhao; Zhi-Kun Su; Hai-Tao Lin; Zhi-Min Zhu; Wen-Lei Song; Martin Yan Hei Li; Kui-Dong Zhao (Mineralium Deposita, 2025)

Unveiling the characteristics of fluoroquinolones in China marginal seas: Spatiotemporal distribution, environmental fate, and mass inventory - Lilian Wen; Jiajia Dai; Jinming Song; Jun Ma; Xuegang Li; Huamao Yuan; Liqin Duan; Qidong Wang; Chuanting Zhao (Marine Pollution Bulletin, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Susceptibility, resistance risk and sublethal effect to fenmezoditiaz, a novel mesoionic insecticide, in the brown planthopper, Nilaparvata lugens - Yan-Chao Zhang; Xiao-Yan Song; Yu Li; Zi-Xin Zhuang; Wen-Nan Ye; Zhao-Yu Liu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2025)

Triple binding pockets of AtSDH: Reduced affinity underpins SDHI- resistance in Alternaria tenuissima - Bin Chen; Ruiqi Liu; Wen He; Yuan Hu; JiaWei Li; Xiujuan Li; Aiguo Gu; Song Yang; Changyang Chen; Xiushi Song; Changjun Chen; Wenyong Shao (Pesticide Biochemistry and Physiology, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

Urinary monohydroxylated polycyclic aromatic hydrocarbons among healthy elderly in the China BAPE study: Exposure characteristics, influencing factors, and health risks - Jiankun Qian; Xiaojie Guo; Chenglei Qi; Peijie Sun; Chenfeng Li; Chenlong Li; Kangning Cao; Yibo Xu; Huimin Ren; Jiran Zhang; Yu Wang; Shan Bao; et al. (Journal of Hazardous Materials, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Transmembrane uptake of polystyrene nanoplastics mediated by aquaporin in tartary buckwheat: Physiological consequence and genomic mechanism - Yu-Kang Hou; Shuo Gao; Qiang Lai; Wen-Rui Lu; You-Bao Cai; Ya-Wen Yuan; Si-Yuan Yao; Hong-Yan Tao; Li-Zhe An; You-Cai Xiong; Yuan Song (Journal of Hazardous Materials, 2025)

Effects of hyperthermophilic composting on antibiotic resistance and environmental health risk of antibiotic treated cow manure - Ting Hu; Wen Song; Guangdong Wang; Xinyue Zhang; Dan Li; Lu An; Bin Luo; Jun Wang; Xun Qian; Jie Gu (Journal of Hazardous Materials, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Effect of chlorogenic acid on the quality of golden pomfret during refrigerated storage: Predictive model using artificial neural network - Ning Yang; Shitong Wen; Chuan Li; Qian Li; Longteng Zhang; Xue Song; Lulu Zhu (Food Control, 2025)

Distribution and partitioning behavior of phthalate esters (PAEs) and non-phthalate ester plasticizers (NPPs) in a home from northern China - Chun-Yan Huo; Li-Yan Liu; Liang Wang; Yu Sun; Shuang Du; Li Song; Yong-Yu Li; Xin-Hong Wang; Wen-Long Li (Environmental Pollution, 2025)

Depth-dependent accumulation and controls of particulate and mineral-associated organic carbon in Inner Mongolian grasslands - Haojun Zheng; Shuai Zhang; Guocheng Wang; Mingming Wang; Yunlong Hu; Yuchen Wei; Kang Xu; Haigang Li; Shixiang Zhao; Biao Zhu; Jinfeng Chang; Zhou Shi; et al. (Science China Earth Sciences, 2025)

Evolution of the Rich Club Properties in Mouse, Macaque, and Human Brain Networks: A Study of Functional Integration, Segregation, and Balance - Xiaoru Zhang; Ming Song; Wentao Jiang; Yuheng Lu; Congying Chu; Wen Li; Haiyan Wang; Weiyang Shi; Yueheng Lan; Tianzi Jiang (Neuroscience Bulletin, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Responses of multi-trophic microbial communities to altered precipitation affected soil respiration in coastal wetlands - Yuqi Zhou; Xinge Li; Shuzhen Li; Xiongfeng Du; Zheng Zhang; Zhaojing Zhang; Kai Feng; Xi Peng; Wen Song; Song Gu; Pengpeng Duan; Baohua Xie; et al. (Applied Soil Ecology, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

Improving chili pepper LAI prediction with TPE-2BVIs and UAV hyperspectral imagery - Haiyang Zhang; Guolong Wang; Fanfan Song; Zhaoqi Wen; Wenwen Li; Ling Tong; Shaozhong Kang (Computers and Electronics in Agriculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Role of UVA-driven cellular senescence via mTOR activation in dihydrotestosterone-induced hair loss in androgenetic alopecia mouse model - Dongfan Wei; Hongyan Zhang; Wen Xu; Beilei Zhang; Li Zhang; Lan Lan; Yujie Li; Yetan Shi; Xiuzu Song (Journal of Photochemistry and Photobiology B: Biology, 2025)

Se improves Cd tolerance by modulating phytohormone signaling and primary metabolism in strawberry - Fei Wu; Wen Li; Xiaoxiao Liu; Weimin Li; Xiaoyu Guo; Yuan Zhao; Haojing Zhang; Qianqian Song; Fei Liu; Ping Zhang; Min Wu; Jin Xu (Journal of Hazardous Materials, 2025)

The microhabitat regulation of moisture - ventilation mediated microbial carbon metabolism in response to humic acid formation during chicken manure and food waste composting - Liqin Wang; Xinzi Wen; Yu Deng; Zimin Wei; Jie Li; Caihong Song (Journal of Environmental Management, 2025)

The potential electrical transmission mechanism of strengthening petroleum hydrocarbon biodegradation by KOH-modified biochar - Wen Li; Quanwei Song; Jufeng Li; Xianyuan Du; Jiacai Xie; Zhongyuan Li; Xing Chen; Nan Zhao; Feng Ju; Hao Ling (Journal of Environmental Chemical Engineering, 2025)

Petrogenesis of rodingite in the Ngamring massif, Xigaze ophiolite (Southern Tibet): Implications for the evolution of the Neo-Tethys Ocean - Gui-Fang Ou; Zhong’ao Liu; Wen-Yong Duan; Guang-Ming Sun; Xu-Ping Li; Song-Jie Wang (Journal of Asian Earth Sciences, 2025)

In-situ synthesized Fe-SSZ-13 zeolite with superior performance for NO oxidation over a wide temperature range - Sai Zhang; Peng-Song Li; Jia-Xin Zhang; Yuan-Hang Qin; Zhen Chen; Li Yang; Tielin Wang; Cun-Wen Wang (Fuel, 2025)

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Preparation of a vegetable-oil film-type emulsion dust suppressant and adsorption performance study on road dust surface in open-pit coal mines - Shiyang Xia; Ziling Song; Xiaoliang Zhao; Zhen Gao; Yu Wen; Yanning Li (Environmental Research, 2025)

Optimizing fertilizer N rates to maximize the N legacy effects of peanut for obtaining high wheat yields with low N surplus in a peanut-wheat rotation - Wenhai Huang; Jun Zou; Ying Yang; Jørgen Eivind Olesen; Yuhao Yang; Robert M. Rees; Hongbao Sun; Shuaijie Shen; Wenjie Li; Li Zhang; Haoyu Zheng; Zhenwei Song; et al. (European Journal of Agronomy, 2025)

Schwann cells transplantation improves nerve injury and alleviates neuropathic pain in rats - Wen-jun Zhang; Xi Li; Jun-xiang Liao; Dong-xia Hu; Song Huang (Purinergic Signalling, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Biodegradation of Neonicotinoid Insecticides Thiacloprid and Thiamethoxam by Microorganisms: Metabolic Process, Metabolic Enzymes and Toxicity Assessments of their Metabolites - Yun-Xiu Zhao; Li-Wen Chen; Yue Shen; Hao Chen; Zi-Yan Yu; Chao Xing; Yi-Fei Chen; Peng-Fei Zhai; Jiu-Wei Song; Ju Yang (Current Microbiology, 2025)

Bioinformatic Analysis of the Significance of the KIR2DL4 Gene in Recurrent Implantation Failure - Xin-Xian Zhang; Zhi-Chao Zhang; Yu-Shan Liu; Li Zhou; Yu-Qin Hu; Cai-Hong Zhang; Wen-Hui Song; Xiao-Hua Wu (Biochemical Genetics, 2025)

Trends and innovations in ocean mesoscale eddy studies via satellite observation: a bibliometric review - Fan Xu; Zhiqiang Wen; Huimin Wang; Tong Li; Xiufang Song; Hao Peng (Frontiers in Marine Science, 2025)
Ocean mesoscale eddies play a crucial role in global ocean circulation, heat transport, and biogeochemical processes. Satellite altimetry has become a foundation in observing and analyzing these dynamic phenomena, offering high-resolution, global coverage of sea level anomalies. This bibliometric review investigates the trends and innovations in mesoscale eddy research using satellite altimetry data over the past decades. Based on Web of Science, VOSviewer, and CiteSpace, we analyze publication growth, geographical and institutional contributions, keyword co-occurrence, and citation networks. Key innovations such as advanced data assimilation, multi-satellite collaboration, and integration with machine learning models are highlighted. Finally, we discuss future opportunities of next-generation altimetry missions like SWOT for mesoscale eddy dynamics. This review serves as a comprehensive guide for researchers exploring mesoscale eddies and satellite-based ocean observations.

Quantifying the nonlinear effects of urban-rural blue-green landscape combination patterns on the trade-off between carbon sinks and surface temperature: An approach based on self-organizing mapping and interpretable machine learning - Chen Qu; Jia Xu; Wen Li; Song Shi; Baozhu Liu (Sustainable Cities and Society, 2025)

Virus-host interactions and their effects on the prokaryotic community in thermokarst lakes - Yutong Song; Guibiao Yang; Pandeng Wang; Xiaoqing Luo; Jian-Yu Jiao; Zhihu Zheng; Luyao Kang; Dianye Zhang; Ziliang Li; Wei Zhou; Xuning Liu; Lili Han; et al. (Science Bulletin, 2025)

The combined inhibitory effect of potassium permanganate and modified polyacrylamide on the flotation behavior of antimonite and arsenopyrite - Jiaqi Lu; Wenjuan Li; Miao Wang; Weiguang Xu; Qihang Dai; Yongsheng Song; Jiankang Wen; Wei Qu (Minerals Engineering, 2025)

AMF and biochar reshape the bacterial network in rhizosphere soil of Ricinus communis under chromium (Cr) stress and improve soil quality - Yuqiang Wen; Ruotong Wu; Tianle Xu; Ranran Cao; Ge Song; Dandan Qi; Wei Chang; Kun Li; Yuan Ping; Mengmeng Zhang; Xiaoxu Fan; Fuqiang Song (Journal of Hazardous Materials, 2025)

Assessing the growth dynamics of Listeria monocytogenes and microbiota in RTE poultry: A combined BP-ANN and traditional approach - Zichen Deng; Wenqian Li; Yihuan Song; Hongyi Wen; Yongxian Zhang; Yan Du; Yan Wang; Can Huang; Jingyu Chen (International Journal of Food Microbiology, 2025)

Development and evaluation of recombinant multi-epitopes vaccine against nervous necrosis virus - Chen Zhang; Wei-Nan Zhao; Xin-Xin Liu; Wen-Ye Song; Hai-Hua Peng; Min Yang; Peng-Fei Li; Jin-Qi Wei; Yong-Can Zhou; Yun Sun (Fish & Shellfish Immunology, 2025)

Hydrated eutectic electrolytes with decoupled weakly hydrogen bonded solvated structures enable fast kinetics for high-performance zinc-ion batteries - Wenruo Li; Xinyao Dong; Farva Ilyas; Haoyuan Zhu; Luzheng Zhao; Wei Liu; Weiqiang Kong; Xu Han; Jiancong Guo; Zaoyan Yu; Yushuai Song; Zhensheng Guan; et al. (Chemical Engineering Journal, 2025)

Extracellular polymeric substance-intercalated MXene membrane for osmotic power generation - Da-Qi Cao; Kai Tang; Guri Yihuo; Yan Jin; Yi-Xuan Song; Yun-Feng Wu; Wen-Yu Zhang; Zhongguo Zhang; Ming-Guo Ma; Li Song; Xiao-Di Hao (Chemical Engineering Journal, 2025)

A hydrophobic cathode design towards high-stability Zn-air batteries: Coupling FeTAP molecules with self-supporting edge-rich graphene membrane - Jiachen Meng; Yulei Zhang; Xuemin Yin; Yanqin Fu; Dan Wen; Qiang Song; Hejun Li (Chemical Engineering Journal, 2025)

Interfacial hydrogen bond interaction propels selective C–P breaking for efficient photodegradation and carbon utilization of glyphosate wastewater - Yu Wen; Jinshu Huang; Huan Liu; Jie Li; Tengyu Liu; Artem S. Belousov; Song Yang; Hu Li (Chemical Engineering Journal, 2025)

In situ constructing artificial interfacial layer enables dendrite-free zinc anode in aqueous batteries - Canglong Li; Changding Wang; Jie Huang; Qiwen Zhao; Wen Liu; Yuxuan Song; Mingjun Rao; Fu Wan; Yuejiao Chen; Weigen Chen; Shuhui Sun (Chemical Engineering Journal, 2025)

Effect of coal mining subsidence on soil microbial communities in mining areas with high groundwater levels - Ruiping Xu; Junying Li; Xinju Li; Wen Song (Environmental Geochemistry and Health, 2025)

Residual plastic film debris induced the reconstruction of soil microbial communities: Potential mechanisms affecting the natural attenuation of PAHs - Wenxiu Bao; Ming Chen; Wen Zhang; Lei Wang; Jianing Wang; Hongwen Sun; Fanyong Song; Leilei Wang; Bing Li (Applied Soil Ecology, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Discovery of isopentenyl flavonoids with inhibitory activity against hepatocellular carcinoma cells based on DeepSAT - Qing Wang; Ben‐Song Xin; Wen-Long Kou; Li-Na Gao; Gu-Xue Zhang; Yan-Jiao Qiao; Guo‐Dong Yao; Xiao‐Xiao Huang; Shao‐Jiang Song (Phytochemistry, 2025)

Clay/carbon composite aerogels for effective solar-driven water desalination and treatment - Huiquan Liu; Wen Luo; Shuai Wang; Yixuan Fu; Zhenxu Li; Yongchen Song; Lunxiang Zhang; Changrui Shi; Zheng Ling (Journal of Environmental Chemical Engineering, 2025)

Vitamin D3 ameliorates hyperglycemia by modulating gut microbiota and metabolites in prediabetic KKay mice - Yujing Zhang; Peng Ni; Hao Chen; Lulu Tang; Hanlu Song; Hongwei Wen; Yufan Miao; Wenjie Li; Xing Li (Food Research International, 2025)

A Systematic Framework for Exploring Valley Fracture Failure Mechanisms During a River Downcutting Process: A Case Study from the Hengduan Mountains - Yaopeng Ji; Shengyuan Song; Wen Zhang; Yuchao Li; Jingyu Xue; Jianping Chen (Rock Mechanics and Rock Engineering, 2025)

Drivers of Soil Bacterial Community Composition and Function in Extremely Degraded Alpine Meadows in Qinghai Plateau - Jiangqin Song; Yali Yin; Yan Liu; Wen Zhao; Qiqi Sui; Jiuyan Huo; Wenxian Zheng; Shixiong Li (Journal of Soil Science and Plant Nutrition, 2025)

Long-term dynamics of sediment and their potential indication for debris flow initiation in Wenchuan seismic area - Wen Zhang; Wankun Li; Chen Cao; Shengyuan Song; Junqi Chen; Han Yin; Zongshuo Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Procalcitonin contributes to hippocampal neuronal damage and impairment of LTP: implications for cognitive dysfunction in LPS-induced neuroinflammation rat model - Wen Li; Changgeng Song; Xiaona Li; Huimin Zhou; Xianghui Zhao; Wen Jiang (Archives of Microbiology, 2025)

Application of scattering image wavelet transform in cave recognition: A case study on a bedrock buried hill reservoir in Bongor Basin, Chad - Yu-Jiang Xiao; Tao Song; Li-Deng Gan; Yan Zhang; Wen-Hui Du; Xing-Yan Fan; Xiao-Feng Dai (Applied Geophysics, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Low oxygen in the open ocean: A case study of mild oxygen minimum zone (OMZ) in the Western Pacific - Lilian Wen; Jun Ma; Xuegang Li; Jiajia Dai; Jinming Song; Qidong Wang; Huamao Yuan; Jianwei Xing; Baoxiao Qu (Marine Environmental Research, 2025)

Improving the graph model to investigate a water allocation dispute in China involving strength of preference and unknown preference - Jing Yu; Liping Fang; Keith W. Hipel; D. Marc Kilgour; Xuemei Li; Wen Song (Journal of Hydrology, 2025)

Antibiotic resistance genes (ARGs) in microorganisms and their indications for the nitrogen/sulfur cycle in the East China Sea sediments - Lilian Wen; Jiajia Dai; Jinming Song; Jun Ma; Xuegang Li; Huamao Yuan; Liqin Duan; Qidong Wang (Journal of Hazardous Materials, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Research on the extraction mechanism of dibenzo-14-crown-4 ether to specific recovery Li+ from spent lithium-ion battery raffinate - Xifan Li; Guijing Chen; Xin Li; Zhaoyang Song; Wen Liu; Baicang Liu (Desalination, 2025)

Methane hydrate formation kinetics and structure information in the presence of cyclopentane under different reaction evolution - Wen-Zhe Sun; Hai-Long Liu; Kai Zhang; Xu-Ke Ruan; Yi-Song Yu; Xiao-Sen Li (Chemical Engineering Journal, 2025)

Au NCs@p53 delivery system triggers a “domino effect” in combination with anti-PD-L1 immunotherapy cascade to potentiate HCC treatment - Liang Yin; Wen Wang; Wenping Cai; Huaqian Li; Qingqing Song; Weijuan Cai (Chemical Engineering Journal, 2025)

Polygonatum cyrtonema Hua polysaccharide alleviates ulcerative colitis via gut microbiota-independent modulation of inflammatory immune response - Jin-Yang Shi; Yong-Jian Wang; Qian-Wen Bao; Ya-Min Qin; Pei-Pei Li; Qiao-Qiao Wu; Cheng-Kai Xia; De-Ling Wu; Song-Zi Xie (Carbohydrate Polymers, 2025)

Preparation and bioactivities of low-molecular weight fucoidans and fuco-oligosaccharides: A review - Hai-Di Liu; Dong-Yue Ma; Shan-Rui Shi; Shi-Lin Song; Wen-Lan Li; Xiao-Hui Qi; Shou-Dong Guo (Carbohydrate Polymers, 2025)

Biomedical data and AI - Hao Xu; Shibo Zhou; Zefeng Zhu; Vincenzo Vitelli; Liangyi Chen; Ziwei Dai; Ning Yang; Luhua Lai; Shengyong Yang; Sergey Ovchinnikov; Zhuoran Qiao; Sirui Liu; et al. (Science China Life Sciences, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Cytological study of Chinese Oenanthe (Apiaceae) with four new reports - Junwen Zhu; Huimin Li; Wei Wang; Jun Wen; Xudong Ma; Naiwei Li; Chunfeng Song (Biologia, 2025)

Predicting stomatal conductance of chili peppers using TPE-optimized LightGBM and SHAP feature analysis based on UAVs’ hyperspectral, thermal infrared imagery, and meteorological data - Haiyang Zhang; Wenwen Li; Guolong Wang; Fanfan Song; Zhaoqi Wen; Hengyuan Zhang; Ling Tong; Shaozhong Kang (Computers and Electronics in Agriculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Co-doping graphitic carbon nitride with Fe atoms and oxygen-containing functional groups for the efficient photo-Fenton degradation of sulfamethoxazole - Ruiyan Zhang; Cong Yan; Qinghua Yan; Congzhe Ren; Wen Zhang; Xiaozhe Song; Xuyang Li; Lei Chen; Fangyuan Zhou; Rong Xue; Feng Shi; Chongqing Xu (Journal of Water Process Engineering, 2025)

Study on the performance of micro/nano-aeration and submerged plants against exogenous pollution - Wen-bo Liang; Yi-Fan Liu; Xiao-Li Yang; Hai-liang Song (Journal of Water Process Engineering, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Photocatalysis and peroxymonosulfate activation by dual Z-scheme g-C3N4/PDI/Co-Fe Prussian blue analogue for doxycycline hydrochloride removal - Di Li; Yuan Zhang; Chunyan Gao; Qi Wen; Xinguo Ma; Fang Song; Jun Zhou (Journal of Environmental Chemical Engineering, 2025)

Dry season dominance of salinity’s impact on hydrogen isotope fractionation in Aegiceras corniculatum mangrove lipids - Yao-Ping Wang; Zhiguang Song; Jia Xia; Zhao-Wen Zhan; Alex L. Sessions; Shaelyn N. Silverman; Yuan Gao; Guopeng Li; Ding He (Geochimica et Cosmochimica Acta, 2025)

Eco-friendly production, separation and purification of D-tagatose and D-allulose from whey powder via one-pot whole-cells biotransformation, yeast fermentation and chromatography - Xin Wen; Huibin Lin; Guangwen Liu; Yuhang Ning; Xixian Xu; Hongtao Hu; Yilin Ren; Can Li; Chengjia Zhang; Nannan Dong; Xin Song; Jianqun Lin; et al. (Food Research International, 2025)

Green biotechnological synthesis of rare sugars/alcohols: D-allulose, allitol, D-tagatose, L-xylulose, L-ribose - Xin Wen; Mesfin Angaw Tesfay; Yuhang Ning; Huibin Lin; Guangwen Liu; Hongtao Hu; Xixian Xu; Xingbo Jiang; Chunxia Zhao; Yilin Ren; Can Li; Chengjia Zhang; et al. (Food Research International, 2025)

Interfacial sorption of 17β-E2 on nano-microplastics: Effects of particle size, functional groups and hydrochemical conditions - Yuhan Li; Xiaoming Song; Zhipeng Zhang; Changwei An; Yunlong Wang; Yuesuo Yang; Yujuan Wen (Environmental Research, 2025)

Full-scale shaking table test on a precast sandwich wall panel structure with a high-damping viscoelastic isolation and mitigation device - Zhong-Wei Hu; Zhao-Dong Xu; Lian-Yu Zhang; Jia-Xuan He; Zheng-Han Chen; Qi-Song Miao; Wen-Feng Li (Engineering Structures, 2025)

Genetically encoded horse heart myoglobin for electron microscopy imaging in mammalian cells - Feng Zhang; Lianwan Chen; Jinfu Wen; Fahui Li; Guohua Song (Chemical Engineering Journal, 2025)

Network pharmacological analysis and experimental verification of Zisheng Tongmai decoction in the treatment of premature ovarian failure - Jiaru Wu; Mengjie Wen; Zecheng Wang; Kun Yu; Xinyue Jin; Chenxu Liu; Qiuhang Song; Guohong Zhang; Beibei Wu; Yunfeng Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The synergistic effect of Rhizophagus irregularis and Biochar on the growth of Switchgrass under sodium-saline-alkali stress: insights from soil mechanical property analysis - Yuqiang Wen; Tianle Xu; Wei Chang; Kun Li; Xiaoxu Fan; Yuan Ping; Fuqiang Song (Mycorrhiza, 2025)

Relationship of Ural Blocking Zonal Width to Cold Air Intrusion in China under Varying Barents–Kara Sea Ice Conditions - Wenjun Song; Yan Li; Yao Yao; Mengying Du; Qi Wen; Jiaqi Shi (Journal of Meteorological Research, 2025)

Molecular characterization of a novel non-segmented double-stranded RNA mycovirus isolated from the phytopathogenic fungus Lasiodiplodia pseudotheobromae - Zhengzhe Guan; Mengjiao Wang; Jiayi Ma; Mengyuan Mu; Xinyu Li; Peimeng Sun; Mengyuan Zhang; Yuanyuan Zhang; Luyang Song; Caiyi Wen; Ying Zhao (Archives of Virology, 2025)

Variations in the archaeal community in wetlands soils under various hydrologic conditions in the Yellow River Estuary - Qingqing Zhao; Jia Jia; Fanyong Song; Tianyuan Li; Wen Zhang; Yujie Huang (Frontiers in Marine Science, 2025)
Unraveling the relationships between archaea and factors influencing their diversity and distribution is a critical issue in marine ecosystems. Here, the archaeal diversity and community structure in 0 - 20 cm soils from freshwater influenced wetlands (FIW), flooding freshwater and underground seawater influenced wetlands (MIW) and seawater influenced wetlands (SIW) in the Yellow River Nature Reserve were examined utilizing high-throughput sequencing of 16S rRNA gene sequencing. Based on the comparison of the alpha diversity indices, the abundance and diversity of the archaeal community in wetlands with varying hydrologic conditions did not significantly change ( p > 0.05), with Thaumarchaeota and Marine_Group_I as the predominant archaeal phylum and class in all the three sampled sites, respectively. Thaumarchaeota, Woesearchaeota and Euryarchaeota constituted more than 90% of the total soil archaeal community in all wetlands. However, beta diversity indices revealed that significantly different distribution patterns of archaea were found among the three wetlands ( p < 0.05). And the archaeal community structure in different wetlands varied as the hydrologic conditions changed. Less discriminated archaeal taxa were found in MIW (1 taxon) than in FIW (24 taxa) and SIW (18 taxa). Furthermore, statistical analysis confirmed that the difference in soil salinity caused by different hydrologic conditions was the major driver of archaeal community structure. Overall, this study highlights the role of hydrologic conditions in structuring the soil archaeal community in coastal wetlands.

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Influences of natural organic acids on the degradation of atrazine in water by pyrite-mediated Fenton oxidation - Yuling Zheng; Fang Li; Chen Yan; Wei Yang; Jia Wen; Biao Song (Journal of Water Process Engineering, 2025)

Interaction mechanism between membrane biofouling and reverse solute diffusion in an osmotic membrane bioreactor - Si-Qi Zhai; Jing Nan; Wen-Jun Cai; Xi-Wei He; Xiao-Li Yang; Yu-Li Yang; Hai-Liang Song (Journal of Water Process Engineering, 2025)

Modified gluten by extrusion can significantly improve the amounts of flavor compounds during the fermentation of umami condiment - Li-Hao Wang; Wen-Hui Qu; Hui Jiang; Song-Gang Xia; Xue Feng; Chang-Hu Xue; Yun-Qi Wen (Innovative Food Science & Emerging Technologies, 2025)

Immobilization of cells expressing d-allulose 3-epimerase and their application in d-allulose bioproduction with the assistance of boric acid - Xin Wen; Huibin Lin; Guangwen Liu; Yuhang Ning; Yilin Ren; Can Li; Chengjia Zhang; Nannan Dong; Jianqiang Lin; Xin Song; Guoqiang Zhuang; Jianqun Lin (Food Bioscience, 2025)

A β-cyclodextrin-based supramolecular modular system creating micellar carriers for codelivery of doxorubicin and siRNA for potential combined chemotherapy and immunotherapy - Xichuan Tang; Yuting Wen; Zhongxing Zhang; Xia Song; Jingling Zhu; Xuehao Tian; Jun Li (Carbohydrate Polymers, 2025)

China’s Yangtze River drought: A cascade of impacts from mountains to sea - Nan Jia; Jie Cheng; Yinshuai Li; Lilin Zheng; Wen Song; Ruishan Chen; Annah Zhu (Science China Earth Sciences, 2025)

PSD-95 Protein: A Promising Therapeutic Target in Chronic Pain - Lulin Ma; Dongdong Sun; Song Wen; Jie Yuan; Jing Li; Xinran Tan; Song Cao (Molecular Neurobiology, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

Comparative genomics provides insights into the evolutionary history of the phylum Ciliophora (Eukaryota, Alveolata) and uncovers the adaptive evolution of anaerobic ciliate classes - Ying Zhang; Fasheng Liang; Yu Fu; Yong Chi; Wen Song; Alan Warren; Lifang Li (Zoologica Scripta, 2025)
Ciliophora are one of the most diverse phyla of unicellular eukaryotes. Members of this group are widely distributed and have been found in several environments including those that are anaerobic. However, the paucity of sufficient omics data for the major classes of the phylum Ciliophora, especially the anaerobic ciliate lineages, has been a serious impediment to research thus far. In this study, omics data were expanded to include representatives of 16 ciliate classes (excluding Cariacotrichea and Copemetopea) using single‐cell sequencing techniques. Using omics data of 57 ciliates and two apicomplexans, we conducted a comparative genomics study. Phylogenomic analysis based on 156 orthologous genes showed that: there are two superclades within the subphylum Intramacronucleata, i.e., Colpodea + Oligohymenophorea + Nassophorea + Plagiopylea + Prostomatea + Phyllopharyngea (CONThreeP), and Spirotrichea + Armophorea + Litostomatea + Odontostomatea + Muranotrichea + Parablepharismea (SALOMP); with the exception of Armophorea, all ciliate classes are monophyletic; neither Metopus nor Plagiopyla is monophyletic; Paraspathidium has a close affiliation with prostomateans. The results of the divergence time estimations indicated that: the radiation of Ciliophora occurred ca. 1067 million years ago (Mya); the SALOMP and CONThreeP lineages diverged from the intramacronucleatean common ancestor ca. 892 Mya and 851 Mya, respectively; the split between Muranotrichea and Parablepharismea occurred ca. 712 Mya; Odontostomatea are the youngest class, with a crown age estimated at ca. 19 Mya. In addition, we profiled stop codon usage and programmed ribosomal frameshifting (PRF) events. Our analyses revealed that: most of the species investigated use either TAA or TGA as the biased stop codon; stop codon usage in Paraspathidium sp. resembles that of Prostomatea; almost all ciliates included in the analyses have prevalent +1 and −1 PRF events. Finally, through GO enrichment analysis for group‐shared orthogroups of five anaerobic ciliate classes, we successfully identified the biological process and molecular function GO terms that were related to the adaptation of this particular group of ciliates to anaerobic environments. Together, these findings provide new insights into the evolutionary history of the Ciliophora and deepen our understanding of the adaptation of anaerobic ciliate groups to anaerobic environments from an evolutionary perspective.

Comparative study on the role of various sterols in enhancing ovarian development and metabolic functions in Pacific white shrimp (Litopenaeus vannamei) broodstock - Xiaolong Liang; Xianming Xiao; Xiuju Gao; Muchun Wen; Yongqiang Song; Chang Xu; Fenglu Han; Erchao Li (Aquaculture, 2025)

Dietary yeast culture can protect against chronic heat stress by improving the survival, antioxidant capacity, immune response, and gut health of juvenile Chinese mitten crab (Eriocheir sinensis) - Song Wang; Erchao Li; Zuoyong Luo; Xuesong Li; Zhijun Liu; Wen Li; Xiaodan Wang; Jian G. Qin; Liqiao Chen (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The carbon transport mediated by the mild oxygen minimum zone (OMZ) in the seamount area of the Western Pacific - Lilian Wen; Jun Ma; Xuegang Li; Jiajia Dai; Jinming Song; Qidong Wang; Kuidong Xu; Jianwei Xing; Baoxiao Qu; Guorong Zhong (Marine Environmental Research, 2025)

Multi-organ toxicity caused by PM2.5 in mice with cardiovascular diseases: The role of PAHs played from the most polluted episodes in China - Jinjin Yu; Jian Sun; Yajing Ma; Xinyi Niu; Ruisi Zhu; Huixin Song; Lingyi Liu; Yuzhi Luo; Songyuan Xia; Jingyu Wang; Lingli Li; Sha Wen; et al. (Journal of Environmental Management, 2025)

Enhanced activation of peroxymonosulfate by CuO modified biochar through mechanochemical synthesis: Insights into the roles of active sites and electron density redistribution - Xiaoqian Fu; Liangguo Yan; Haiqiang Qi; Wen Song; Yanfei Li; Xuguang Li (Journal of Environmental Chemical Engineering, 2025)

Automatic identification of rock fractures based on deep learning - Yaopeng Ji; Shengyuan Song; Wen Zhang; Yuchao Li; Jingyu Xue; Jianping Chen (Engineering Geology, 2025)

Prior information assisted multi-scale network for precipitation nowcasting - Dan Song; Yu Wang; Wenhui Li; Wen Liu; Zhiqiang Wei; An-An Liu (Computers & Geosciences, 2025)

Engineering Shewanella oneidensis to efficiently co-utilize glucose and xylose for converting cellulose hydrolysate from corn stover to electricity - Junqi Zhang; Wenjing Lv; Yangyang Wang; Jingxuan Tan; Qijing Liu; Huan Yu; Chao Li; Longhai Dai; Jing Zou; Zhanying Liu; Wen-Wei Li; Guosheng Xin; et al. (Chemical Engineering Journal, 2025)

The integrated strategy of W/MoC quantum dot heterointerface and defect engineering enhances the performance of solar cells - Wen Wang; Jixin Yao; Xiuying Wang; Song Ye; Haifeng Xu; Dongmeng Chen; Guang Li (Chemical Engineering Journal, 2025)

Exaptation of pectoral fins for olfaction in the spiny red gurnard (Chelidonichthys spinosus) through an ancient receptor - Lisen Li; Deqian Fan; Chenglong Zhu; Zhuoya Liu; Wenji Huang; Peidong Xin; Huishan Yue; Mengying Li; Yufei Wang; Wenjie Xu; Jiangmin Zheng; Ye Li; et al. (Science China Life Sciences, 2025)

Health Risk of Heavy Metal and Implication for Ecological Threat in Soils Weathered from the Black Shale - Wanfu Zhao; Yinxian Song; Wei Li; Yubo Wen; Junfeng Ji (Bulletin of Environmental Contamination and Toxicology, 2025)

Hydrochemistry Predominantly Shapes the Unique Nitrogen-Fixing Bacterial Communities in Tibetan Hot Springs - Zhao-Qi Song; Li Wang; Yaru Ma; Dandan Deng; Yang Song; Feng Liang; Xiangyu Guan; Wen-Jun Li; Hongchen Jiang (Journal of Earth Science, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

A rare tetrahydroimidazopyridine from the marine-derived fungus Paraconiothyrium sp. YK-03 - Wen-Ke Gao; Xiao-Yan Song; Shi-Wei Li; Bian-Xia Xue; Hong-Hua Wu; Li-Hua Zhang; Yue-Hu Pei (Natural Product Research, 2025)

Comparative effects of four feed attractants on growth, appetite, digestion and absorption in juvenile Chinese mitten crab (Eriocheir sinensis) - Wen Li; Erchao Li; Song Wang; Jiadai Liu; Minxu Wang; Xiaodan Wang; Chuanjie Qin; Jianguang Qin; Liqiao Chen (Aquaculture, 2025)

Dietary supplementation with glutamate enhanced antioxidant capacity, ammonia detoxification and ion regulation ability in Nile tilapia (Oreochromis niloticus) exposed to acute alkalinity stress - Minxu Wang; Erchao Li; Yuxing Huang; Wei Liu; Song Wang; Wen Li; Liqiao Chen; Xiaodan Wang (Aquaculture, 2025)

Combining slow-release fertilizer and plastic film mulching reduced the carbon footprint and enhanced maize yield on the Loess Plateau - Xiaoqing Han; Pengfei Dang; Lechen Liao; Fangqi Song; Miaomiao Zhang; Maoxue Zhang; Guoqing Li; Shuyue Wen; Ning Yang; Xiping Pan; Xiaofan Wang; Wen Wang; et al. (Journal of Environmental Sciences, 2025)

What influences different stakeholders' willingness to accept and pay for reusable tableware? Evidence from a CVM survey of Guangdong-Hong Kong-Macao GBA - Kaihan Cai; Yiliang Guo; Ni Sheng; Li Wang; Xi He; Qingbin Song; Chen Chen; Zongguo Wen (Environmental Impact Assessment Review, 2025)

Boosting Zn metal reversibility via an efficient ternary aqueous electrolyte - Peter Joseph Chimtali; Asante Obed Frimpong; Fangren Qian; Zeinab Mohamed; Luyao Wen; Jialin Shi; Hassan Akhtar; Dengfeng Cao; Shuangming Chen; Xiaojun Wu; Changda Wang; Li Song (Chemical Engineering Journal, 2025)

Bio-inspired construction of hydrophobic Mg(OH)2/Co-MOF/DOPO hybrids for simultaneously improving flame retardancy and mechanical properties of poly(L-lactic acid) composites - Cui Li; Zhaotian Ba; Bingchen Wu; Xinxin Shi; Hui Liu; Lili Ma; Xin Wen; Pingan Song (Chemical Engineering Journal, 2025)

Novel high-safety composite separator: Achieving efficient alkaline water electrolysis by compositing microporous polysulfone membrane on one side of complete structure polyphenylene sulfide fabric - Wen Song; Zhaoling Sun; Miao Guo; Yunyong Tang; Maliang Zhang; Kunmei Su; Jianxiong Li; Zhenhuan Li (Chemical Engineering Journal, 2025)

Litter removal effectively alleviates the nitrogen limitation in grazing exclusion alpine meadows - Jiangqin Song; Yali Yin; Wen Zhao; Qiqi Sui; Jiuyan Huo; Wenxian Zheng; Shixiong Li (CATENA, 2025)

Fore-arc metasomatism by hybrid slab fluids during subduction initiation: Sr–Mg–Ca isotopes of rodingite, western Yarlung Zangbo suture zone - Gui-Fang Ou; Song-Jie Wang; Hao Deng; Wen-Yong Duan; Xu-Ping Li; Hans-Peter Schertl (Chemical Geology, 2025)

Investigating the role of two-dimensional and three-dimensional urban structures in seasonal surface radiation budget - Jingyi Chen; Shisong Cao; Meng Du; Mingyi Du; Xianglei Liu; Wen Song; Ying Liang; Wen He; Ling Li; Nuan Wang (Building and Environment, 2025)

Dissecting the cell microenvironment of ovarian endometrioma through single-cell RNA sequencing - Jiangpeng Wu; Siyu Xia; Wenting Ye; Yan Sun; Jing Cai; Fubing Yu; Haiping Wen; Xiuwei Yi; Taikang Li; Mingwei Chen; Jiayun Chen; Ge Song; et al. (Science China Life Sciences, 2025)

Investigating the psammophilic karyorelictean ciliate families Kentrophoridae and Cryptopharyngidae (Protista, Ciliophora): molecular phylogeny, geographic distributions and a brief revision including descriptions of a new genus, a new species and a new combination - Mingzhen Ma; Danxu Tang; Wen Song; Lifang Li; Igor V. Dovgal; Khaled A. S. Al-Rasheid; Hunter N. Hines; Ying Yan (Marine Life Science & Technology, 2024)
Psammophillic ciliates are an integral part of the foodweb despite being underrepresented in terms of molecular phylogeny and modern taxonomy. To investigate the karyorelictean group, sampling was conducted in interstitial marine habitats in China for ciliates living between the sand grains, resulting in an examination of the families Cryptopharyngidae Jankowski, 1980 and Kentrophoridae Jankowski, 1980. Three species, i.e., Cryptopharynx setigerus Kahl, 1928, Kentrophoros fasciolatus (Sauerbrey, 1928) Foissner, 1995 and K. fistulosus (Fauré-Fremiet, 1950) Foissner, 1995, are clearly recognized as being cosmopolitan, while other species await further recording. Phylogenetic analyses were carried out based on updated data. These revealed that the families Cryptopharyngidae and Kentrophoridae are closely related, and most genera studied are monophyletic, although Cryptopharynx qingdaoensis n. sp. is located within the Kentrophoridae branch. Brief revisions of two genera, namely Cryptopharynx Kahl, 1928 and Kentrophoros Sauerbrey, 1928, are provided including keys to the identification of nine species belonging to the former and 12 species belonging to the latter. One new genus, Parakentrophoros n. gen., and one new species, Cryptopharynx qingdaoensis n. sp., are described and a new combination, Parakentrophoros canalis (Wright, 1982) n. comb., is established. Finally, it appears that the subapical oral apparatus undergoes a gradual degeneration process from Cryptopharyngidae to Kentrophoridae.

A monochrome pipelined HMI system for foodborne microorganisms testing - Jia-Yong Song; Ze-Sheng Qin; Chang-Wen Xue; Li-Feng Bian; Chen Yang (Computers and Electronics in Agriculture, 2024)

Supplementation of yeast culture to low-fishmeal diets improves growth, intestinal health, and heat stress resistance in juvenile Chinese mitten crab (Eriocheir sinensis) - Song Wang; Erchao Li; Qiuran Yu; Zuoyong Luo; Wen Li; Xiaodan Wang; Jianguang Qin; Liqiao Chen (Aquaculture, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

New insights into thallium(I) behaviors at birnessite surfaces: Effects of an organic buffer and goethite - Wen Zhuang; Tianqiang Zhu; Feng Li; Chuanyong Jing; Samantha C. Ying; Macon J. Abernathy; Jinming Song; Hui Yin (Journal of Hazardous Materials, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

A novel approach based on supramolecular solvents microextraction for quick detection of perfluoroalkyl acids and their precursors in aquatic food - Xiaoyu Liu; Xianli Wang; Shuang Hong; Huatian Zhou; Xiaolong Cao; Kepiao Li; Qicai Zhang; Chunxia Yao; Wanchao Chen; Wen Li; Weiguo Song; Qinxiong Rao (Journal of Hazardous Materials, 2024)

Umami-enhancing effect of Agaricus bisporus-pork bone stocks based on the EUC value and sensory evaluation - Ke Shi; Zhenqi Li; Yibo Bai; Yu Zhang; Huanlu Song; Wenqing Pan; Wanying Chen; Wen Xiong; Li Yang; Zijian Huang (International Journal of Gastronomy and Food Science, 2024)

A comprehensive approach for quantifying source-specific ecological and health risks of potentially toxic elements in agricultural soil - Li-Mei Cai; Ke Quan; Han-Hui Wen; Jie Luo; Shuo Wang; Lai-Guo Chen; He Song; Ao Wang (Environmental Research, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

High-throughput prediction of stalk cellulose and hemicellulose content in maize using machine learning and Fourier transform infrared spectroscopy - Fanghui Chen; Xing Liu; Chengchen Lu; Mingxiu Ruan; Yujing Wen; Shaodong Wang; Youhong Song; Lin Li; Liang Zhou; Haiyang Jiang; Leiming Wu (Bioresource Technology, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

The roles of abscisic acid and ethylene in cadmium accumulation and tolerance in plants - Jiayou Liu; Liu Yang; Ying Wen; Yuxuan Li; Sergey Shabala; Jie Zhang; Won-Yong Song (Plant and Soil, 2024)

Alterations in leukocyte telomere length and mitochondrial DNA copy number in benzene poisoning patients - Dianpeng Wang; Dafeng Lin; Xiangli Yang; Dongpeng Wu; Peimao Li; Zhimin Zhang; Wen Zhang; Yan Guo; Song Fu; Naixing Zhang (Molecular Biology Reports, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Study on the thermo-hydraulic behaviors within a CiADS 61-pin wire-wrapped fuel assembly under porous blockage conditions based on LBEblockageFoam - Yun-Xiang Li; Run-Sheng Yang; Yue Li; Xing-Kang Su; Yi-Wen Han; Zi-Nan Huang; Lu Meng; Song Li; You-Peng Zhang; Lu Zhang; Wei Jiang (Annals of Nuclear Energy, 2024)

Functional diversification of contact calls contribute to the cohesion of a multi-level society - Yi-Jun Yang; Ying Yan; Gu Fang; Yu-Ting Song; Jing Zang; Wen-Yong Tian; Dai-Bo Zhu; Paul A. Garber; Bao-Guo Li; Xiao-Guang Qi (Behavioral Ecology and Sociobiology, 2024)

Solibacillus ferritrahens sp. nov., a novel siderophore-producing bacterium isolated from Wumeng Mountain National Nature Reserve in Yunnan Province - Xiao-Di Liu; Jiang-Yuan Zhao; Le-Le Li; Jian-Yu Li; Pei-Wen Yang; Song-Guo Liang; Lu-Yao Feng; Zhu-Feng Shi; Zhang-Gui Ding; Ming-Gang Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Antibiotic resistance genes (ARGs) and their eco-environmental response in the Bohai Sea sediments - Lilian Wen; Jiajia Dai; Jinming Song; Jun Ma; Xuegang Li; Huamao Yuan; Liqin Duan; Qidong Wang (Marine Pollution Bulletin, 2024)

High-yield synthesis of quasi-MOF using synergistic modulated hydrothermal process for NH3-SCR of NO - Kunli Song; Xinya Zhou; Dandan Ma; Xuanlin Guo; Jun Li; Shasha Yang; Peng Xiao; Renjin Chen; Jian-Wen Shi (Process Safety and Environmental Protection, 2024)

Area-wide survey and monitoring of insecticide resistance in the brown planthopper, Nilaparvata lugens (Stål), from 2020 to 2023 in China - Wen-Nan Ye; Yu Li; Yan-Chao Zhang; Zhao-Yu Liu; Xin-Yu Song; Xin-Guo Pei; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2024)

Coarse-to-fine semantic segmentation of satellite images - Hao Chen; Wen Yang; Li Liu; Gui-Song Xia (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

Fabrication of boron modified bi-functional air diffusion electrode for ciprofloxacin degradation: In-situ H2O2 generation and self-activation - Hengrui Zhang; Bairun Chen; Jing Li; Xinran Song; Jiaxin Zhai; Wen Liu; Shuyan Kong; Xuan Xing (Chemical Engineering Journal, 2024)

Single-Atom Cu anchored polymeric carbon nitride for enhanced one-step plasma-catalytic conversion of CH4 and CO2 into acetic acid - Jun Wu; Shangzhi Song; Lei Wang; Ruoping Li; Jiaqi Wen; Yanan Guo; Jing Ding; Danhua Mei; Hui Wan; Guofeng Guan (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

YOLOv8-ECFS: A lightweight model for weed species detection in soybean fields - Wendong Niu; Xingpeng Lei; Hao Li; Hongqi Wu; Fenshan Hu; Xiaoxia Wen; Decong Zheng; Haiyan Song (Crop Protection, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Optimization of differentiation conditions for porcine adipose-derived mesenchymal stem cells and analysis of fatty acids in cultured fat - Pei-Pei Liu; Zi-Jiang Yang; Wen-Juan Song; Shi-Jie Ding; Hui-Xia Li; Chun-Bao Li (Food Research International, 2024)

Glycoprotein from selenium-enriched yam activates immune cells and enhances intestinal immunity via the NF-κB signaling pathway - Siqi Wang; Jinjin Yu; Lili Zhou; Yuzhi Luo; Lingyi Liu; Sha Wen; Lingli Li; Yajing Ma; Huixin Song; Song Ming; Weifeng Li; Xiaofeng Niu (Food Bioscience, 2024)

Acidification state and interannual variability in marginal sea: A case study of the Bohai and the Yellow Seas surface waters in April 2023 - Zhibo Wang; Shanshan Liu; Jinming Song; Lilian Wen; Huamao Yuan; Liqin Duan; Zhipeng He; Xuegang Li (Environmental Research, 2024)

Successful subduction of oceanic plate after failed attempts in the Late Archean: Petrological and geochemical constraints - Xi Wang; Rong-Feng Ge; Yong-Fei Zheng; Wen-Bin Zhu; San-Zhong Li; Rong-Song Tian; Yue Wang; Yi-Wei Rong (Earth and Planetary Science Letters, 2024)

Insights into the factors influencing the oxidation of antibiotic pollutants in nitrogen-doped biochar/PMS system: The roles of physicochemical properties and reaction pathways - Wen Song; Zihan Yu; Hang Li; Yuqi Ji; Lingling Cao; Liyao Ren; Xuguang Li; Yanfei Li; Xing Xu; Liangguo Yan (Chemical Engineering Journal, 2024)

Synergistic effect of lightning rod and piezo-photocatalysis in sea urchin-shape Zn-MOF-74@g-C3N4 step-scheme heterojunction for H2O2 production under visible light irradiation - Di Li; Qi Wen; Chunyan Gao; Yuan Zhang; Jun Zhou; Shaomin Liu; Fang Song; Kai Wang (Chemical Engineering Journal, 2024)

Climatic characteristics and meteorology-sensitivity of surface solar radiation in reanalysis products compared to observations and satellite data over China - Qi Wen; Kang Liu; Yan Li; Xu Li; Wenjun Song (Atmospheric Environment, 2024)

Sodium Fluoride Exposure Induces Developmental Toxicity and Cardiotoxicity in Zebrafish Embryos - Feiqing Wang; Fa Chen; Wen Song; Yanju Li; Haiyan Wu; Tingting Tian; Mengxian Tian; Dongxin Tang; Yang Liu (Biological Trace Element Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Antiviral C-geranylated flavonoids from Artocarpus communis - Rui-Li Huang; Wei Tang; Chaoqun Wang; Cong Yan; Yun Hu; Hai-Xia Yang; Hai-Yang Xiang; Xiao-Jun Huang; Li-Jun Hu; Wen-Cai Ye; Jian-Guo Song; Ying Wang (Phytochemistry, 2024)

Low-Alkalinity flotation separation of antimony and arsenic minerals with modified polyacrylamide - Jiaqi Lu; Wenjuan Li; Weiguang Xu; Miao Wang; Jianhang Zhou; Yongsheng Song; Jiankang Wen; Yong Chen (Minerals Engineering, 2024)

Different fates of particulate matters driven by marine hypoxia: A case study of oxygen minimum zone in the Western Pacific - Jun Ma; Lilian Wen; Xuegang Li; Jiajia Dai; Jinming Song; Qidong Wang; Kuidong Xu; Huamao Yuan; Liqin Duan (Marine Environmental Research, 2024)

Measurement of 224Ra in water via pulsed ionization chamber (PIC) radon detector - Haowei Xu; Chunqian Li; Pengxia Liu; Wen Liu; Shibin Zhao; Natasha T. Dimova; Xiliang Cui; Lijun Song; Tianyi Zhu; Ergang Lian; Chun Xia; Yanming Xue; et al. (Journal of Environmental Radioactivity, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Bioreduction of Se(IV) by Lactiplantibacillus plantarum NML21 and synthesis of selenium nanospheres Se(0) - Longlin Wang; Li Song; Pengjie Wang; Hao Zhang; Yiheng Li; Juan Song; Liwen Zhong; Caihong Liu; Weibing Zhang; Pengcheng Wen (Food Chemistry, 2024)

Molecularly imprinted polymers and porous organic frameworks based analytical methods for disinfection by-products in water and wastewater - Jinhua Li; Dani Sun; Yuhao Wen; Xuan Chen; Hongdan Wang; Shuang Li; Zhihua Song; Huitao Liu; Jiping Ma; Lingxin Chen (Environmental Pollution, 2024)

Protective layer constructed by liquid phase quenching for long lifespan potassium ion batteries - Shedong Li; Lu-Kang Zhao; Yu-Hua Bian; Hong Chen; Xuan-Wen Gao; Yingying Song; Zhaomeng Liu; Wen-Bin Luo (Chemical Engineering Journal, 2024)

Rationally designed β-cyclodextrin-crosslinked polyacrylamide hydrogels for cell spheroid formation and 3D tumor model construction - Taili Chen; Yuting Wen; Xia Song; Zhongxing Zhang; Jingling Zhu; Xuehao Tian; Shan Zeng; Jun Li (Carbohydrate Polymers, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

Current insights into environmental acetochlor toxicity and remediation strategies - Wen-Juan Chen; Shao-Fang Chen; Haoran Song; Zeren Li; Xiaofang Luo; Xidong Zhang; Xiaofan Zhou (Environmental Geochemistry and Health, 2024)

Transcriptome Analysis Reveals the Regulatory Mechanism of Lipid Metabolism and Oxidative Stress in Litopenaeus vannamei under Low-Salinity Stress - Siyao Cao; Yundong Li; Song Jiang; Qibin Yang; Jianhua Huang; Lishi Yang; Jianzhi Shi; Shigui Jiang; Guoliang Wen; Falin Zhou (Journal of Marine Science and Engineering, 2024)
Salinity is a crucial environmental factor influencing the survival, growth, development, and reproduction of aquatic animals. However, the underlying molecular mechanisms of the shrimp’s response to salinity stress are not yet fully understood. Therefore, we used the Illumina NovaSeq 6000 platform to perform transcriptome sequencing of the hepatopancreas of Litopenaeus vannamei under high-salinity (30 PSU), medium-salinity (10 PSU), and low-salinity (0.5 PSU) conditions. We obtained 63.23 Gb of high-quality data and identified 3589 differentially expressed genes (DEGs), including 1638 upregulated and 1951 downregulated genes. Notably, a comparison between the control group (30 PSU) and the low-salinity group (0.5 PSU) revealed that the BBOX1 and CHE1 genes were significantly upregulated, while the ACOX1, MPV, CYP2L1, GCH, MVK, TREt1, and XDH genes were significantly downregulated. These genes are primarily involved in key metabolic pathways, such as fatty acid oxidation, cholesterol metabolism, and hormone synthesis and metabolism. The key genes involved in fatty acid β-oxidation, such as ACOX1, ACAD, HADH, HSD17B4, PECR, CROT, PIPOX, and CG5009, all showed a downward trend, suggesting that L. vannamei may respond to salt stress by regulating fatty acid oxidative metabolism, optimizing energy utilization, and maintaining cell homeostasis under low-salinity conditions. Functional annotation of gene ontology (GO) and KEGG pathway enrichment analysis highlighted the roles of these significant DEGs in the adaptation of L. vannamei to environments of varying salinity, underscoring the importance of metabolic pathways in their adaptive physiological responses. This study provides a crucial molecular biological basis for understanding the molecular mechanisms and physiological protection strategies of L. vannamei under salinity stress.

Two pairs of new isobenzofuranone enantiomers from a soil-derived fungus Penicillium canescens DWS225 - Jing Wang; Xiao-Qian Wu; Ji-Song Mo; Yu-Fen Tan; Hong-Ping Long; Si-Qian Zhou; Shao Liu; Jing Li; Wen-Xuan Wang (Natural Product Research, 2024)

Floating solar power as an alternative to hydropower expansion along China's Yellow River - Kai Chen; Yubin Jin; Yueyang Feng; Wen Song; Yingjie Li; Yanxi Zhou; Xiaona Guo; Yinshuai Li; Xiaomei Kou; Annah Lake Zhu; Ruishan Chen (Resources, Conservation and Recycling, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Taxonomy and phylogeny of three species in Perichaena sensu lato (Myxomycetes = Myxogastria) from China - Wen-Long Song; Min Li; Zi-Qi Wang; Shuang-Lin Chen (European Journal of Protistology, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

An antioxidative-enhanced endoplasmic reticulum-targeted cyanine dye for efficient tumor immunotherapy - Hekai Yang; Fahui Li; Shanshan Jin; Shuzhen Chen; Le Sun; Liuya Wei; Guangzhao Xu; Shuhua Cao; Weiguo Song; Xiaolong Zeng; Wenda Zhong; Wen Sun (Chemical Engineering Journal, 2024)

Sponge iron-coupled biochar solution can achieve the synergistic augmentation of carbon sequestration, carbon sink capacity, and denitrification in ecological ditches - Bi–Ni Jiang; Ying–Ying Zhang; Yan Wang; Hai–qin Liu; Qing Zhou; Yi–Jing Yang; Zhi–Yong Zhang; Yu–Li Yang; Wen–jing Guo; Hai–Liang Song (Chemical Engineering Journal, 2024)

Synergistic impact of dual active sites in Nb-Fe2P nanoparticles on electrocatalytic nitrate reduction with high selectivity - Xiaoyin Li; Miaomiao Xing; Wen He; Shuhua Lv; Qingdian Wang; Xing Gao; Hongyu Mou; Deliang Zhang; Jibin Song (Chemical Engineering Journal, 2024)

Synthesis of ultrafine Mo2N particles supported on N doped carbon material for guaiacol hydrodeoxygenation - Chenglong Wen; Shuning Li; Peng Zhang; Mohong Lu; Jie Zhu; Mingshi Li; Chunshan Song (Biomass and Bioenergy, 2024)

Molecular mechanisms and atmospheric implications of the simplest criegee intermediate and hydrochloric acid chemistry in the gas phase and at the aqueous interfaces - Chao Ding; Mingjie Wen; Tianlei Zhang; Zeyao Li; Rongrong Li; Rui Wang; Ting Ou; Fengmin Song; Qiang Zhang (Atmospheric Environment, 2024)

A synthetic TLR4 agonist significantly increases humoral immune responses and the protective ability of an MDCK-cell-derived inactivated H7N9 vaccine in mice - Jian Luo; Min Zhang; Qian Ye; Feixia Gao; Wenting Xu; Beibei Li; Qi Wang; Liang Zhao; Wen-Song Tan (Archives of Virology, 2024)

Simultaneous methane mitigation and nitrogen removal by denitrifying anaerobic methane oxidation in lake sediments - Yanan Bai; Wangting Yang; Hanyu Li; Qinan Hu; Sile Wen; Lidong Shen; Yuzhi Song (Science of The Total Environment, 2024)

Deep learning reconstruction of high-Reynolds-number turbulent flow field around a cylinder based on limited sensors - Rui Li; Baiyang Song; Yaoran Chen; Xiaowei Jin; Dai Zhou; Zhaolong Han; Wen-Li Chen; Yong Cao (Ocean Engineering, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Predicting hourly heating load in district heating system based on the hybrid Bi-directional long short-term memory and temporal convolutional network model - Jiancai Song; Wen Li; Shuo Zhu; Chenhao Zhou; Guixiang Xue; Xiangdong Wu (Journal of Cleaner Production, 2024)

Natural mineral colloids facilitated transport of EE2 in saturated porous media: Effects of humic acid and conjugate form - Xiaoming Song; Yingjun Li; Zhipeng Zhang; Yujuan Wen; Yunlong Wang (Journal of Contaminant Hydrology, 2024)

Ultra-wide film mulching with moderate irrigation water salinity enhances cotton growth under drip irrigation in Xinjiang, China - Zhanli Ma; Jian Liu; Jinzhu Zhang; Feihu Yin; Li Guo; Yue Wen; Libing Song; Yan Zhu; Yonghui Liang; Zhenhua Wang (Field Crops Research, 2024)

Enhanced performance in lithium metal batteries: A dual-layer solid electrolyte interphase strategy via perfluoropolyether derivative additive - Yu Zhan; Pengfei Zhai; Tinglu Song; Wen Yang; Yuchuan Li (Chemical Engineering Journal, 2024)

Mineral-derived layered carbon-based catalysts for enhanced Fenton-like reactions and catalytic ceramic membrane systems: Si-O coordination mediates radical generation and electron transfer - Taisheng Zhao; Chang Tian; Haibo Li; Wen Song; Xuguang Li; Liangguo Yan; Xing Xu; Yanxia Zhao (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

The selection of animal models influences the assessment of anti-tumor efficacy: promising sialic acid-conjugate modified liposomes demonstrate remarkable therapeutic effects in diverse mouse strains - Lu Wei; Lin Lin; Jia Wang; Xinying Guan; Wen Li; Yangxu Gui; Shupei Liao; Mingyang Wang; Jiaqi Li; Yihui Deng; Yanzhi Song (Drug Delivery and Translational Research, 2024)

Learning-based double layer control method of yaw stability simulation research for rear wheel independent drive electric tractor plowing operation - Zhen-hao Luo; Bin Xie; Zhong-ju Chen; Sheng-li Zhang; Zi-hao Zhao; Bo-wen Zheng; Chang-kai Wen; Zheng-he Song (Computers and Electronics in Agriculture, 2024)

Variations in surface area and biogeochemistry of subarctic-arctic lakes established through satellite and in-situ observations: An overview of published research from the past 30 years - Ruixue Zhao; Yingxin Shang; Pierre-André Jacinthe; Sijia Li; Ge Liu; Zhidan Wen; Zijin Wang; Qian Yang; Chong Fang; Kaishan Song (Science of The Total Environment, 2024)

Association of the external environmental exposome and obesity: A comprehensive nationwide study in 2019 among Chinese children and adolescents - Li Chen; Yang Qin; Yi Zhang; Xinli Song; RuoLin Wang; Jianuo Jiang; Jieyu Liu; Tongjun Guo; Wen Yuan; Zhiying Song; Yanhui Dong; Yi Song; et al. (Science of The Total Environment, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

Fruit grading system by reconstructed 3D hyperspectral full-surface images - Jia-Yong Song; Ze-Sheng Qin; Chang-Wen Xue; Li-Feng Bian; Chen Yang (Postharvest Biology and Technology, 2024)

Zinc isotope evidence for enhanced organic carbon burial driving transient oxygenation of the Mesoproterozoic ocean - Kexin Song; Dandan Li; Yi-Wen Lv; Chengshuai Yuan; Yuan-Ru Qu; Sheng-Ao Liu (Precambrian Research, 2024)

Elucidating the unexpected importance of intermediate-volatility organic compounds (IVOCs) from refueling procedure - Xinping Yang; Kai Song; Song Guo; Yunjing Wang; Junfang Wang; Di Peng; Yi Wen; Ang Li; Baoming Fan; Sihua Lu; Yan Ding (Journal of Hazardous Materials, 2024)

Bimetallic peroxide nanocatalytic gel for water disinfection - Yang Guo; Zhihui Niu; Jianyu Huang; Yingying Ding; Xiuling Li; Yuanda Song; Guangwu Wen; Xiaowei Li (Journal of Environmental Chemical Engineering, 2024)

Pseudo-targeted lipidomics insights into lipid discrepancies between yak colostrum and mature milk based on UHPLC-Qtrap-MS - Yiheng Li; Huiyuan Guo; Xue Yang; Xiaoli Yang; Hao Zhang; Pengjie Wang; Juan Song; Longlin Wang; Weibing Zhang; Pengcheng Wen (Food Chemistry, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Thermally stabilized polyacrylonitrile/polyphenylene sulfide composite membranes for efficient emission control in harsh environments - Wen Song; Cong Xie; Guofeng Yang; Maliang Zhang; Kunmei Su; Jianxiong Li; Zhenhuan Li (Chemical Engineering Journal, 2024)

A hybrid learning approach to model the diversity of window-opening behavior - Yiqiao Liu; Wen Tong Chong; Yat Huang Yau; Jinshun Wu; Yufan Chang; Tong Cui; Li Chang; Song Pan (Building and Environment, 2024)

Mixed sowing improves plant and soil bacterial community restoration in the degraded alpine meadow - Wen Zhao; Yali Yin; Jiangqin Song; Shixiong Li (Plant and Soil, 2024)

MiR-184 Mediated the Expression of ZNF865 in Exosome to Promote Procession in the PD Model - Chang Liu; Yang Wang; Jing-wen Li; Xiaoyan Zhu; Hai-song Jiang; Hong Zhao; Li-ming Zhang (Molecular Neurobiology, 2024)
Exosomes are nanoscale small vesicles (EVs) secreted by cells that carry important bio information, including proteins, miRNAs, and more. Exosome contents are readily present in body fluids, including blood, and urine of humans and animals, and thereby act as markers of diseases. In patients with Parkinson’s disease (PD), exosomes may spread alpha-synuclein and miR-184 between the cells contributing to dopaminergic neuronal loss. In this study, we detected the levels of miR-184 in urine-excreted neuronal exosomes between PD patients and age-matched healthy subjects by qRT-PCR analysis. Transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA) were also used to determine the ultracellular structures of exosomes nanoparticles. MPP + and MPTP were used to construct the cell and animal PD model. Behavioral tests were used to detect motor performance. Furthermore, the cytological experiments were measured to examine the relationship between miR-184 and ZNF865. We found that the levels of miR-184 in urine-derived neuronal exosomes from PD patients were higher, compared to aged-matched normal people. The exosomes from PD patients were larger with greater numbers than those from the age-matched healthy subjects. The difference in miR-184 in urinary exosomes between PD patients and normal people may provide a novel perspective for early diagnosis of PD. However, no difference in CD63 level was observed in Exo-control and Exo-PD groups (exosome from control or PD groups). Moreover, ZNF865 was detected as the targeted gene of miR-184. In addition, miR-184 ASO (miR-184 antisense oligodeoxynucleotide, miR-184 ASO) could rescue the damage of neuronal apoptosis and motor performance in PD mice. Our results showed the miR-184 potential to function as a diagnostic marker of PD. Graphical Abstract

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Temporal dynamics of Grime's CSR strategies in plant communities during 60 years of succession - Yan‐song Zhang; Scott J. Meiners; Yani Meng; Qi Yao; Kun Guo; Wen‐Yong Guo; Shao‐peng Li (Ecology Letters, 2024)
Grime's competitive, stress‐tolerant, ruderal (CSR) theory predicts a shift in plant communities from ruderal to stress‐tolerant strategies during secondary succession. However, this fundamental tenet lacks empirical validation using long‐term continuous successional data. Utilizing a 60‐year longitudinal data of old‐field succession, we investigated the community‐level dynamics of plant strategies over time. Our findings reveal that while plant communities generally transitioned from ruderal to stress‐tolerant strategies during succession, initial abandonment conditions crucially shaped early successional strategies, leading to varied strategy trajectories across different fields. Furthermore, we found a notable divergence in the CSR strategies of alien and native species over succession. Initially, alien and native species exhibited similar ruderal strategies, but in later stages, alien species exhibited higher ruderal and lower stress tolerance compared to native species. Overall, our findings underscore the applicability of Grime's predictions regarding temporal shifts in CSR strategies depending on both initial community conditions and species origin.

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Green manure removal with reduced nitrogen improves saline-alkali soil organic carbon storage in a wheat-green manure cropping system - Fangdi Chang; Hongyuan Zhang; Na Zhao; Peiyi Zhao; Jiashen Song; Ru Yu; Zhengrong Kan; Xiquan Wang; Jing Wang; Hanjiang Liu; Dongxun Han; Xinya Wen; et al. (Science of The Total Environment, 2024)

A randomized double-blind clinical trial: Comparison of oclacitinib with a traditional Chinese herbal medicine product (Dihuang Guiqin capsule) in the treatment of canine atopic dermatitis - Jun-Jie Qin; Hao Zhu; Zhe-Wen Song; Xiao-Jiao Hou; Xiu-Min Wang; Lei Wang; Jian-Xi Li (Research in Veterinary Science, 2024)

Asiaticasics A-O, structurally intriguing coumarins from Toddalia asiatica with potential inflammatory inhibitory activity - Si-Chen Song; Bai-Dong Ren; Xue-Wen Wu; Yi-Fan Xie; Bin Cheng; Qiong Wei; Wen-Hui Pang; Ze-Kai Wu; Xing-Jie Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2024)

Using satellite imagery to estimate CO2 partial pressure and exchange with the atmosphere in the Songhua River - Chunlan Xiong; Hui Tao; Shiwei Liu; Ge Liu; Zhidan Wen; Yingxin Shang; Qiang Wang; Chong Fang; Sijia Li; Kaishan Song (Journal of Hydrology, 2024)

Transoceanic ships as a source of alien dinoflagellate invasions of inland freshwater ecosystems - Lixia Shang; Zhangxi Hu; Yunyan Deng; Jing Li; Yuyang Liu; Xiaoying Song; Xinyu Zhai; Zifeng Zhan; Wen Tian; Jinxiang Xu; Yangchun Han; Hao Shen; et al. (Harmful Algae, 2024)

Starter molds and multi-enzyme catalysis in koji fermentation of soy sauce brewing: A review - Yihao Liu; Guangru Sun; Jingyao Li; Peng Cheng; Qian Song; Wen Lv; Chunling Wang (Food Research International, 2024)

Effects of plastic film mulching on yield, water use efficiency, and nitrogen use efficiency of different crops in China: A meta-analysis - Tiantian Huang; Qianxiang Wu; Yangyang Yuan; Xintong Zhang; Ruiqi Sun; Rui Hao; Xiaohua Yang; Congfeng Li; Xiaoliang Qin; Fangqi Song; Charles O. Joseph; Wen Wang; et al. (Field Crops Research, 2024)

ZnS-coated Yb3+-doped perovskite quantum dots: A stable and efficient quantum cutting photon energy converter for silicon-based electronics - Yue Wang; Nan Ding; Donglei Zhou; Wen Xu; Rui Sun; Wei Li; Yuqi Wang; Liheng Sun; Songtao Hu; Hongwei Song (Chemical Engineering Journal, 2024)

Nutrient characteristics driven by multiple factors in large estuaries during summer: A case study of the Yangtze River Estuary - Lilian Wen; Jinming Song; Jiajia Dai; Xuegang Li; Jun Ma; Huamao Yuan; Liqin Duan; Qidong Wang (Marine Pollution Bulletin, 2024)

Enhancing social vulnerability assessment with energy resilience: A comprehensive study of the Netherlands - Wen Song; Yinshuai Li; Jie Cheng; Ruishan Chen; Jun Wu; Nan Jia (Sustainable Cities and Society, 2024)

Developing efficient, binder-free 3D porous Ti3C2Tx-MXene electrodes for enhanced capacitive deionization towards desalination - Shuli Lei; Tao Yang; Chang Tian; Tao Yan; Xuguang Li; Wen Song; Wei Liu; Liangguo Yan; Yanxia Zhao (Desalination, 2024)

Full carbon upcycling of organophosphorus wastewater enabled by interface photolysis - Zhuochun Huang; Jinshu Huang; Tengyu Liu; Yu Wen; Hongguo Wu; Song Yang; Hu Li (Chemical Engineering Journal, 2024)

Devonian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Wenkun Qie; Kun Liang; Wen Guo; Biao Gao; Junjun Song; Bo Chen; Pu Huang; Li Qiao; Honghe Xu; Jitao Chen; Yucong Sun; Yichun Zhang (Science China Earth Sciences, 2024)

Research on fine collection and interpretation methods of discontinuities on high-steep rock slopes based on UAV multi-angle nap-of-the-object photogrammetry - Shengyuan Song; Mingyu Zhao; Wen Zhang; Fengyan Wang; Jianping Chen; Yongchao Li (Bulletin of Engineering Geology and the Environment, 2024)

Spatial variations of DOM in a diverse range of lakes across various frozen ground zones in China: Insights into molecular composition - Zhidan Wen; Jiarui Han; Yingxin Shang; Hui Tao; Chong Fang; Lili Lyu; Sijia Li; Junbin Hou; Ge Liu; Kaishan Song (Water Research, 2024)

Establishing the global isoscape of leaf carbon in C3 plants through the integrations of remote sensing, carbon, geographic, and physiological information - Xiang Wang; Guo Chen; Joseph Awange; Yongze Song; Qi Wu; Xiaowei Li; Edmund February; Gustavo Saiz; Ralf Kiese; Xing Li; Jingfeng Xiao; Xiaoxiang Zhao; et al. (Remote Sensing of Environment, 2024)

Intelligent multi-objective optimization of 3D printing low-carbon concrete for multi-scenario requirements - Song-Yuan Geng; Qi-Ling Luo; Bo-Yuan Cheng; Li-Xiao Li; Dong-Chang Wen; Wu-Jian Long (Journal of Cleaner Production, 2024)

Sulfide compositions of young Chang’e-5 basalts and implications for sulfur isotopes in lunar basalt sources - Zaicong Wang; Yiheng Li; Wen Zhang; Qi He; Fabin Pan; Zhaochu Hu; Keqing Zong; Yantong Feng; Harry Becker; James M.D. Day; Wenlei Song; Hejiu Hui; et al. (Geochimica et Cosmochimica Acta, 2024)

Tracing DUPAL anomaly evolution in the Tethyan-Indian oceanic mantle - Chao Wang; Shuguang Song; Guochun Zhao; Mark B. Allen; Li Su; Lukáš Ackerman; Jiří Sláma; Donghai Zhang; Tao Wen; Di Feng; Ladislav Strnad (Geochimica et Cosmochimica Acta, 2024)

Corrigendum to “Structural transformations for a subbituminous coal, impact of temperature on gold-tube pyrolysis chars evaluated using HRTEM” [Fuel 311 (2022) 122581] - Wu Li; Yu Song; Wen-bin Yang; Jonathan P. Mathews (Fuel, 2024)

Stochastic processes dominated the soil bacterial community assemblages along an altitudinal gradient in boreal forests - Li Ji; Song Sheng; Fangyuan Shen; Lili Yang; Shizhi Wen; Gongxiu He; Na Wang; Xu Wang; Lixue Yang (CATENA, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Pivotal Role of GSTO2 in Ferroptotic Neuronal Injury After Intracerebral Hemorrhage - Li Lin; Xiao-Na Li; Zhen-Yan Xie; Yong-Zhen Hu; Qing-Shan Long; Yi-Qi Wen; Xiao-Bing Wei; Li-Yang Zhang; Xue-Song Li (Journal of Molecular Neuroscience, 2024)
Previous research has found that an adaptive response to ferroptosis involving glutathione peroxidase 4 (GPX4) is triggered after intracerebral hemorrhage. However, little is known about the mechanisms underlying adaptive responses to ferroptosis. To explore the mechanisms underlying adaptive responses to ferroptosis after intracerebral hemorrhage, we used hemin-treated HT22 cells to mimic brain injury after hemorrhagic stroke in vitro to evaluate the antioxidant enzymes and performed bioinformatics analysis based on the mRNA sequencing data. Further, we determined the expression of GSTO2 in hemin-treated hippocampal neurons and in a mouse model of hippocampus-intracerebral hemorrhage (h-ICH) by using Western blot. After hemin treatment, the antioxidant enzymes GPX4, Nrf2, and glutathione (GSH) were upregulated, suggesting that an adaptive response to ferroptosis was triggered. Furthermore, we performed mRNA sequencing to explore the underlying mechanism, and the results showed that 2234 genes were differentially expressed. Among these, ten genes related to ferroptosis (Acsl1, Ftl1, Gclc, Gclm, Hmox1, Map1lc3b, Slc7a11, Slc40a1, Tfrc, and Slc39a14) were altered after hemin treatment. In addition, analysis of the data retrieved from the GO database for the ten targeted genes showed that 20 items on biological processes, 17 items on cellular components, and 19 items on molecular functions were significantly enriched. Based on the GO data, we performed GSEA and found that the glutathione metabolic process was significantly enriched in the hemin phenotype. Notably, the expression of glutathione S-transferase omega (GSTO2), which is involved in glutathione metabolism, was decreased after hemin treatment, and overexpression of Gsto2 decreased lipid reactive oxygen species level in hemin-exposed HT22 cells. In addition, the expression of GSTO2 was also decreased in a mouse model of hippocampus-intracerebral hemorrhage (h-ICH). The decreased expression of GSTO2 in the glutathione metabolic process may be involved in ferroptotic neuronal injury following hemorrhagic stroke.

Multi-objective optimization of saline water irrigation in arid oasis regions: Integrating water-saving, salinity control, yield enhancement, and CO2 emission reduction for sustainable cotton production - Zhanli Ma; Yan Zhu; Jian Liu; Yanqiang Li; Jinzhu Zhang; Yue Wen; Libing Song; Yonghui Liang; Zhenhua Wang (Science of The Total Environment, 2024)

Boosting solar vapor generation and desalination by low-cost reduced graphene oxide/cellulose aerogel and multiple energy utilization - Jing Li; Wen Song; Yanfei Li; Xuguang Li; Liyuan Yang; Liangguo Yan (Journal of Environmental Chemical Engineering, 2024)

Kinetic studies of the secondary hydrate formation in porous media based on experiments in a cubic hydrate simulator and a new kinetic model - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yi-Song Yu; Qiu-Nan Lv; Yang Yu; Yi-Fan Weng; Jian-Wu Liu; Jian-Xing Yu (Fuel, 2024)

Rational design of highly efficient carbon-based materials for electrochemical CO2 reduction reaction - Song Li; Shuai Li; Zhanhua Wu; Lingyan Qin; Jiaqi Liu; Wen Zhou; Haitao Kang; Lele Gong; Lipeng Zhang (Fuel, 2024)

Community-level bioaugmentation results in enzymatic activity- and aroma-enhanced Daqu through altering microbial community structure and metabolic function - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Correction to: Quantitatively mapping the research status and trends of vegetation responses to climate change with bibliometric analysis - Xinzhe Li; Zhiqiang Wen; Lizhen Cui; Yang Chen; Tong Li; Hongdou Liu; Zhihong Xu; Xiaoyong Cui; Xiufang Song (Journal of Soils and Sediments, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Expansion of YALIcloneHR toolkit for Yarrowia lipolytica combined with Golden Gate and CRISPR technology - Qi Shen; Fang Yan; Ya-Wen Li; Jian Wang; Jia Ji; Wen-Xin Yan; Dan-Chen He; Ping Song; Tian-Qiong Shi (Biotechnology Letters, 2024)

Multipurpose new gas chromatography column based on pillararenes functionalized with imidazolium ionic liquids - Tao Sun; Mengyi Ba; Yanli Song; Wen Li; YuanYuan Zhang; Zhiqiang Cai; Shaoqiang Hu; Xianming Liu; Donatella Nardiello; Maurizio Quinto (Analytica Chimica Acta, 2024)

Phosphorus-doped synergy of phase change in heterogeneous catalysts of NiS–NiS2 for efficient electrocatalysis of Pb(II) - Yong-Yu Li; Kai-Yuan Li; Shi-Hua Chen; Na Ma; Zong-Yin Song; Meng Yang; Jie Wang; Wen-Qing Liu (Analytica Chimica Acta, 2024)

Effect of filling materials on reconstructed soil phosphorus adsorption and desorption in mining area - Kexin Jing; Xiangyu Min; Wen Song; Dongyun Xu; Xinju Li (Soil and Tillage Research, 2024)

Effects of land reclamation on soil organic carbon and its components in reclaimed coal mining subsidence areas - Wen Song; Junying Li; Xinju Li; Dongyun Xu; Xiangyu Min (Science of The Total Environment, 2024)

Exploring the associations between phthalate exposure and cardiometabolic risk factors clustering among children: The potential mediating role of insulin-resistant-related genes DNA methylation - Jieyu Liu; Jieyun Song; Di Gao; Yanhui Li; Tongjun Guo; Wen Yuan; Manman Chen; Li Chen; Yi Zhang; Qi Ma; Mengjie Cui; Xinli Song; et al. (Journal of Hazardous Materials, 2024)

Aspartic acid/arginine enhance the stability of gelatin emulsions - Hui-min Yan; Yu Song; Man-man Yu; Xiu-ning Yao; Wen-wen Zhang; Ying Xu; Xue-qing Li; Yu-qin Xu; Shun Fang; Jun Qi; Guo-yuan Xiong; Chao Li; et al. (Journal of Food Engineering, 2024)

Kinetics studies of methane hydrate formation and dissociation in the presence of cyclopentane - Yi-Song Yu; Wen-Zhe Sun; Chang Chen; Xiao-Sen Li; Zhao-Yang Chen (Fuel, 2024)

A novel chlorophyll-a retrieval model based on suspended particulate matter classification and different machine learning - Chong Fang; Changchun Song; Zhidan Wen; Ge Liu; Xiaodi Wang; Sijia Li; Yingxin Shang; Hui Tao; Lili Lyu; Kaishan Song (Environmental Research, 2024)

Microscopic hyperspectral imaging and an improved detection model based detection of Mycogone perniciosa chlamydospore in soil - Xuan Wei; Yongjie Liu; Qiming Song; Jinping Zou; Zhiqiang Wen; Jiayu Li; Dengfei Jie (European Journal of Agronomy, 2024)

Dynamic relationship between membrane fouling and reverse diffusion of inorganic draw solutes in forward osmosis - Hai-Liang Song; Si-Qi Zhai; Jing Nan; Wen-Jun Cai; Shi-Yun Xu; Yue-Wei Tang; Yu-Li Yang (Desalination, 2024)

Feeding strategy determine flexible biogas via shaping microbial abundance and interaction in anaerobic digestion - Pengjie Wu; Tianyu Bai; Ying Yang; Kunyao Li; Hao Tan; Suyu Zhuang; Fuyu Song; Zuopeng Lv; Hongyu Wen; Haiying Yu (Biomass and Bioenergy, 2024)

Combined metabolome and transcriptome analysis reveals a critical role of lignin biosynthesis and lignification in stem-like pneumatophore development of the mangrove Avicennia marina - Yu-Chen Zhang; Li-Han Zhuang; Jia-Jie Zhou; Shi-Wei Song; Jing Li; He-Zi Huang; Bing-Jie Chi; You-Hui Zhong; Jing-Wen Liu; Hai-Lei Zheng; Xue-Yi Zhu (Planta, 2024)

An investigation of the maintenance mechanisms of the quasi-biweekly Pacific-Japan teleconnection - Yu Zhu; Ruidan Chen; Qingtao Song; Xiuzhen Li; Yuanyuan Guo; Zhiping Wen (Climate Dynamics, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Moraxella haemolytica sp. nov., isolated from a goat with respiratory disease - Fu-Xiang Li; Wen-Hua Zhao; Zhan-Hong Li; Jian-Ling Song; Hua-Feng Gao (Archives of Microbiology, 2024)

Luteolin inhibits angiogenesis and enhances radiotherapy sensitivity of laryngeal cancer via downregulating Integrin β1 - Zhen Li; Hongzhou Ge; Yonggang Xie; Yueqin Zhang; Xiaoyan Zhao; Wen Sun; Meiyan Song (Tissue and Cell, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Farmers perceive diminishing ecosystem services, but overlook dis-services in intensively used agricultural landscapes in the North China Plain - Jiali Cheng; Zhan Xu; Zhengyuan Liang; Fan Li; Wen-Feng Cong; Chaochun Zhang; Lei Song; Chong Wang; Fusuo Zhang; Andries Richter; Wopke van der Werf; Jeroen C.J. Groot (Journal of Environmental Management, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Development and characterization of self-emulsifying high internal phase emulsions using endogenous phospholipids from Antarctic krill oil - Dong-wen Fu; Jing-jing Li; Dong-mei Dai; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Chemistry, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Ultralow thermal conductivity of robust vermiculite aerogels fabricated by fast trivalent cation induced nanosheet gelation - Changrui Shi; Wen Luo; Hongsheng Dong; Yang Zhang; Shuai Wang; Junjie Wang; Yongchen Song; Mingjun Yang; Yanghui Li; Zheng Ling (Chemical Engineering Journal, 2023)

The source, activity influencing factors and biological activities for future development of chitin deacetylase - Bicheng Liang; Wen Song; Ronge Xing; Song Liu; Huahua Yu; Pengcheng Li (Carbohydrate Polymers, 2023)

Shoot Production of Solanum tuberosum L. ‘Yansi’ Using a Simple Continuous Immersion Airlift Bioreactor Culture System - Hang-Lin Song; Rong-de Jin; Xue-Li Quan; Ji-De Zhang; Wen-Wen Qi; Xi-Hua Cui (Potato Research, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Distribution patterns of six metals and their influencing factors in M4 seamount seawater of the Western Pacific - Jun Ma; Xuegang Li; Jinming Song; Lilian Wen; Xianmeng Liang; Kuidong Xu; Jiajia Dai (Marine Pollution Bulletin, 2023)

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Remote estimation of phycocyanin concentration in inland waters based on optical classification - Lili Lyu; Kaishan Song; Zhidan Wen; Ge Liu; Chong Fang; Yingxin Shang; Sijia Li; Hui Tao; Xiang Wang; Yong Li; Xiangyu Wang (Science of The Total Environment, 2023)

Thermal imaging: The digital eye facilitates high-throughput phenotyping traits of plant growth and stress responses - Ting Wen; Jian-Hong Li; Qi Wang; Yang-Yang Gao; Ge-Fei Hao; Bao-An Song (Science of The Total Environment, 2023)

An attention-based multi-scale convolution network for intelligent underwater acoustic signal recognition - Aolong Zhou; Xiaoyong Li; Wen Zhang; Chengwu Zhao; Kaijun Ren; Yanxin Ma; Junqiang Song (Ocean Engineering, 2023)

Effect of regulating dissolved oxygen concentration in pulp with aerated gas on pyrite flotation - Ximei Luo; Wen Yang; Shuming Wen; Qiqiang Lin; Dayong Wei; Chao Li; Ying Zhang; Zhenguo Song; Yunfan Wang (Minerals Engineering, 2023)

New evidence of consistency between phylogeny and morphology for two taxa in ciliated protists, the subclasses Oligotrichia and Choreotrichia (Protista, Ciliophora) - Wen Song; Huixin Jiao; Juan Yang; Danxu Tang; Tingting Ye; Lu Li; Lei Yang; Lifang Li; Weibo Song; Saleh A. Al-Farraj; Hunter N. Hines; Weiwei Liu; et al. (Molecular Phylogenetics and Evolution, 2023)

Multi-stage two-echelon crowdsourcing logistics assignment model with future committing drivers - Ming-Yang Li; Wen-Song Zhang; Yong Wu; Lei Wang (Journal of Cleaner Production, 2023)

Heterogeneous oxidative desulfurization of fuels using amphiphilic mesoporous phosphomolybdate-based poly(ionic liquid) over a wide temperature range - Shao-Xu Mao; Jun-Yi Song; Wen-Shuai Zhu; Hua-Ming Li; Jing-Yu Pang; Dong-Bin Dang; Yan Bai (Fuel, 2023)

An anisotropic electromagnetic hydrogel promotes cardiomyocyte maturation and post-infarction cardiac repair - Xiaopei Li; Peng Lu; Zhaoyang Liu; Ziang Wen; Xiangyu Li; Chufan Wang; Wanjun Jin; Bin Zhou; Ningping Huang; Meijuan Song; Xiaowei Wang (Chemical Engineering Journal, 2023)

Electrochemical oxidation treatment of reverse osmosis concentrated landfill leachate: Effect of operation parameters and evolution of dissolved organic matter - Ye-Chao Tian; Wen-Xiang Ji; Yu-Ze Han; Ze-Tao Wu; Hai-Ou Song; Ai-Min Li; Wen-Tao Li (Chemical Engineering Journal, 2023)

Rationally designed multifunctional nanoparticles as GSH-responsive anticancer drug delivery systems based on host-guest polymers derived from dextran and β-cyclodextrin - Xichuan Tang; Yuting Wen; Zhongxing Zhang; Jingling Zhu; Xia Song; Jun Li (Carbohydrate Polymers, 2023)

Biomass-based single- and double-network hydrogels derived from cellulose microfiber and chitosan for potential application as plant growing substrate - Zhongxing Zhang; Jingling Zhu; Xia Song; Yuting Wen; Chenxian Zhu; Jun Li (Carbohydrate Polymers, 2023)

Fragmentation process of soil aggregates under concentrated water flow in red soil hilly region with different land use patterns - Li-li Wen; Jin-yue Wang; Yu-song Deng; Xiao-qian Duan (Journal of Mountain Science, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Hypothermia-mediated oxidative stress induces immunosuppression, morphological impairment and cell fate disorder in the intestine of freshwater drum, Aplodinotus grunniens - Jianxiang Chen; Pao Xu; Haibo Wen; Miaomiao Xue; Qingyong Wang; Jiyan He; Changchang He; Shengyan Su; Jianlin Li; Fan Yu; Wenrong Feng; Meiyao Wang; et al. (Aquaculture, 2023)

Bacteria rather than fungi mediate the chemodiversity of dissolved organic matter in a mudflat intertidal zone - Kai Ma; Yueyue Li; Xia Liu; Wen Song; Jiayin Zhou; Xiaofan Gong; Mengqi Wang; Chun Li; Jihua Liu; Qichao Tu (Science of The Total Environment, 2023)

Pb-Zn mineralization formed from coupled hydrocarbon-bearing and hydrothermal fluids in the Ediacaran strata in the central Sichuan Basin, China - Lianqiang Zhu; Zezhang Song; Guangdi Liu; Wenzhi Zhao; Long Wen; Xingwang Tian; Wenzhi Wang; Dailin Yang; Wei Yan; Qiang Li (Precambrian Research, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Enhancing degradation of norfloxacin using chrysanthemum-shaped bimetallic NH2-MIL-53(Fe/Ti) photocatalysts under visible light irradiation - Wen Gao; Fangyuan Wang; Meilin Ou; Qianqian Wu; Lei Wang; Haonan Zhu; Yuanyuan Li; Ning Kong; Jianping Qiu; Shanshan Hu; Shuang Song (Journal of Environmental Chemical Engineering, 2023)

Provenance of Early Carboniferous clastic sedimentary rocks in the Lhasa Block, Tibet: Insights into the paleogeography and tectonic evolution of the northern margin of East Gondwana - Meng-Long Duan; Chao-Ming Xie; Bin Wang; Yu-Hang Song; Wen-qing Li; Yu-jie Hao (Journal of Asian Earth Sciences, 2023)

Excessive N applications reduces yield and biological N fixation of summer-peanut in the North China Plain - Wenhai Huang; Yuhao Yang; Haoyu Zheng; Jørgen Eivind Olesen; Robert M. Rees; Jun Zou; Li Zhang; Suya Hu; Bowen Qiao; Xiaohui Wang; Shuaijie Shen; Biaoding Yang; et al. (Field Crops Research, 2023)

Morphology and phylogeny of four trachelocercid ciliates (Ciliophora, Karyorelictea, Trachelocercidae) from North China Sea, with description of a new species - Tingting Ye; Wen Song; Yuqing Li; Khaled A.S. Al-Rasheid; Valentina Serra; Mingzhen Ma (European Journal of Protistology, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Clonal integration under heterogeneous water environment increases plant biomass and nitrogen uptake in a temperate steppe - Yuqiang Tian; Yu Cui; Shuhai Wen; Xiaobing Li; Minghua Song; Xiaoxia Chen; Yong Zhang; Xingliang Xu; Yakov Kuzyakov (Plant and Soil, 2023)

Tree communities and functional traits determine herbivore compositional turnover - Ming-Qiang Wang; Zhixin Wen; Jinzhao Ke; Douglas Chesters; Yi Li; Jing-Ting Chen; Arong Luo; Xiaoyu Shi; Qing-Song Zhou; Xiao-Juan Liu; Keping Ma; Helge Bruelheide; et al. (Oecologia, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

Salidroside promotes healthy longevity by interfering with HSP90 activity - Jianfei Zhang; Zhiquan Li; Jiangbo Song; Lei Zhou; Xin Chen; Wen Ge; Tianyi Dong; Yuxin Luo; Ting Mao; Zheng Li; Duan Tan; Lene Juel Rasmussen; et al. (GeroScience, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A System Dynamics Model of Urban Rainstorm and Flood Resilience to Achieve the Sustainable Development Goals - Wen Li; Rengui Jiang; Hao Wu; Jiancang Xie; Yong Zhao; Yingxue Song; Fawen Li (Sustainable Cities and Society, 2023)

Response of total suspended matter to natural and anthropogenic factors since 1990 in China's large lakes - Hui Tao; Kaishan Song; Ge Liu; Zhidan Wen; Yang Lu; Junbin Hou; Lili Lyu; Qiang Wang; Yingxin Shang; Sijia Li; Chong Fang (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Diverse diterpenoids from Callicarpa rubella Lindl. as natural inhibitors of macrophage foam cell formation - Xue-Wen Wu; Qian-Lang Feng; Yi-Fan Xie; Si-Chen Song; Bin Cheng; Yan Ma; Qing Li; Xu Ji; Xiao-Li Li; Guang Cao; Wei-Lie Xiao (Phytochemistry, 2023)

Differential expression of SLC30A10 and RAGE in mouse pups by early life lead exposure - Ning Li; Liuding Wen; Yue Shen; Tiange Li; Tianlin Wang; Mingwu Qiao; Lianjun Song; Xianqing Huang (Journal of Trace Elements in Medicine and Biology, 2023)

Skeleton engineering of rigid covalent organic frameworks to alter the number of binding sites for improved radionuclide extraction - Xiangbin Lin; Weiwen Xin; Shusen Chen; Yan Song; Linsen Yang; Yongchao Qian; Lin Fu; Yanglansen Cui; Xiaofeng He; Tinyang Li; Zhehua Zhang; Yadong Wu; et al. (Journal of Hazardous Materials, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Zn anode surface engineering for stable zinc-ion batteries: Carbon dots incorporated mesoporous TiO2 as a coating layer - Tian-Bing Song; Qian-Li Ma; Xi-Rong Zhang; Jia-Wen Ni; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Spartina alterniflora invasion differentially alters microbial residues and their contribution to soil organic C in coastal marsh and mangrove wetlands - Xueli Ding; Weiqi Wang; Jiahui Wen; Tianshu Feng; Josep Peñuelas; Jordi Sardans; Chao Liang; Evgenios Agathokleous; Chun Wang; Zhaoliang Song; Qiang Li; Timothy R. Filley; et al. (CATENA, 2023)

Low CO2 partial pressure steers CHO cells into a defective metabolic state - Liang Zhao; Chen Wang; Jiaqi Wang; Li Fan; Min Chen; Qian Ye; Wen-Song Tan (Biotechnology Letters, 2023)

Prevalence and genetic variation of the M, N, and S2 genes of feline coronavirus in Shandong Province, China - Xiao-Li Song; Wen-Feng Li; Hu Shan; Hai-Yan Yang; Chuan-Mei Zhang (Archives of Virology, 2023)

Evolutionary roles of polyploidization‐derived structural variations in the phenotypic diversification of Panax species - Yu‐Xin Zhang; Xin‐Feng Wang; Yu‐Qian Niu; Yu‐Guo Wang; Wen‐Ju Zhang; Zhi‐Ping Song; Ji Yang; Lin‐Feng Li (Molecular Ecology, 2023)
Genomic structural variations (SVs) are widespread in plant and animal genomes and play important roles in phenotypic novelty and species adaptation. Frequent whole genome duplications followed by (re)diploidizations have resulted in high diversity of genome architecture among extant species. In this study, we identified abundant genomic SVs in the Panax genus that are hypothesized to have occurred through during the repeated polyploidizations/(re)diploidizations. Our genome‐wide comparisons demonstrated that although these polyploidization‐derived SVs have evolved at distinct evolutionary stages, a large number of SV‐intersecting genes showed enrichment in functionally important pathways related to secondary metabolites, photosynthesis and basic cellular activities. In line with these observations, our metabolic analyses of these Panax species revealed high diversity of primary and secondary metabolites both at the tissue and interspecific levels. In particular, genomic SVs identified at ginsenoside biosynthesis genes, including copy number variation and large fragment deletion, appear to have played important roles in the evolution and diversification of ginsenosides. A further herbivore deterrence experiment demonstrated that, as major triterpenoidal saponins found exclusively in Panax , ginsenosides provide protection against insect herbivores. Our study provides new insights on how polyploidization‐derived SVs have contributed to phenotypic novelty and plant adaptation.

An advanced treatment process for 3-high wastewater discharged from crude oil storage tanks - Xue-Wen Li; Zhong-Yi Cui; Bao-Fu Zhao; Jin-An Wang; Yue-Qin Song; Xiao-Long Zhou (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Environmental heterogeneity and dispersal limitation simultaneously determine the spatial scaling of different microbial functional groups - Yueyue Li; Kai Ma; Wen Song; Jiayin Zhou; Xia Liu; Mengqi Wang; Qichao Tu (Science of The Total Environment, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Liver-cell protective pyridones from the fungi Tolypocladium album dws120 - Xiao-Qian Wu; Jing Li; Xi Zhou; Jing Wang; Yu-Fen Tan; Ji-Song Mo; Shao Liu; Kang-Ping Xu; Gui-Shan Tan; Wei Zhang; Wen-Xuan Wang (Phytochemistry, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

Jinggangmycin stimulates reproduction and increases CHCs-dependent desiccation tolerance in Drosophila melanogaster - Wei Dong; Wen-Jun Wu; Chen-Yang Song; Ting Li; Jian-Zhen Zhang (Pesticide Biochemistry and Physiology, 2023)

Anomaly diagnosis of stay cables based on vehicle-induced cable force sums - De-Long Li; Dong-Hui Yang; Ting-Hua Yi; Song-Han Zhang; Wen-Jie Li; Chong Li (Engineering Structures, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Quantitatively mapping the research status and trends of vegetation responses to climate change with bibliometric analysis - Xinzhe Li; Zhiqiang Wen; Lizhen Cui; Yang Chen; Tong Li; Hongdou Liu; Zhihong Xu; Xiaoyong Cui; Xiufang Song (Journal of Soils and Sediments, 2023)
Purpose Vegetation is a typical sensitive indicator of climate change, and therefore provides theoretical and valuable information for addressing issues arising from climate change including improving soil ecosystem services. Exploring how vegetation responses to climate change has become one of major hotspots of research. However, few scholars have performed bibliometric analyses of this field. This study investigated the current research activities and the trend developments of vegetation responses to climate change. Materials and methods We conducted a quantitative bibliometric analysis of 2,310 publications on vegetation responses to climate change from 1991 to 2021 retrieved in the Web of Science Core Collection. The analysis comprised significant journals, disciplines, and scholars, as well as partnerships between countries and institutions, keyword co-occurrence and burst analysis. The bibliometric analysis tools, Histcite, Vosviewer, CiteSpace software, and R (Bibliometrix package), were applied. Results and discussion The related publications on vegetation responses to climate change had been increasing exponentially in the past 30 years and its total global cited score reached its peak in 2010. The USA and China were the leading countries, with the Chinese Academy of Sciences having the highest number of publications and citations. The scholars who had the most citations were Allen CD, Bresears DD, and Running SW. Six research clusters were generated by keywords co-occurrence analysis, including impact, response, CO 2 , growth, climate change, and vegetation. These clusters represented the current research topics that highlighted the responses of vegetation to climate change, the manifestation of its impact, and coping strategies. In future research on vegetation, the emphasis is expected to be placed on “human activities” and “N 2 O emission”. Conclusion This study has performed a comprehensive and systematic and quantitative analysis of the publications on the responses of vegetation to climate change. The results reveal the characteristics, development patterns, and research trends of studies on vegetation activity in response to climate change, which sheds new insights into understanding the relationship between soil and climate.

Recent Advances in Understanding Multi-scale Climate Variability of the Asian Monsoon - Wen Chen; Renhe Zhang; Renguang Wu; Zhiping Wen; Liantong Zhou; Lin Wang; Peng Hu; Tianjiao Ma; Jinling Piao; Lei Song; Zhibiao Wang; Juncong Li; et al. (Advances in Atmospheric Sciences, 2023)

In-situ detection equipment for radon-in-water: unattended operation and monthly investigations - Chunqian Li; Meng Li; Guangquan Chen; Huaming Yu; Chenglun Zhang; Wen Liu; Jinjia Guo; Shibin Zhao; Lijun Song; Xiliang Cui; Ying Chai; Lu Cao; et al. (Acta Oceanologica Sinica, 2023)

Measuring 222Rn in aquatic environment via Pulsed Ionization Chamber Radon Detector - Lijun Song; Wen Liu; Shibin Zhao; Chunqian Li; Jinjia Guo; Natasha Dimova; Bochao Xu (Acta Oceanologica Sinica, 2023)

Santalane-type sesquiterpenoids and isobenzofuranones from cultures of Paraconiothyrium sporulosum YK-03 - Li-Hua Zhang; Wen-Ke Gao; Shi-Wei Li; Xiao-Yan Song; Hong-Hua Wu; Hai-Feng Wang; Gang Chen; Shao-Xia Wang; Yue-Hu Pei (Phytochemistry, 2023)

Using a microbial fuel cell to balance the carbon‑nitrogen mismatch in submerged fixed-bed reactors for the resilient treatment of mariculture wastewater - Zuoliang Sun; Yuanrong Wei; Xiefa Song; Brendan T. Higgins; Zhitao Huang; Wen Hao; Meng Li (Journal of Water Process Engineering, 2023)

Sentinel-3 OLCI observations of Chinese lake turbidity using machine learning algorithms - Yong Li; Sijia Li; Kaishan Song; Ge Liu; Zhidan Wen; Chong Fang; Yingxin Shang; Lili Lyu; Lele Zhang (Journal of Hydrology, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Chemical characterization and source attribution of organic pollutants in industrial wastewaters from a Chinese chemical industrial park - Yihua Huang; Yinong You; Manman Wu; Min Han; Jin Zhang; Wei Gao; Danping Xie; Hongzhan Chen; Hui Ou; Ninghui Song; Chunlei Cheng; Wen Zhuang; et al. (Environmental Research, 2023)

Soil reconstruction and heavy metal pollution risk in reclaimed cultivated land with coal gangue filling in mining areas - Wen Song; Ruiping Xu; Xinju Li; Xiangyu Min; Jinning Zhang; Huizhong Zhang; Xiao Hu; Junying Li (CATENA, 2023)

Chitinolyticbacter albus sp. Nov., A Novel Chitin-Degrading Bacterium Isolated from Ancient Wood Rhizosphere Soil - Meng-Yu Zhang; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Zhu-Feng Shi; Zhang-Gui Ding; et al. (Current Microbiology, 2023)

A residual network with geographical and meteorological attention for multi-year ENSO forecasts - Dan Song; Yuting Ling; Tong Hao; Wenhui Li; Wen Liu; Tongwei Ren; Zhiqiang Wei; An-an Liu (Frontiers in Marine Science, 2023)
Introduction As global temperatures continue to rise, extreme weather phenomena such as El Niño and the Southern Oscillation (ENSO) near the equatorial Pacific Ocean are occurring more frequently and leading to tropical cyclones, droughts, and a series of extreme weather disasters. Accurately predicting ENSO in advance can greatly reduce the serious damage to human society, economy, and ecological environment. However, existing methods often neglect the data relation between geographical regions and meteorological factors, hindering the accuracy of ENSO prediction. Methods To overcome this problem, we propose a residual network with geographical and meteorological attention to capture important geographical information and explore the spatio-temporal correlation of different meteorological factors. Specifically, we propose two main attention modules: (1) the Geographical Semantic Information Enhancement Module (GSIEM), which selectively attends to important geographical regions and filters out irrelevant noise through a spatial-axis attention map, and (2) the Meteorological Factors Discriminating Enhancement Module (MFDEM), which aims to learn the spatio-temporal dependency of different meteorological factors using a learnable channel-axis weight map. We then integrate our proposed two attention modules into the backbone using residual connection, enhancing the model's prediction ability. Results We conducted extensive experimental comparisons and ablation studies to evaluate the performance of our proposed method. The results show that our method outperforms existing state-of-the-art methods in ENSO prediction, with a significant improvement in prediction accuracy. Discussion Our proposed method effectively captures geographical and meteorological information, facilitating accurate ENSO prediction. The attention modules we proposed can effectively filter out irrelevant noise and learn the spatio-temporal dependency of different meteorological factors, contributing to the superior performance of our model. Overall, our study provides a novel approach for ENSO prediction and has great potential for practical applications.

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Control of N-nitrosodimethylamine (NDMA) formation from N,N-dimethylhydrazine compounds by ozone-based advanced oxidation processes - Yang Song; Jianshan Peng; Kai Li; Sha Feng; Wen Qin; Jin Jiang; Jun Ma (Journal of Hazardous Materials, 2023)

Genesis of the Yawan Sb deposit, West Qinling Orogen, Central China: Constraints from S–Pb–C–O isotopes and Sm Nd geochronology - Zhao-yang Song; Yan-chen Yang; Shi-jiong Han; Bao-yi Li; Zi-jian Zeng; Tian-wen Chen (Journal of Geochemical Exploration, 2023)

Development of an Antarctic krill oil based self-microemulsion drug delivery system and its enhancement of bioaccessibility for curcumin - Dong-wen Fu; Ye Tian; Zi-han Wang; Jin-zhe Li; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Bioscience, 2023)

Bifunctional catalytic degradation of diclofenac over Cu–Pd co-modified sponge iron-based trimetal: Parameter optimization - He Li; Yongquan Shi; Wenchao Jia; Yu Gong; Ninghui Song; Ziyan Du; Xiang Shao; Wen Gu; Weilong Xing; Yongming Ju (Environmental Research, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

Ultrahigh solar vapor evaporation rate of super-hydrophilic aerogel by introducing environmental energy and convective flow - Jing Li; Yujiao Shao; Wen Song; Xuguang Li; Yanfei Li; Liyuan Yang; Xinghua Xie; Liangguo Yan (Chemical Engineering Journal, 2023)

Pseudomonas subflava sp. nov., a new Gram-negative bacterium isolated from Guishan in Yunnan province, south–west China - Cheng Ling; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Yao Lu; et al. (Antonie van Leeuwenhoek, 2023)

Full-scale pore characteristics in coal and their influence on the adsorption capacity of coalbed methane - Yunbo Li; Wen Liu; Dangyu Song; Zixian Ren; Haifeng Wang; Xingxin Guo (Environmental Science and Pollution Research, 2023)

Combining mechanisms of black carbon and magnetic minerals in power plant fly ash - Meng Yao Li; Zhou Xin Peng; You Ying Chen; Shi Yun Xiao; Bo Wen Zhang; Yi Xin Shen; Sheng Kang Wang; Xue Song Wang; Zhao Xiang Han (Science of The Total Environment, 2023)

Enhanced diesel emissions at low ambient temperature: hazardous materials in fine particles - Wei W. Song; Wen X. Fang; Huan Liu; Wen L. Li; Zhi Zhang; Chun H. Li; Dajiang Yu; Qing Zhao; Xian S. Wang; Ke B. He (Journal of Hazardous Materials, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Scheduling single-satellite observation and transmission tasks by using hybrid Actor-Critic reinforcement learning - Zhijiang Wen; Lu Li; Jiakai Song; Shengyu Zhang; Haiying Hu (Advances in Space Research, 2023)

Distinct ecological mechanisms drive the spatial scaling of abundant and rare microbial taxa in a coastal sediment - Xia Liu; Hongjun Li; Wen Song; Qichao Tu (Journal of Biogeography, 2023)
Aim Revealing the ecological mechanisms driving the diversity patterns of microbial communities across space and through time is an essential issue in microbial biogeography. This study links microbial spatial scaling with ecological mechanisms, aiming to provide novel mechanistic insights into the biogeographic patterns followed by different types of microbes. Location Beibu Gulf, a semi‐enclosed oceanic bay located on the southern coast of China. Taxon Bacteria, which were further classified as abundant and rare taxa. Methods By employing high throughput sequencing, two typical spatial scaling models, diversity‐area (DAR) and distance‐decay relationships (DDR), were investigated for the abundant and rare microbial communities in a coastal sediment ecosystem. Both alpha‐ and beta‐diversity indices were extended to Hill numbers to verify the contribution of abundant and rare taxa to DAR and DDR. The iCAMP approach was used to quantify the contribution of different ecological processes in structuring microbial communities. Results Strong spatial scaling patterns were observed for the whole communities and the rare subcommunities but only weak patterns for the abundant subcommunities. Rare subcommunities were mainly responsible for the observed spatial scaling patterns, as confirmed by extending spatial scaling diversity metrics to Hill numbers. Both environmental heterogeneity and local community assembly mechanisms drove the spatial scaling of microbial communities. Strong ecological drift and dispersal limitation underlay the spatial scaling of rare subcommunities, whereas high homogeneous selection weakened the spatial scaling of abundant subcommunities. Main Conclusions Rare taxa were mainly responsible for the biogeographic patterns followed by sediment microbial communities in the Beibu Gulf. Distinct ecological mechanisms underlay the different biogeographic patterns followed by abundant and rare subcommunities.

(NH4)2Mo3S13/MnFe2O4 hybrid with multiple active sites boosted activation of peroxymonosulfate for removal of tetracycline - Xuguang Li; Qiaodi Wang; Xiaoyu Zheng; Le Wang; Wei Zhang; Wen Song; Yanfei Li; Weiyan Pan; Tianyang Zhao; Liangguo Yan (Environmental Science and Pollution Research, 2023)

Triassic granitoids in the East Kunlun Orogenic Belt, Northwestern China: magmatic source and implications for geodynamic evolution - Zhi-He Xu; Wei Xin; Xiao-Dong Zhou; Qing-Lin Xu; Fu-Wen Li; Zhao-Jun Song (International Geology Review, 2023)

A new β -class milbemycin derivative from a mutant of genetically engineered strain Streptomyces avermitilis AVE-H39 - Huan Qi; Cheng-Hong Zhang; Shao-Yong Zhang; Wen-Shuai Song; Wen-Sheng Xiang; Li-Qin Zhang; Ji-Dong Wang (Natural Product Research, 2023)

Modeling the Operating Performance of a Drinking Water Biological Aerated Filter and the Formation of Organic Nitrogen - Jia Kang; Chu-qiong Song; Ning Zhou; Yao-wen Zhang; Shu-li Liu; Gang-fu Song; Wa-ni Zhou (Environmental Science and Pollution Research, 2023)

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

Potential capture and conversion of CO2 from oceanwater through mineral carbonation - Wen Zhuang; Xiaocheng Song; Min Liu; Qian Wang; Jinming Song; Liqin Duan; Xuegang Li; Huamao Yuan (Science of The Total Environment, 2023)

Knockdown of Sly-miR160a using short tandem target mimic (STTM) enhanced expression of auxin signaling genes and delayed postharvest ripening of tomato fruit - Francine Ngaffo Mekontso; Shuhui Wu; Ruizuo Fu; Wen Li; Lanhuan Meng; Qing Wang; Jiangkuo Li; Hongmiao Song; Xiangbin Xu (Postharvest Biology and Technology, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Bacteria and filamentous fungi running a relay race in Daqu fermentation enable macromolecular degradation and flavor substance formation - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2023)

N-acetylcysteine promotes the proliferation of porcine adipose-derived stem cells during in vitro long-term expansion for cultured meat production - Wen-Juan Song; Pei-Pei Liu; Zi-Qing Meng; Shi- Jie Ding; Hui- Xia Li (Food Research International, 2023)

Fucoidan/κ-carrageenan mixed gel: Effect of anions of different valence including chloride, bromide, iodide, sulfate and phosphate - Nan Wang; Jie Tian; Li Guo; Xueting Chen; Bingbing Hu; Shuang Song; Chengrong Wen (Food Hydrocolloids, 2023)

Fluorinated metal–organic frameworks for enhanced stability and iodine adsorption selectivity under humid conditions - Wen Zhang; Jian Zhang; Xiuting Dong; Menglin Li; Qing He; Song Zhao; Lixin Xie (Chemical Engineering Journal, 2023)

Microbiome Structure and Mucosal Morphology of Jejunum Appendix and Colon of Rats in Health and Dysbiosis - Chenyi Shao; Xiaobo Song; Lili Wang; Hongying Zhang; Yinhui Liu; Chunhao Wang; Shenmin Chen; Baowei Ren; Shu Wen; Jing Xiao; Li Tang (Current Microbiology, 2023)
Gut microbiota contributes to human health. Plenty of studies demonstrate that antibiotics can disrupt gut ecosystem leading to dysbiosis. Little is known about the microbial variation of appendix and its up/downstream intestine after antibiotic treatment. This study aimed to investigate the microbiome and mucosal morphology of jejunum, appendix, and colon of rats in health and dysbiosis. A rodent model of antibiotic-induced dysbiosis was employed. Microscopy was used to observe mucosal morphological changes. 16S rRNA sequencing was performed for identifying bacterial taxa and microbiome structure. The appendices of dysbiosis were found enlarged and inflated with loose contents. Microscopy revealed the impairment of intestinal epithelial cells. High-throughput sequencing showed the Operational Taxonomic Units changed from 361 ± 33, 634 ± 18, 639 ± 19 in the normal jejunum, appendix, colon to 748 ± 98, 230 ± 11, 253 ± 16 in the disordered segments, respectively. In dysbiosis, Bacteroidetes translocated inversely from the colon and appendix (0.26%, 0.23%) to the jejunum (13.87% ± 0.11%); the relative abundance of all intestinal Enterococcaceae increased, while Lactobacillaceae decreased. Several bacterial clusters were found correlated to the normal appendix, whereas nonspecific clusters correlated to the disordered appendix. In conclusion, species richness and evenness reduced in the disordered appendix and colon; similar microbiome patterns were shared between the appendix and colon regardless of dysbiosis; site-specific bacteria were missing in the disordered appendix. Appendix is likely a transit region involving in upper and lower intestinal microflora modulation. The limitation of this study is all the data were derived from rats. We must be cautious about translating the microbiome results from rats to humans.

An environmentally insensitive fluorescent probe for G4 DNA detection: Design, synthesis, and mechanism studies - Xue-Xian Lang; Shu-Hui Sun; Hao-Wen Cao; Yan-Song Chen; Hong-Yao Li; Ming-Qi Wang (Analytica Chimica Acta, 2023)

Spatial-temporal transformer network for multi-year ENSO prediction - Dan Song; Xinqi Su; Wenhui Li; Zhengya Sun; Tongwei Ren; Wen Liu; An-An Liu (Frontiers in Marine Science, 2023)
The El Niño-Southern Oscillation (ENSO) is a quasi-periodic climate type that occurs near the equatorial Pacific Ocean. Extreme periods of this climate type can cause terrible weather and climate anomalies on a global scale. Therefore, it is critical to accurately, quickly, and effectively predict the occurrence of ENSO events. Most existing research methods rely on the powerful data-fitting capability of deep learning which does not fully consider the spatio-temporal evolution of ENSO and its quasi-periodic character, resulting in neural networks with complex structures but a poor prediction. Moreover, due to the large magnitude of ocean climate variability over long intervals, they also ignored nearby prediction results when predicting the Niño 3.4 index for the next month, which led to large errors. To solve these problem, we propose a spatio-temporal transformer network to model the inherent characteristics of the sea surface temperature anomaly map and heat content anomaly map along with the changes in space and time by designing an effective attention mechanism, and innovatively incorporate temporal index into the feature learning procedure to model the influence of seasonal variation on the prediction of the ENSO phenomenon. More importantly, to better conduct long-term prediction, we propose an effective recurrent prediction strategy using previous prediction as prior knowledge to enhance the reliability of long-term prediction. Extensive experimental results show that our model can provide an 18-month valid ENSO prediction, which validates the effectiveness of our method.

Enhancing Power Transmission Stability of AUV’s Wireless Power Transfer System with Compact Planar Magnetic Coupler - Haibing Wen; Jiayuan Li; Kehan Zhang; Jinying Ye; Zhengchao Yan; Baowei Song; Xiangqian Tong (Journal of Marine Science and Engineering, 2023)
In this paper, a wireless power transfer (WPT) system with a compact planar magnetic coupler for an autonomous underwater vehicle (AUV) is proposed. A passive induction (PI) coil is integrated into the circular transmitter (Tx) coil to build a uniform magnetic field (UMF), which can guarantee the stable output of the WPT system under uncertain radial and axial misalignments for AUV. Based on normalized magnetic induction intensity distribution analysis, a UMF constructing method with a PI coil is given, aiming to eliminate the fluctuation of magnetic field intensity, and the PI coil design principles and flow chart are obtained. The theoretical analysis shows the proposed integrated coil can effectively enhance the radial misalignment tolerance compared with a conventional circular spiral coil. The zero-phase angle (ZPA) input condition can be achieved by adjusting the series capacitor connected with the Tx coil in S-S compensation topology. Experimental results show that the proposed magnetic coupler containing an integrated coil significantly improves the stability of output power and power transfer efficiency within the possible radial and axial misalignments compared with a conventional coupler. It was demonstrated that the output power changes less than 5.5% and the power transfer efficiency maintains at approximately 84.5% in arbitrary radial positions within the possible working region with an axial transfer distance of 50 mm in saltwater.

Quality prediction of tractor rotary tillage based on BiConvLSTM with self-attention - Ruo-chen Li; Chang-kai Wen; Shu-yan Li; Rui Li; Hong-yu Pu; Yu Jiang; Zheng-he Song (Computers and Electronics in Agriculture, 2023)

Potential risks of CO2 removal project based on carbonate pump to marine ecosystem - Liqin Duan; Jinming Song; Xuegang Li; Huamao Yuan; Wen Zhuang (Science of The Total Environment, 2023)

ApCYP4C6 participates in the metabolism of glucosinolates in pea aphids Acyrthosiphon pisum - Lei Liu; Wen-Jun Wang; Li-Wen Song; Yi-Ting Wu; Jiang-Wen Wei; Sen-Shan Wang; Jing-Jiang Zhou (Journal of Asia-Pacific Entomology, 2023)

Tracing tectonic processes from Proto- to Paleo-Tethys in the East Kunlun Orogen by detrital zircons - Di Feng; Chao Wang; Shuguang Song; Lu Xiong; Guibin Zhang; Mark B. Allen; Jie Dong; Tao Wen; Li Su (Gondwana Research, 2023)

Evaluation the food safety of cultured fat via detection of residues of adipogenic differentiation cocktail in cultured fat with high performance liquid chromatography and enzyme-linked immunosorbent assay - Wen-Juan Song; Pei-Pei Liu; Chun-Bao Li; Hui- Xia Li; Shi- Jie Ding; Guang-Hong Zhou (Food Research International, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

MOF-derived ultrasmall Ru@RuO2 heterostructures as bifunctional and pH-universal electrocatalysts for 0.79 V asymmetric amphoteric overall water splitting - Zhe Li; Jizhao Zou; Tao Liang; Xinrui Song; Zhangjian Li; Jiaming Wen; Minggui Peng; Xierong Zeng; Haitao Huang; Hongliang Wu (Chemical Engineering Journal, 2023)

Corrigendum to “miR-7-5p overexpression suppresses cell proliferation and promotes apoptosis through inhibiting the ability of DNA damage repair of PARP-1 and BRCA1 in TK6 cells exposed to hydroquinone” [Chem. Biol. Interact. 283 (2018) 84–90] - Hao Luo; Hairong Liang; Yuting Chen; Shaoyun Chen; Yongchun Xu; Longmei Xu; Jiaxian Liu; Kairu Zhou; Jucheng Peng; Guoqiang Guo; Bei Lai; Li Song; et al. (Chemico-Biological Interactions, 2023)

Transferring a new Fusarium head blight resistance locus FhbRc1 from Roegneria ciliaris into wheat by developing alien translocation lines - Rongrong Song; Yifan Cheng; Mingxing Wen; Xinying Song; Tong Wang; Mengshuang Xia; Haojie Sun; Menghao Cheng; Huimin Cui; Chunxia Yuan; Xiaoxue Liu; Zongkuan Wang; et al. (Theoretical and Applied Genetics, 2023)

Glucocorticoid and glycolysis inhibitors cooperatively abrogate acute graft-versus-host disease - Qi Wen; Zheng-Li Xu; Yu Wang; Meng Lv; Yang Song; Zhong-Shi Lyv; Tong Xing; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

In silico analysis of NAC gene family in the mangrove plant Avicennia marina provides clues for adaptation to intertidal habitats - Shiwei Song; Dongna Ma; Chaoqun Xu; Zejun Guo; Jing Li; Lingyu Song; Mingyue Wei; Ludan Zhang; You-Hui Zhong; Yu-Chen Zhang; Jing-Wen Liu; Bingjie Chi; et al. (Plant Molecular Biology, 2023)

Elevation of hsa-miR-7-5p level mediated by CtBP1-p300-AP1 complex targets ATXN1 to trigger NF-κB-dependent inflammation response - Li-Qiong Lou; Wen-Qiang Zhou; Xin Song; Zhi Chen (Journal of Molecular Medicine, 2023)

Multi-locus gene editing effectively knocked out cyp19a1a and foxl2 in Monopterus albus, a hermaphroditic fish - Mingxi Hou; Ke Feng; Hongrui Luo; Yinjun Jiang; Wen Xu; Yongming Li; Binbin Tao; Ji Chen; Zuoyan Zhu; Yanlong Song; Wei Hu (Aquaculture, 2023)

The effects of seawater thermodynamic parameters on the oxygen minimum zone (OMZ) in the tropical western Pacific Ocean - Jun Ma; Xuegang Li; Jinming Song; Lilian Wen; Qidong Wang; Kuidong Xu; Jiajia Dai; Guorong Zhong (Marine Pollution Bulletin, 2023)

Bioelectrochemical systems for enhanced nitrogen removal with minimal greenhouse gas emission from carbon-deficient wastewater: A review - Hongbo Liu; Song Qin; Anze Li; Jian Wen; Eric Lichtfouse; Heping Zhao; Xianzhong Zhang (Science of The Total Environment, 2023)

Sonocatalytic removal of tetracycline in the presence of S-scheme Cu2O/BiFeO3 heterojunction: Operating parameters, mechanisms, degradation pathways and toxicological evaluation - Xin Wang; Xue-Song He; Chun-Yu Li; Shi-Lin Liu; Wen Lu; Zheng Xiang; Yang Wang (Journal of Water Process Engineering, 2023)

Degradation mechanism and pathway of tetracycline in milk by heterojunction N-TiO2-Bi2WO6 film under visible light - Yuedeng Tang; Ting Li; Wenxuan Xiao; Zitong Huang; Huicui Wen; Wenbei Situ; Xianliang Song (Food Chemistry, 2023)

Synergistic engineering of structural and electronic regulation of In2Se3 for ultrastable Li − ion battery - Guanhua Zhang; Xiaojing Li; Donghai Wei; Huihuang Yu; Jinghua Ye; Song Chen; Wen Zhang; Jian Zhu; Xidong Duan (Chemical Engineering Journal, 2023)

A novel spiro-heterocycle milbemycin metabolite from a genetically engineered strain of Streptomyces bingchenggensis - Zhi-Kui Hao; Shao-Yong Zhang; Huan Qi; Wen-Sheng Xiang; Jian-Song Li; Ji-Dong Wang (Natural Product Research, 2023)

Increased Soluble Epoxide Hydrolase Activity Positively Correlates with Mortality in Heart Failure Patients with Preserved Ejection Fraction: Evidence from Metabolomics - Liyuan Peng; Ziping Song; Chengcheng Zhao; Kudusi Abuduwufuer; Yanwen Wang; Zheng Wen; Li Ni; Chenze Li; Ying Yu; Yi Zhu; Hualiang Jiang; Jinshan Shen; et al. (Phenomics, 2023)

Residue depletion of danofloxacin in Yellow River carp (Cyprinus carpio haematopterus) following multiple oral administration - Zhe-Wen Song; Fang Yang; Yue Liu; Hao-Tian Shao; Mei Zhang; Jun-Cheng Chen; Kai-Li Ma; Fan Yang (Aquaculture, 2023)

E2F4 regulates cell cycle to mediate embryonic development in pigs - Wen-Jie Jiang; Ming-Hong Sun; Xiao-Han Li; Song-Hee Lee; Geun Heo; Dongjie Zhou; Xiang-Shun Cui (Theriogenology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Heavy rare earth element and crustal-derived silicon enrichment in Huayangchuan carbonatites, Qinling orogenic belt - Chun-wan Wei; Cheng Xu; Wen-lei Song; Wei Chen; Aiguo Shi; Zhuoqi Li; Chaoxi Fan (Lithos, 2023)

Coordination engineering strategy of iron single-atom catalysts boosts anti-Cu(II) interference detection of As(III) with a high sensitivity - Pei-Hua Li; Zong-Yin Song; Xiang-Yu Xiao; Bo Liang; Meng Yang; Shi-Hua Chen; Wen-Qing Liu; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Frequency response characteristics of a thermally coupled three-stage Stirling-type pulse tube cryocooler capable of achieving 110 mW@7 K - Fengshuo Wen; Shaoshuai Liu; Wenting Wu; Jiantang Song; Nanxi Li; Zhenhua Jiang; Yinong Wu (International Journal of Refrigeration, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Causal effects of air pollution on mental health among Adults——An exploration of susceptible populations and the role of physical activity based on a longitudinal nationwide cohort in China - Ke Ju; Liyong Lu; Wen Wang; Ting Chen; Chenyu Yang; En Zhang; Zongyou Xu; Shanshan Li; Jiangning Song; Jay Pan; Yuming Guo (Environmental Research, 2023)

Supercooled sugar alcohols stabilized by alkali hydroxides for long-term room-temperature phase change solar-thermal energy storage - Xiaoxiang Li; Jingyi Zhang; Yizhe Liu; Yangzhe Xu; Kehang Cui; Zhenpeng Yao; Benwei Fu; Chengyi Song; Wen Shang; Peng Tao; Tao Deng (Chemical Engineering Journal, 2023)

Highly efficient and robust nickel-iron bifunctional catalyst coupling selective methanol oxidation and freshwater/seawater hydrogen evolution via CO-free pathway - Xiangbowen Du; Mingwu Tan; Tong Wei; Hisayoshi Kobayashi; Junjie Song; Zhengxin Peng; Hongliang Zhu; Zhikang Jin; Renhong Li; Wen Liu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

A high-efficient and low-consumption nanoimprint method to prepare large-area and high-quality Nafion array for the ordered MEA of fuel cell - Yali Li; Qinglin Wen; Jiaqi Qin; Siyi Zou; Fandi Ning; Chuang Bai; Saifei Pan; Hanqing Jin; Pengpeng Xu; Min Shen; YuJiang Song; Xiaochun Zhou. (Chemical Engineering Journal, 2023)

SBA-15-supported ultrastable Mo2N@CN catalysts for hydrodeoxygenation of guaiacol - Fan Wang; Chenglong Wen; Mohong Lu; Peng Zhang; Jie Zhu; Mingshi Li; Yuhua Shan; Chunshan Song (Biomass and Bioenergy, 2023)

Drug-induced microglial phagocytosis in multiple sclerosis and experimental autoimmune encephalomyelitis and the underlying mechanisms - Wen-Yuan Ju; Qing Wang; Li-Juan Song; Zhi-Bin Ding; Xiao-Hui Li; Gajendra Kumar; Yuqing Yan; Cun-Gen Ma (Molecular Biology Reports, 2023)

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

Effect of divalent cations on electrochemiluminescence of metal-organic frameworks in bioassay - Xuyu Feng; Bin Li; Longyi Zhu; Wen Chen; Ying Wu; Yanru Duan; Meiyan Song; Ying Wan; Shengyuan Deng (Analytica Chimica Acta, 2023)

A feasibility study on the use of hydrophobic eutectic solvents as pseudo-stationary phases in capillary electrophoresis for chiral separations - Ang Li; Song Xue; Yu Xu; Sihui Ding; Di Wen; Qi Zhang (Analytica Chimica Acta, 2023)

A Fundamental Role of Slope Aspect and Elevation in Controlling Diversity Patterns of Soil Bacterial Communities: Insights from an Arid-Montane Ecosystem in China - Long-Fei Chen; Jun-Qia Kong; Zhi-Bin He; Wen-Zhi Zhao; Ming-Dan Song; Yue-Mei Li; Yuan Gao; Shu-Ping Yang (Journal of Soil Science and Plant Nutrition, 2022)

Characterization of a novel victorivirus from Nigrospora chinensis, a fungus isolated from tobacco - Jie Zhong; Wen Wen Sui; Ping Li; Qian Jun Tang; Tian Bo Liu; Yan Song Xiao (Archives of Virology, 2022)

Trace element signature of hydrothermal quartz: a potential tracer for ore genesis - Juan Dong; Li-Bin Jia; Mei-jia Song; Shu-Teng Xu; Mao-Wen Yuan; Cheng-Lu Li; Yuan-Jiang Yang (Arabian Journal of Geosciences, 2022)

Correction to: Increased Soluble Epoxide Hydrolase Activity Positively Correlates with Mortality in Heart Failure Patients with Preserved Ejection Fraction: Evidence from Metabolomics - Liyuan Peng; Ziping Song; Chengcheng Zhao; Kudusi Abuduwufuer; Yanwen Wang; Zheng Wen; Li Ni; Chenze Li; Ying Yu; Yi Zhu; Hualiang Jiang; Jinshan Shen; et al. (Phenomics, 2022)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Investigation of compound drought risk and driving factors in Nepal - Wen Song; Shisong Cao; Mingyi Du; You Mo; Suju Li (Natural Hazards, 2022)

Sorption behavior and mechanisms of thallium to microplastics - Min Liu; Xiaocheng Song; Qian Wang; Shilei Li; Siwang Kou; Zhenhui Gao; Wen Zhuang (Frontiers in Marine Science, 2022)
Thallium (Tl) is a metal of high toxicity, and the problem of Tl pollution is being faced globally. However, environmental data on Tl are still scarce and its biogeochemical behaviors remain mostly unclear. Studies have revealed the potential transport of other heavy metal by microplastics (MPs), but there is no report on the interactions between Tl and MPs yet. Therefore, we studied the adsorption of Tl by the three most commonly detected MPs, i.e., polyethylene (PE), polystyrene (PS), and polypropylene (PP) in fresh and seawater. We considered the effects of particle size, pH and competitive cations on adsorption capacity. The results showed PS has the highest adsorption capacity for Tl which was mainly through surface complexation. PS showed the lowest crystallinity and had the most oxygen-containing functional groups among the studied MPs. The adsorption of Tl on PE and PP was dominated by physical adsorption. The adsorptions exhibited significant salinity and pH dependence. Dominant cations in seawater competed with Tl ions for adsorption sites on MPs. With the increase in pH, the deprotonation of the carboxyl functional groups on MPs was enhanced, which increased the effective adsorption sites and promoted the adsorption of Tl. However, the adsorption capacity of the studied MPs for Tl was much lower than the corresponding capacity of natural minerals (clay, iron and manganese oxides) previously reported. Therefore, MPs may not be the main factors affecting the environmental behavior of Tl. This study provides valuable information for the study of thallium’s environmental behavior and ecological risk assessment.

Endosperm-specific accumulation of human α-lactalbumin increases seed lysine content in maize - Chenwanli Li; Wen Ma; Lifang Jin; Rentao Song; Weiwei Qi (Plant Cell Reports, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Ambient gaseous pollutant exposure and incidence of visual impairment among children and adolescents: findings from a longitudinal, two-center cohort study in China - Li Chen; Jing Wei; Tao Ma; Di Gao; Xijie Wang; Bo Wen; Manman Chen; Yanhui Li; Jun Jiang; Lijuan Wu; Weiming Li; Xiangtong Liu; et al. (Environmental Science and Pollution Research, 2022)

Transcriptome Analysis of Greenfin Horse-Faced Filefish (Thamnaconus septentrionalis) Gills in Response to Amyloodinium ocellatum (AO) Infection - Li-Guo Yang; Yue Wang; Wen-Bin Xu; Bo Qin; Na Ying; Xue-Feng Song; Yan-Feng Yue; Xiao-Shan Wang; Bian-Bian Zhang; Yan-Qing Wu (Fishes, 2022)
The greenfin horse-faced filefish (Thamnaconus septentrionalis) is susceptible to recurrent Amyloodinium ocellatum (AO) infestation over the grow-out production cycle. This parasite breeds mainly on the gills, causing hypoxia in the fish body, and leading to many deaths. The host-parasite response drives a complex immune reaction, which is poorly understood. To generate a model for host-parasite interaction and the pathogenesis of AO in greenfin horse-faced filefish, an RNA-seq approach, differential gene expression, GO, and KEGG analyses were employed. Overall, 624 new genes and 2076 differentially expressed genes (DEGs) were detected, including 942 upregulated and 1134 downregulated genes in the gills. Compared with the control group, the expression of leptin a, GTPase IMAP family member 4, and NLR family CARD domain-containing protein 3 was significantly higher in the AO-infected group. Conversely, cell wall integrity and stress response component 1-like, and hepcidin-like were significantly downregulated in the gills of AO-infected fish. GO and KEGG enrichment analysis indicated that DEGs were significantly enriched in signaling pathways associated with viral protein interaction with cytokine and cytokine receptor and cytokine–cytokine receptor interaction. Collectively, this transcriptomic study provides novel molecular insights into the pathology caused by AO infestation and alternative theories for future research implementing strategies to control and manage AO.

Correction to: Gene Selection in a Single Cell Gene Space Based on D–S Evidence Theory - Zhaowen Li; Qinli Zhang; Pei Wang; Fang Liu; Yan Song; Ching-Feng Wen (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Gene Selection in a Single Cell Gene Space Based on D–S Evidence Theory - Zhaowen Li; Qinli Zhang; Pei Wang; Fang Liu; Yan Song; Ching-Feng Wen (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Identification and expression of potential olfactory-related genes related to Niemann–Pick C2 protein and ionotropic receptors in Haemaphysalis longicornis - Yingying Cui; Jungang Wang; Qiyong Liu; Dongmei Li; Wen Zhang; Xiaobo Liu; Jun Wang; Xiuping Song; Feng Yao; Haixia Wu; Ning Zhao (Experimental and Applied Acarology, 2022)

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Transcriptome Changes Induced by Botrytis cinerea Stress and Weighted Gene Co-expression Network Analysis (WGCNA) in Actinidia chinensis - Zhe-Xin Li; Wen-Lin Zhang; Deng-Wei Jue; Xia Liu; Yu-Song Jiang; Jian-Min Tang (Plant Molecular Biology Reporter, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Cu-sulfide mineralogy, texture, and geochemistry in the Tiegelongnan porphyry-epithermal copper system, Tibet, China - Chao Yang; Georges Beaudoin; Ju-Xing Tang; Yang Song; Li-Qiang Wang; Xiao-Wen Huang (Mineralium Deposita, 2022)

Therapeutic Effects of Sodium Para-Aminosalicylic Acid on Cognitive Deficits and Activated ERK1/2-p90RSK/NF-κB Inflammatory Pathway in Pb-Exposed Rats - Li-li Lu; Yu-wen Zhang; Zhao-cong Li; Yuan-yuan Fang; Lei-lei Wang; Yue-song Zhao; Shao-jun Li; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2022)

Xylariaopyrones E–I, five new α-pyrone derivatives from the endophytic fungus Xylariales sp. (HM-1) - Wen-Wen Yang; Li-Wen Lu; Xue-Qing Zhang; Shang-Song Bao; Fei Cao; Zhi-Yong Guo; Zhang-Shuang Deng; Peter Proksch (Natural Product Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Complete Depletion of Primordial Germ Cells Results in Masculinization of Monopterus albus, a Protogynous Hermaphroditic Fish - Mingxi Hou; Ke Feng; Hongrui Luo; Yinjun Jiang; Wen Xu; Yongming Li; Yanlong Song; Ji Chen; Binbin Tao; Zuoyan Zhu; Wei Hu (Marine Biotechnology, 2022)

Global divergent trends of algal blooms detected by satellite during 1982–2018 - Chong Fang; Kaishan Song; Hans W Paerl; Pierre‐Andre Jacinthe; Zhidan Wen; Ge Liu; Hui Tao; Xiaofeng Xu; Tiit Kutser; Zongming Wang; Hongtao Duan; Kun Shi; et al. (Global Change Biology, 2022)
Algal blooms (ABs) in inland lakes have caused adverse ecological effects, and health impairment of animals and humans. We used archived Landsat images to examine ABs in lakes (>1 km 2 ) around the globe over a 37‐year time span (1982–2018). Out of the 176032 lakes with area >1 km 2 detected globally, 863 were impacted by ABs, 708 had sufficiently long records to define a trend, and 66% exhibited increasing trends in frequency ratio (FRQR, ratio of the number of ABs events observed in a year in a given lake to the number of available Landsat images for that lake) or area ratio (AR, ratio of annual maximum area covered by ABs observed in a lake to the surface area of that lake), while 34% showed a decreasing trend. Across North America, an intensification of ABs severity was observed for FRQR ( p p p p

Unexpected role of electron‐transfer hub in direct degradation of pollutants by exoelectrogenic bacteria - Ting‐Ting Zhu; Zhou‐Hua Cheng; Sheng‐Song Yu; Wen‐Wei Li; Dong‐Feng Liu; Han‐Qing Yu (Environmental Microbiology, 2022)
Summary Exoelectrogenic bacteria (EEB) are capable of anaerobic respiration with diverse extracellular electron acceptors including insoluble minerals, electrodes and flavins, but the detailed electron transfer pathways and reaction mechanisms remain elusive. Here, we discover that CymA, which is usually considered to solely serve as an inner‐membrane electron transfer hub in Shewanella oneidensis MR‐1 (a model EEB), might also function as a reductase for direct reducing diverse nitroaromatic compounds (e.g. 2,4‐dichloronitrobenzene) and azo dyes. Such a process can be accelerated by dosing anthraquinone‐2,6‐disulfonate. The CymA‐based reduction pathways in S . oneidensis MR‐1 for different contaminants could be functionally reconstructed and strengthened in Escherichia coli . The direct reduction of lowly polar contaminants by quinol oxidases like CymA homologues might be universal in diverse microbes. This work offers new insights into the pollutant reduction mechanisms of EEB and unveils a new function of CymA to act as a terminal reductase.

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

The associations of urinary DEHP metabolite levels, serum thyroid hormones, and thyroid-related genes among the adolescent students from China: a cross-sectional study - Yaming Zhao; Xinyue Song; Shuang Ding; Wen Qi; Yuezhu Zhang; Qi Xu; Tianyang Zhao; Xueting Zhang; Xu Li; Fuju Wu; Lin Ye (Environmental Science and Pollution Research, 2022)

Azithromycin-loaded linolenic acid-modified methoxy poly(ethylene glycol) micelles for bacterial infection treatment - Yi Wen; Zhimei Song; Hongmei Xu; Sijia Feng; Li Zhu; Fangfang Teng; Runliang Feng (Drug Delivery and Translational Research, 2022)

Automatic recognition of erosion area on the slope of tailings dam using region growing segmentation algorithm - Qihang Li; Jiabo Geng; Danqing Song; Wen Nie; Pooya Saffari; Jiangtong Liu (Arabian Journal of Geosciences, 2022)

Litter nitrogen concentration changes mediate effects of drought and plant species richness on litter decomposition - Jiang Wang; Yuan Ge; Johannes H. C. Cornelissen; Xiao-Yan Wang; Song Gao; Yi Bai; Tong Chen; Zhong-Wang Jing; Chong-Bang Zhang; Wen-Li Liu; Jun-Min Li; Fei-Hai Yu (Oecologia, 2022)

Assessing the fractionation and bioavailability of heavy metals in soil–rice system and the associated health risk - Yuanyuan Wang; Weiwei Xu; Jizhou Li; Yinxian Song; Ming Hua; Wenbo Li; Yubo Wen; Tianyuan Li; Xinxing He (Environmental Geochemistry and Health, 2022)

East Asian summer monsoon changes in subtropical China since late Pleistocene: Evidence from the Ailuropoda-Stegodon fauna - Zhi-wen Li; Li Sun; Bao-sheng Li; Feng-nian Wang; Ding-ding Du; You-gui Song; Hui-Juan Zhang; Liu-qin Chen; Dan Xu (Journal of Mountain Science, 2022)

High frequency of extreme precipitation increases Stipa grandis biomass by altering plant and microbial nitrogen acquisition - Shuhai Wen; Yuqiang Tian; Shengnan Ouyang; Minghua Song; Xiaobing Li; Yong Zhang; Si Gao; Xingliang Xu; Yakov Kuzyakov (Biology and Fertility of Soils, 2022)

Genome-wide identification and expression analysis of glycosyltransferase gene family 1 in Quercus robur L. - Jie Zhang; Li-Mei Lin; Wen-Wen Cheng; Xin Song; Yue-Hong Long; Zhao-Bin Xing (Journal of Applied Genetics, 2021)

Explanation of heavy metal pollution in coal mines of china from the perspective of coal gangue geochemical characteristics - Huadong Gao; Yanli Huang; Wei Li; Junmeng Li; Shenyang Ouyang; Tianqi Song; Fengyuan Lv; Wen Zhai; Kun Ma (Environmental Science and Pollution Research, 2021)

Interdecadal change in the relationship between boreal winter North Pacific Oscillation and Eastern Australian rainfall in the following autumn - Linye Song; Shangfeng Chen; Wen Chen; Wansuo Duan; Yun Li (Climate Dynamics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Hybrid Scheduling for Multi-Equipment at U-Shape Trafficked Automated Terminal Based on Chaos Particle Swarm Optimization - Junjun Li; Jingyu Yang; Bowei Xu; Yongsheng Yang; Furong Wen; Haitao Song (Journal of Marine Science and Engineering, 2021)
Aimed to improve the efficiency of port operations, Shanghai Zhenhua Heavy Industries Co., Ltd. (ZPMC) proposed a new U-shape trafficked automated terminal. The new U-shape trafficked automated terminal brings a new hybrid scheduling problem. A hybrid scheduling model for yard crane (YC), AGV and ET in the U-shape trafficked automated terminal yard is established to solve the problem. The AGV and ET yard lanes are assumed to be one-way lane. Take the YC, AGV and ET scheduling results (the container transportation sequences) as variables and the minimization of the maximum completion time as the objective function. A scheduling model architecture with hierarchical abstraction of scheduling objects is proposed to refine the problem. The total completion time is solved based on a static and dynamic mixed scheduling strategy. A chaotic particle swarm optimization algorithm with speed control (CCPSO) is proposed, which include a chaotic particle strategy, a particle iterative speed control strategy, and a particle mapping space for hybrid scheduling. The presented model and algorithm were applied to experiments with different numbers of containers and AGVs. The parameters of simulation part refer to Qinzhou Port. The simulation results show that CCPSO can obtain a near-optimal solution in a shorter time and find a better solution when the solution time is sufficient, comparing with the traditional particle swarm optimization algorithm, the adaptive particle swarm optimization algorithm and the random position particle swarm optimization algorithm.

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Marine alkaloids as the chemical marker for the prey–predator relationship of the sponge Xestospongia sp. and the nudibranch Jorunna funebris - Qihao Wu; Song-Wei Li; Nicole J. de Voogd; Hong Wang; Li-Gong Yao; Yue-Wei Guo; Xu-Wen Li (Marine Life Science & Technology, 2021)
The dietary relationship study between marine sponge Xestospongia sp. and its nudibranch predators Jorunna funebris based on the discovery of isoquinolinequinones has long been studied. In this study, chemical investigation of the sponge Xestospongia sp. and nudibranch J. funebris from the South China Sea yielded a new marine alkaloid neopetroside C ( 1 ), together with nine known alkaloids ( 2 – 10 ). The chemical structures of all the compounds were elucidated by extensive spectroscopic analysis. Neopetroside C ( 1 ) featured a riboside of nicotinic acid with a rare α - N glycosildic linkage and an acyl residue of ( Z )-2-methylbut-2-enoic acid attached to C-5′. The plausible chemical ecology relationship between sponge Xestospongia sp. and its nudibranch predator J. funebris was proposed based on the biogenetic relationship of the common marine alkaloids. The observation of two structural fragments, ( Z )-2-methylbut-2-enoyloxy and trigonelline groups in both sponge and nudibranch, indicated that nudibranch might uptake chemicals from sponge and then modify and transform them into chemical weapons to defend against predators.

Bis(ethylmaltolato)oxidovanadium (IV) alleviates neuronal apoptosis through regulating peroxisome proliferator-activated receptor γ in a triple transgenic animal model of Alzheimer’s disease - Zhijun He; Jianxi Song; Xuexia Li; Xiaoqian Li; Huazhang Zhu; Chong Wu; Wen Xiao; Xiubo Du; Jiazuan Ni; Nan Li; Qiong Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Gonadal lipidomics profile of an ovoviviparity teleost, black rockfish, during gonadal development - Jianshuang Li; Min Song; Haishen Wen; Ying Zhang; Yun Li; Likang Lyu; Xiaojie Wang; Xin Qi (Fish Physiology and Biochemistry, 2021)

Homeobox Gene Six3 is Required for the Differentiation of D2-Type Medium Spiny Neurons - Xiaolei Song; Haotian Chen; Zicong Shang; Heng Du; Zhenmeiyu Li; Yan Wen; Guoping Liu; Dashi Qi; Yan You; Zhengang Yang; Zhuangzhi Zhang; Zhejun Xu (Neuroscience Bulletin, 2021)
Medium spiny neurons (MSNs) in the striatum, which can be divided into D1 and D2 MSNs, originate from the lateral ganglionic eminence (LGE). Previously, we reported that Six3 is a downstream target of Sp8/Sp9 in the transcriptional regulatory cascade of D2 MSN development and that conditionally knocking out Six3 leads to a severe loss of D2 MSNs. Here, we showed that Six3 mainly functions in D2 MSN precursor cells and gradually loses its function as D2 MSNs mature. Conditional deletion of Six3 had little effect on cell proliferation but blocked the differentiation of D2 MSN precursor cells. In addition, conditional overexpression of Six3 promoted the differentiation of precursor cells in the LGE. We measured an increase of apoptosis in the postnatal striatum of conditional Six3 -knockout mice. This suggests that, in the absence of Six3, abnormally differentiated D2 MSNs are eliminated by programmed cell death. These results further identify Six3 as an important regulatory element during D2 MSN differentiation.

Effects of continuous cucumber cropping on crop quality and soil fungal community - Kaining Sun; Longyun Fu; Yang Song; Liang Yuan; Haoran Zhang; Dan Wen; Ning Yang; Xiao Wang; Yaoquan Yue; Xuhua Li; Kean Wang (Environmental Monitoring and Assessment, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Ring distribution patterns—diversification or speciation? Comparative phylogeography of two small mammals in the mountains surrounding the Sichuan Basin - Yanqun Wang; Anderson Feijó; Jilong Cheng; Lin Xia; Zhixin Wen; Deyan Ge; Jian Sun; Liang Lu; Song Li; Qisen Yang (Molecular Ecology, 2021)
Studying the genetic differentiation in a unique geographical area contributes to understanding the process of speciation. Here, we explore the spatial genetic structure and underlying formation mechanism of two congeneric small mammal species ( Apodemus draco and A. chevrieri ), which are mainly distributed in the mountains surrounding the lowland Sichuan Basin, southwest China. We applied a set of comparative phylogeographical analyses to determine their genetic diversification patterns, combining mitochondrial ( Cytb and COI ) and nuclear (microsatellite loci) markers, with dense sampling throughout the range (411 A . draco from 21 sites and 191 A . chevrieri from 22 sites). Moreover, we performed three complementary statistical methods to investigate the correlation between genotype and geographical and environmental components, and predicted the potential suitable distributional range under the present and historical climate conditions. Our results suggest that both species have experienced allopatric differentiation and admixture in historical periods, resulting in a ring‐shape diversification, under the barrier effect of the Sichuan Basin. We infer that the tectonic events of the Qinghai–Tibetan Plateau and climatic oscillations during the Quaternary played an important role on the genetic divergence of the two species by providing environmental heterogeneity and geographical variation. Our study reveals a case of two sympatric small mammals following a ring‐shaped diversification pattern and provides insight into the process of differentiation.

Design, synthesis and evaluation of dihydrotriazine derivatives-bearing 5-aryloxypyrazole moieties as antibacterial agents - Tian-Yi Zhang; Chun-Shi Li; Ming-Yue Cui; Xue-Qian Bai; Jiang-Hui Chen; Ze-Wen Song; Bo Feng; Xue-Kun Liu (Molecular Diversity, 2021)

Fine mapping QTL and mining genes for protein content in soybean by the combination of linkage and association analysis - Xiyu Li; Ping Wang; Kaixin Zhang; Shulin Liu; Zhongying Qi; Yanlong Fang; Yue Wang; Xiaocui Tian; Jie Song; Jiajing Wang; Chang Yang; Xu Sun; et al. (Theoretical and Applied Genetics, 2021)

Prophylactic Melatonin Treatment Ameliorated Propofol-Induced Cognitive Dysfunction in Aged Rats - Junhua Li; Guiyun Wu; Wen Song; Yafang Liu; Zhixiao Han; Zhiwen Shen; Yujuan Li (Neurotoxicity Research, 2021)

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

Genome-wide linkage mapping for canopy activity related traits using three RIL populations in bread wheat - Faji Li; Weie Wen; Jindong Liu; Shengnan Zhai; Xinyou Cao; Cheng Liu; Dungong Cheng; Jun Guo; Yan Zi; Ran Han; Xiaolu Wang; Aifeng Liu; et al. (Euphytica, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Snapshot of the Pliocene environment of West Kunlun region, Northwest China - Jia Liu; Teng-Xiang Wang; Xin-Wen Zhang; Ai Song; Shu-Feng Li; Jian Huang; Teresa Spicer; Robert A. Spicer; Fei-Xiang Wu; Tao Su; Zhe-Kun Zhou (Palaeobiodiversity and Palaeoenvironments, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Long-term remote sensing of total suspended matter using Landsat series sensors in Hulun Lake, China - Qiang Wang; Kaishan Song; Zhidan Wen; Yingxin Shang; Sijia Li; Chong Fang; Jia Du; Fangrui Zhao; Ge Liu (International Journal of Remote Sensing, 2021)

Bacillus amyloliquefaciens application to prevent biofilms in reclaimed water microirrigation systems* - Jiaxin Wen; Yang Xiao; Peng Song; Bo Sun; Tahir Muhammad; Lianghe Ma; An Waier Aosiman; Yunkai Li (Irrigation and Drainage, 2021)
Reclaimed water (RW) applied in drip irrigation systems could be a solution to cope with the challenges of limited freshwater resources. Biofilm growth in irrigation systems is an unavoidable issue when using RW. To date, strong chemical bactericides mostly dominate the commercial market in controlling biofilms. However, recently scientists have been concerned about their real efficacy and environmental risks. This study assesses a low‐concentration microbial antagonist (i.e., Bacillus amyloliquefaciens inoculums, BAI) intermittently injected into the systems to mitigate biofilm formation in three types of drip emitters using two kinds of treated RW. The results indicated that the application of BAI significantly ( p

Spatial–temporal differences in disaster perception and response among new media users and the influence factors: a case study of the Shouguang Flood in Shandong province - Shuolin Geng; Qi Zhou; Mingjie Li; Dianxing Song; Yanjun Wen (Natural Hazards, 2021)

Correction to: The effect of teprenone on the intestinal morphology and microbial community of Chinese sea bass (Lateolabrax maculatus) under intermittent hypoxic stress - Hong-biao Dong; Yong-xu Sun; Ya-fei Duan; Hua Li; Yong Li; Qing-song Liu; Wen-hao Wang; Jia-song Zhang (Fish Physiology and Biochemistry, 2020)

An allotriploid hybrid developed from a female 2n gamete was obtained from Eriobotrya japonica (Thunb.) Lindl × E. deflexa (Hemsl.) Nakai - Yanjuan Song; Jiangbo Dang; Weiwei Chen; Guo Wen; Qiao He; Xiaolin Li; Shoukai Lin; Guolu Liang; Qigao Guo (Euphytica, 2020)

LncRNA A2M-AS1 lessens the injury of cardiomyocytes caused by hypoxia and reoxygenation via regulating IL1R2 - Xue-Lian Song; Fei-Fei Zhang; Wen-Jing Wang; Xin-Ning Li; Yi Dang; Ying-Xiao Li; Qian Yang; Mei-Jing Shi; Xiao-Yong Qi (Genes & Genomics, 2020)

Zircon U-Pb-Hf isotopes and geochemistry of Jurassic igneous rocks from the southern Zhangguangcai Range, NE China: constraints on magmatism, petrogenesis and tectonic implications - Zuo-Zhen Han; Xiang Ren; Hans-Peter Schertl; Xu-Ping Li; Zhi-Gang Song; Qing-Xiang Du; Chao Han; Wen-Jian Zhong; Li-Hua Gao (International Geology Review, 2020)

Early nodulin 93 protein gene: essential for induction of somatic embryogenesis in oil palm - Pek-Lan Chan; Ray J. Rose; Abdul Munir Abdul Murad; Zamri Zainal; Pei-Wen Ong; Leslie Cheng-Li Ooi; Eng-Ti Leslie Low; Zamzuri Ishak; Suzaini Yahya; Youhong Song; Rajinder Singh (Plant Cell Reports, 2020)

Synthesis and molecular docking studies of novel pyrimidine derivatives as potential antibacterial agents - Xue-Qian Bai; Chun-Shi Li; Ming-Yue Cui; Ze-Wen Song; Xing-Yu Zhou; Chao Zhang; Yang Zhao; Tian-Yi Zhang; Tie-Yan Jiang (Molecular Diversity, 2020)

Optimization for allitol production from d-glucose by using immobilized glucose isomerase and recombinant E. coli expressing d-psicose-3-epimerase, ribitol dehydrogenase and formate dehydrogenase - Xin Wen; Huibin Lin; Yilin Ren; Can Li; Chengjia Zhang; Xin Song; Jianqun Lin; Jianqiang Lin (Biotechnology Letters, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

The effect of teprenone on the intestinal morphology and microbial community of Chinese sea bass (Lateolabrax maculatus) under intermittent hypoxic stress - Hong-biao Dong; Yong-xu Sun; Ya-fei Duan; Hua Li; Yong Li; Qing-song Liu; Wen-hao Wang; Jia-song Zhang (Fish Physiology and Biochemistry, 2020)

Correction to: Organic Matter Pollution During the Spring Thaw in Hulun Lake Basin: Contribution of Multiform Human Activities - Wenlin Wang; Wenjing Li; Yan Yan; Bo Liu; Tanjing Wang; Sichen Mao; Ninghui Song; Huashan Dou; Wen Ao; Changxin Zou (Bulletin of Environmental Contamination and Toxicology, 2020)

Organic Matter Pollution During the Spring Thaw in Hulun Lake Basin: Contribution of Multiform Human Activities - Wenlin Wang; Wenjing Li; Yan Yan; Bo Liu; Tanjing Wang; Sichen Mao; Linhui Song; Huashan Dou; Wen Ao; Changxin Zou (Bulletin of Environmental Contamination and Toxicology, 2020)

A new bis-γ-pyrone polypropionate of onchidiol family from marine pulmonate mollusk Onchidium sp - Song-Wei Li; Wan-Xiang Cui; Xia-Juan Huan; Margherita Gavagnin; Ernesto Mollo; Ze-Hong Miao; Li-Gong Yao; Xu-Wen Li; Yue-Wei Guo (Natural Product Research, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

New insight into the molecular phylogeny of the genus Liparis s.l. (Orchidaceae: Malaxideae) with a new generic segregate: Blepharoglossum - Lin Li; Shih-Wen Chung; Bo Li; Song-Jun Zeng; Hai-Fei Yan; Shi-Jin Li (Plant Systematics and Evolution, 2020)
Molecular studies have shown that Liparis s.l. is polyphyletic, with the epiphytic Liparis alliance well separated from the clade representing Liparis in its restricted sense and further forming a phylogenetically heterogeneous assemblage. The generic status of Cestichis , as the key member of the epiphytic Liparis alliance, remains contentious, and the relationships between Cestichis , Stichorkis and Platystyliparis are still unclear and in need of further studies. We herein employ DNA sequence data from nuclear ITS and plastid mat K regions to clarify the generic boundaries of Cestichis and its relationship to the allied genera. Results from both Bayesian inference and maximum likelihood analysis congruently indicate that Cestichis as currently circumscribed is not monophyletic. The Blepharoglossum clade, corresponding to commonly recognized sect. Blepharoglossum , forms a monophyletic lineage closely related to the genus Oberonia instead of the core Cestichis clade. A re-evaluation of the diagnostic morphological characters reveals that this lineage represents a morphologically distinct group. Based on these results, Blepharoglossum is removed from Cestichis and elevated to generic status. Our study also sheds light on the homoplastic nature of some diagnostic morphological characters used traditionally in the taxonomy of the Malaxidinae.

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Morphological and Anatomical Differences among Three Seagrass Species in a High-energy Coastal Area Typically Dominated by Surfgrass in a Rocky Coastal Area of Shandong Peninsula, China - Wen-Tao Li; Jia Song; Chongfeng Zhong; Xin Hou; Ran Cheng; Pei-dong Zhang (Ocean Science Journal, 2020)

Effect of nutritional factors on the accretion of secondary metabolites in Malaysian ginseng adventitious root cultures - Xi-Hua Cui; Hosakatte Niranjana Murthy; Ji-De Zhang; Hang-Lin Song; Yin-Ji Jiang; Wen-Wen Qi; Yong Yi Li; Kee-Yoeup Paek; So-Young Park (Plant Biotechnology Reports, 2020)

Evaluating the effects of transgenic Bt rice cultivation on soil stability - Ying-ying Song; Jia-wen Liu; Li-kun Li; Man-qiang Liu; Xiao-yun Chen; Fa-jun Chen (Environmental Science and Pollution Research, 2020)

Three new dibenzofurans from Cydonia oblonga Mill - Jiao-Jiao Wei; Wen-Qiong Wang; Wei-Bin Song; Li-Jiang Xuan (Natural Product Research, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Common Variant in TREM1 Influencing Brain Amyloid Deposition in Mild Cognitive Impairment and Alzheimer’s Disease - Yue-Song Liu; Wen-Jing Yan; Chen-Chen Tan; Jie-Qiong Li; Wei Xu; Xi-Peng Cao; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

A recombinant infectious bronchitis virus from a chicken with a spike gene closely related to that of a turkey coronavirus - Yan Wang; Xuejiao Cui; Xu Chen; Shixing Yang; Yu Ling; Qianben Song; Su Zhu; Luying Sun; Chuang Li; Yu Li; Xutao Deng; Eric Delwart; et al. (Archives of Virology, 2020)

Neogenkwanine I from the flower buds of Daphne genkwa with its stereostructure confirmation using quantum calculation profiles and antitumor evaluation - Xue-Wen Hou; Shuang Han; Ying-Ying Zhang; Hai-Bi Su; Pin-Yi Gao; Ling-Zhi Li; Shao-Jiang Song (Natural Product Research, 2020)

Lonicerae japonicae flos and Lonicerae flos: a systematic review of ethnopharmacology, phytochemistry and pharmacology - Yuke Li; Wen Li; Chaomei Fu; Ying Song; Qiang Fu (Phytochemistry Reviews, 2020)

Relative roles of formation and preservation on gold endowment along the Sanshandao gold belt in the Jiaodong gold province, China: importance for province- to district-scale gold exploration - Liang Zhang; David I. Groves; Li-Qiang Yang; Gong-Wen Wang; Xiang-Dong Liu; Da-Peng Li; Ying-Xin Song; Wei Shan; Si-Chen Sun; Zhao-Kun Wang (Mineralium Deposita, 2020)

The DI–DII linker of human parainfluenza virus type 3 fusion protein is critical for the virus - Ying Liu; Miaomiao Chi; Hongling Wen; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2020)

Preparation and Characterization of TiO2 Nanotube Arrays with Short Tube Length and Its Photocatalytic Degradation of Organic Pollutants - Jiao Li; Wen-hao Shen; Shu-fang Song; Xiao-quan Chen; Jean-Pierre Corriou (Water, Air, & Soil Pollution, 2020)

Molecular detection and identification of Brassica juncea phyllody and witches’ broom-associated phytoplasmas of group 16SrVI-A in Inner Mongolia, China - Lei Zhang; Pei-Ling Song; Ping-Ping Sun; Wen-Jun Zhao; Zi-Qin Li; Zheng-Nan Li (European Journal of Plant Pathology, 2020)

Genomic characterization of a novel astrovirus identified in Amur tigers from a zoo in China - Hui-Hui Zhang; Qi-Guan Qiu; Shu-Jing Liu; Wen-Qin Hu; Jie-Yu Li; Tian-Ning Liu; You-Song Peng; Xing-Yi Ge; Chao-Ting Xiao (Archives of Virology, 2019)

Dynamic effect of the South Asian high on the interannual zonal extension of the western North Pacific subtropical high - Wei Wei; Renhe Zhang; Min Wen; Song Yang; Wenhong Li (International Journal of Climatology, 2019)
The South Asian high (SAH) and the North Pacific subtropical high (NPSH) are two crucial systems affecting the summer rainfall over East Asia. Features of the relative vorticity of the SAH and its dynamic effect on zonal extension of the western NPSH (WNPSH) are investigated on interannual timescales using data diagnosis and numerical model experiments. Results show that two climatological centres of negative relative vorticity are observed along the northern flank of the SAH over the Tibetan Plateau and northern West Asia at 200 hPa during boreal summer. The relatively more intense centre over the Tibetan Plateau (TPV) shows a pronounced southeast‐northwest (SE‐NW) variation, indicating a SE‐NW shift of the SAH. When the SAH shifts southeastward, an anomalous anticyclone occurs over eastern China at 200 hPa. In the middle troposphere, this anomalous anticyclone is located over southern China and the northern South China Sea, leading to a westward extension of the WNPSH. A diagnostic analysis of the vorticity equation indicates that the negative relative vorticity anomalies at 500 hPa are mainly caused by the downward advection of the mean relative vorticity by anomalous sinking motions. When the SAH extends southeastward, intense convergence on the southeastern flank of the anomalous upper‐level anticyclone induces descending motions that cause downward advection of mean negative vorticity. Consequently, negative vorticity anomaly is formed at 500 hPa, leading to a westward extension of the WNPSH. Results from the experiments using an idealized anomalous atmospheric general circulation model further demonstrate that the upper‐level anomalous anticyclone associated with a southeastward extension of the SAH triggers an anomalous anticyclone at the middle level, causing a westward extension of the WNPSH.

Isoflurane produces antidepressant effects inducing BDNF-TrkB signaling in CUMS mice - Sha-Sha Zhang; Yu-Hua Tian; Song-Jun Jin; Wen-Cheng Wang; Jing-Xin Zhao; Xiao-Ming Si; Li Zhang; Hong Xu; Jing-Yu Jin (Psychopharmacology, 2019)

Impact of ozonation and biologically enhanced activated carbon filtration on the composition of micropollutants in drinking water - Wei-Guang Li; Wen Qin; Yang Song; Ze-Jia Zheng; Long-Yi Lv (Environmental Science and Pollution Research, 2019)

High genetic diversity and recombination events of porcine astrovirus strains identified from ill and asymptomatic pigs in 2017, Hunan Province, China - Sun-Liang Lv; Hui-Hui Zhang; Jie-Yu Li; Wen-Qin Hu; Ya-Ting Song; Tanja Opriessnig; Chao-Ting Xiao (Virus Genes, 2019)

Detection and attribution of upper-tropospheric warming over the tropical western Pacific - Yana Li; Song Yang; Yi Deng; Xiaoming Hu; Ming Cai; Wen Zhou (Climate Dynamics, 2019)

Early Cretaceous gold mineralization in the Lesser Xing’an Range of NE China: the Yongxin example - Zhong-Hai Zhao; Jing-Gui Sun; Guang-Hui Li; Wen-Xi Xu; Chang-Lu Lü; Song Wu; Yan Guo; Jin Liu; Liang Ren (International Geology Review, 2019)

Damage Analysis of High-Temperature Rocks Subjected to LN2 Thermal Shock - Xiaoguang Wu; Zhongwei Huang; Shikun Zhang; Zhen Cheng; Ran Li; Hengyu Song; Haitao Wen; Pengpeng Huang (Rock Mechanics and Rock Engineering, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Variations of Physical and Mechanical Properties of Heated Granite After Rapid Cooling with Liquid Nitrogen - Xiaoguang Wu; Zhongwei Huang; Hengyu Song; Shikun Zhang; Zhen Cheng; Ran Li; Haitao Wen; Pengpeng Huang; Xianwei Dai (Rock Mechanics and Rock Engineering, 2019)

Preparation of AgCl/TNTs nanocomposites for organic dyes and inorganic heavy metal removal - Cheng-Yen Tsai; Chen-Wuing Liu; Hsing-Cheng Hsi; Kuen-Song Lin; Yi-Wen Lin; Li-Chi Lai; Tsung-Nan Weng (Environmental Science and Pollution Research, 2019)

Development and chemical characterization of Casparian strips in the roots of Chinese fir (Cunninghamia lanceolata) - Chengwei Song; Weiwei Shen; Liang Du; Jialong Wen; Jinxing Lin; Ruili Li (Trees, 2019)

The number of cultivars in varietal winter-wheat mixtures influence aboveground biomass and grain yield in North China - Xiaoliang Qin; Yüze Li; Chengxiao Shi; Duanpu Song; Xiaoxia Wen; Yuncheng Liao; Kadambot H. M. Siddique (Plant and Soil, 2019)

Agricultural Development and Implication for Wetlands Sustainability: A Case from Baoqing County, Northeast China - Chong Fang; Zhidan Wen; Lin Li; Jia Du; Ge Liu; Xiaodi Wang; Kaishan Song (Chinese Geographical Science, 2019)

Arrangement of High-standard Basic Farmland Construction Based on Village-region Cultivated Land Quality Uniformity - Wen Song; Kening Wu; Huafu Zhao; Rui Zhao; Ting Li (Chinese Geographical Science, 2019)

Are glutamate transporters neuroprotective or neurodegenerative during cerebral ischemia? - Li-Nan Zhang; Liang Hao; Yu-Song Guo; Hai-Yan Wang; Lin-lin Li; Li-Zhe Liu; Wen-Bin Li (Journal of Molecular Medicine, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

Magnetic mineral diagenesis in sediments of saline lake Lop Nur - Wen Li; Gui-jin Mu; Yong-chong Lin; Hao-ze Song (Journal of Mountain Science, 2019)

The fecal virome of red-crowned cranes - Yan Wang; Shixing Yang; Dawei Liu; Chenglin Zhou; Wang Li; Yuan Lin; Xiaochun Wang; Quan Shen; Hua Wang; Chuang Li; Minghui Zong; Yuzhu Ding; et al. (Archives of Virology, 2019)

Devonian integrative stratigraphy and timescale of China - Wenkun Qie; Xueping Ma; Honghe Xu; Li Qiao; Kun Liang; Wen Guo; Junjun Song; Bo Chen; Jianfeng Lu (Science China Earth Sciences, 2019)

Plastic-film mulch and fertilization rate affect the fate of urea-15N in maize production - Qiu-Jin Ma; Xiao Gang Li; Wen-Yuan Song; Bin Jia; Qian Zhang; Limei Lin; Feng-Min Li (Nutrient Cycling in Agroecosystems, 2018)

Cell culture medium supplemented with taurine decreases basic charge variant levels of a monoclonal antibody - Mengjuan Liu; Jiaqi Wang; Hongping Tang; Li Fan; Liang Zhao; Hai-Bin Wang; Yan Zhou; Wen-Song Tan (Biotechnology Letters, 2018)

Serum Oxidative Stress Marker Levels in Unmedicated and Medicated Patients with Schizophrenia - Zhi-Le Bai; Xue-Song Li; Guang-Yang Chen; Yang Du; Ze-Xu Wei; Xi Chen; Guang-En Zheng; Wen Deng; Yong Cheng (Journal of Molecular Neuroscience, 2018)

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

Characterization of a novel 4.0-kb y-type HMW-GS from Eremopyrum distans - S.F. Dai; D.Y. Xu; Z.J. Wen; Z.P. Song; H.X. Chen; H.Y Li; J.R. Li; L.Z. Kang; Z.H. Yan (Cereal Research Communications, 2018)

Learning-Based Cell Injection Control for Precise Drop-on-Demand Cell Printing - Jia Shi; Bin Wu; Bin Song; Jinchun Song; Shihao Li; Dieter Trau; Wen F. Lu (Annals of Biomedical Engineering, 2018)

Ultra-low carbon dioxide partial pressure improves the galactosylation of a monoclonal antibody produced in Chinese hamster ovary cells in a bioreactor - Chen Wang; Jiaqi Wang; Min Chen; Li Fan; Liang Zhao; Wen-Song Tan (Biotechnology Letters, 2018)

MPEG-PCL Copolymeric Micelles for Encapsulation of Azithromycin - Wenxiu Wei; Shida Li; Hongmei Xu; Feilong Zhou; Yi Wen; Zhimei Song; Sijia Feng; Runliang Feng (AAPS PharmSciTech, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Functional analysis of amino acids at stalk/head interface of human parainfluenza virus type 3 hemagglutinin-neuraminidase protein in the membrane fusion process - Jingjing Jiang; Hongling Wen; Miaomiao Chi; Ying Liu; Jingxue Liu; Zhankui Cao; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2018)

Application of the sodium hyaluronate-CNTF scaffolds in repairing adult rat spinal cord injury and facilitating neural network formation - Yabin Xie; Wei Song; Wen Zhao; Yudan Gao; Junkui Shang; Peng Hao; Zhaoyang Yang; Hongmei Duan; Xiaoguang Li (Science China Life Sciences, 2018)

Analysis and Risk Assessment of Seven Toxic Element Residues in Raw Bovine Milk in China - Xue-Yin Qu; Nan Zheng; Xue-Wei Zhou; Song-Li Li; Jia-Qi Wang; Wen-Ju Zhang (Biological Trace Element Research, 2018)

Identification of QTLs associated with heat tolerance at the heading and flowering stage in rice (Oryza sativa L.) - Mao-mao Li; Xia Li; Li-qin Yu; Jin-wen Wu; Hui Li; Jin Liu; Xiao-ding Ma; Su-min Jo; Dong-Soo Park; Youchun Song; Dongjin Shin; Long-zhi Han (Euphytica, 2018)

Degradation behavior of triclosan by co-exposure to chlorine dioxide and UV irradiation: influencing factors and toxicity changes - Qing-song Li; Hui-wen Cai; Guo-xin Li; Guo-yuan Chen; Xiao-yan Ma; Wen-long He (Environmental Science and Pollution Research, 2018)

Construction of collaborative mapping engine for dynamic disaster and emergency response - Guoqiang Peng; Yongning Wen; Yuting Li; Songshan Yue; Zhiyao Song (Natural Hazards, 2018)

Intramuscular Delivery of scAAV9-hIGF1 Prolongs Survival in the hSOD1G93A ALS Mouse Model via Upregulation of D-Amino Acid Oxidase - HuiQian Lin; HaoJie Hu; WeiSong Duan; YaLing Liu; GuoJun Tan; ZhongYao Li; YaKun Liu; BinBin Deng; XueQin Song; Wan Wang; Di Wen; Ying Wang; et al. (Molecular Neurobiology, 2018)

Relationship Between Perisylvian Essential Language Sites and Arcuate Fasciculus in the Left Hemisphere of Healthy Adults - Yu Lin; Kai Zhang; Shuai Li; Song Li; Jingna Jin; Fang Jin; Wen Qin; Long Hai; Meng Zhu; Chunshui Yu; Zhipeng Liu; Tao Yin; et al. (Neuroscience Bulletin, 2017)

mPGES-1-derived prostaglandin E2 stimulates Stat3 to promote podocyte apoptosis - Jing Yu; Yimei Wu; Lu Wang; Wen Zhang; Man Xu; Jiayu Song; Yu Fu; Yiyun Cui; Wei Gong; Shuzhen Li; Weiwei Xia; Songming Huang; et al. (Apoptosis, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Investigating spatial variability of vertical water fluxes through the streambed in distinctive stream morphologies using temperature and head data - Liping Wang; Weiwei Jiang; Jinxi Song; Xinyi Dou; Hongtao Guo; Shaofeng Xu; Guotao Zhang; Ming Wen; Yongqing Long; Qi Li (Hydrogeology Journal, 2017)

Seasonal-related effects on ammonium removal in activated carbon filter biologically enhanced by heterotrophic nitrifying bacteria for drinking water treatment - Wen Qin; Wei-Guang Li; Xu-jin Gong; Xiao-Fei Huang; Wen-biao Fan; Duoying Zhang; Peng Yao; Xiao-ju Wang; Yang Song (Environmental Science and Pollution Research, 2017)

Cortical thickness development of human primary visual cortex related to the age of blindness onset - Qiaojun Li; Ming Song; Jiayuan Xu; Wen Qin; Chunshui Yu; Tianzi Jiang (Brain Imaging and Behavior, 2017)

A new dimeric stilbene from the lianas of Gnetum parvifolium - Li-Wen Tian; Jun-Jiang Lv; Yao Liu; Lu-Yao Song; Lian-Bing Hou; Cheng Zhong; Yang Xie (Natural Product Research, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Rapid quantification of multi-components in alcohol precipitation liquid of Codonopsis Radix using near infrared spectroscopy (NIRS) - Yu Luo; Wen-long Li; Wen-hua Huang; Xue-hua Liu; Yan-gang Song; Hai-bin Qu (Journal of Zhejiang University-SCIENCE B, 2017)

The septin protein S ep4 facilitates host infection by plant fungal pathogens via mediating initiation of infection structure formation - Hui‐Qiang Feng; Gui‐Hua Li; Shun‐Wen Du; Song Yang; Xue‐Qian Li; Paul de Figueiredo; Qing‐Ming Qin (Environmental Microbiology, 2017)
Summary Many phytopathogenic fungi use infection structures (IFSs, i.e., appressoria and infection cushions) to penetrate host cuticles. However, the conserved mechanisms that mediate initiation of IFS formation in divergent pathogens upon sensing the presence of host plants remain obscure. Here, we demonstrate that a conserved septin gene SEP4 plays crucial roles in this process. Disruption of SEP4 in the plant grey mould fungus Botrytis cinerea completely blocked IFS formation and abolished the virulence of Δ Bcsep4 mutants on unwounded hosts. During IFS formation, mutants lacking SEP4 could produce reactive oxygen species (ROS) normally. Inhibition of ROS production in strains harbouring the SEP4 gene resulted in disordered assembly of Sep4 and the subsequent failure to form infection cushions, suggesting that proper Sep4 assembly regulated by ROS is required for initiation of IFS formation and infection. Moreover, loss of SEP4 severely impaired mutant conidiation, melanin and chitin accumulation in hyphal tips and lesion expansion on wounded hosts, but significantly promoted germ tube elongation and sclerotium production. SEP4 ‐mediated fungal pathogenic development, including IFS formation, was validated in the hemibiotroph Magnaporthe oryzae . Our findings indicate that Sep4 plays pleiotropic roles in B. cinerea development and specifically facilities host infection by mediating initiation of IFS formation in divergent plant fungal pathogens in response to ROS signaling.

A new tetrahydrobenzofuranone metabolite from Streptomyces sp. HS-NF-853 - Kai Yan; Jin-Meng Li; Ren-Xin Xiang; Jian-Song Li; Hui Zhang; Huan Qi; Chong-Xi Liu; Ji-Dong Wang; Wen-Sheng Xiang (Natural Product Research, 2017)

New milbemycin metabolites from the genetically engineered strain Streptomyces bingchenggensis BCJ60 - Jian-Song Li; Min-Na Du; Hui Zhang; Ji Zhang; Shao-Yong Zhang; Hai-Yan Wang; An-Liang Chen; Ji-Dong Wang; Wen-Sheng Xiang (Natural Product Research, 2017)

The fourth central polypurine tract guides the synthesis of prototype foamy virus plus-strand DNA - Dongxue Chen; Jing Song; Yan Sun; Zhi Li; Didi Wen; Qingmei Liu; Wanhong Liu; Xiaohua He (Virus Genes, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

A new patchoulane-type sesquiterpenoid glycoside from the roots of Croton crassifolius - Qing-Qing Yuan; Wei-Bin Song; Wen-Qiong Wang; Li-Jiang Xuan (Natural Product Research, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Endogenous neurogenesis in adult mammals after spinal cord injury - Hongmei Duan; Wei Song; Wen Zhao; Yudan Gao; Zhaoyang Yang; Xiaoguang Li (Science China Life Sciences, 2016)

Synergistic and Superimposed Effect of Bone Marrow-Derived Mesenchymal Stem Cells Combined with Fasudil in Experimental Autoimmune Encephalomyelitis - Jing-Wen Yu; Yan-Hua Li; Guo-Bin Song; Jie-Zhong Yu; Chun-Yun Liu; Jian-Chun Liu; Hai-Fei Zhang; Wan-Fang Yang; Qing Wang; Ya-Ping Yan; Bao-Guo Xiao; Cun-Gen Ma (Journal of Molecular Neuroscience, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Object-based image analysis for mapping geomorphic zones of coral reefs in the Xisha Islands, China - Jingping Xu; Jianhua Zhao; Fang Li; Lin Wang; Derui Song; Shiyong Wen; Fei Wang; Ning Gao (Acta Oceanologica Sinica, 2016)

Multienzymatic cascade synthesis of fucosyloligosaccharide via a two-step fermentation strategy in Escherichia coli - Hui-Min Qin; Songtao Li; Yu-Fu Zhang; Jian-Wen Wang; Jixuan Li; Shiyi Song; Fuping Lu; Yu Li (Biotechnology Letters, 2016)

Gene expression pattern analysis of a recombinant Escherichia coli strain possessing high growth and lycopene production capability when using fructose as carbon source - Wen Du; Yajian Song; Mengya Liu; Haixu Yang; Yao Zhang; Yanli Fan; Xuegang Luo; Zhongyuan Li; Nan Wang; Hongpeng He; Hao Zhou; Wenjian Ma; et al. (Biotechnology Letters, 2016)

Enhanced Neuroprotection of Acetyl-11-Keto-β-Boswellic Acid (AKBA)-Loaded O-Carboxymethyl Chitosan Nanoparticles Through Antioxidant and Anti-Inflammatory Pathways - Yi Ding; Youbei Qiao; Min Wang; Huinan Zhang; Liang Li; Yikai Zhang; Jie Ge; Ying Song; Yuwen Li; Aidong Wen (Molecular Neurobiology, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Difference in resistance to Salmonella enteritidis infection among allelic variants of TLR4 (903, 1832) in SPF chickens - L. Liu; X. W. Zhao; Y. M. Song; Q. H. Li; P. Li; R. R. Liu; M. Q. Zheng; J. Wen; G. P. Zhao (Journal of Applied Genetics, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Characterization of CDOM from urban waters in Northern-Northeastern China using excitation-emission matrix fluorescence and parallel factor analysis - Ying Zhao; Kaishan Song; Sijia Li; Jianhang Ma; Zhidan Wen (Environmental Science and Pollution Research, 2016)

A Molecular Aspect in the Regulation of Drug Metabolism: Does PXR-Induced Enzyme Expression Always Lead to Functional Changes in Drug Metabolism? - Yuan Wei; Chenxiao Tang; Vinayak Sant; Song Li; Samuel M. Poloyac; Wen Xie (Current Pharmacology Reports, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Changes in the physiological properties and kinetics of citric acid accumulation via carbon ion irradiation mutagenesis of Aspergillus niger - Wei Hu; Ji-hong Chen; Shu-yang Wang; Jing Liu; Yuan Song; Qing-feng Wu; Wen-jian Li (Journal of Zhejiang University-SCIENCE B, 2016)

A novel Phakopsora pachyrhizi resistance allele (Rpp) contributed by PI 567068A - Zachary R. King; Donna K. Harris; Kerry F. Pedley; Qijian Song; Dechun Wang; Zixiang Wen; James W. Buck; Zenglu Li; H. Roger Boerma (Theoretical and Applied Genetics, 2016)

Ammonium removal of drinking water at low temperature by activated carbon filter biologically enhanced with heterotrophic nitrifying bacteria - Wen Qin; Wei-Guang Li; Duo-Ying Zhang; Xiao-Fei Huang; Yang Song (Environmental Science and Pollution Research, 2016)

Impact of emission control on PM2.5 and the chemical composition change in Beijing-Tianjin-Hebei during the APEC summit 2014 - Wei Wen; Shuiyuan Cheng; Xufeng Chen; Gang Wang; Song Li; Xiaoqi Wang; Xiaoyu Liu (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

Culture temperature modulates monoclonal antibody charge variation distribution in Chinese hamster ovary cell cultures - Xintao Zhang; Ya-Ting Sun; Hongping Tang; Li Fan; Dongdong Hu; Jintao Liu; Xuping Liu; Wen-Song Tan (Biotechnology Letters, 2015)

Transcriptome profiling of trichome-less reveals genes associated with multicellular trichome development in Cucumis sativus - Jun-Long Zhao; Yun-Li Wang; Dan-Qing Yao; Wen-Ying Zhu; Long Chen; Huan-Le He; Jun-Song Pan; Run Cai (Molecular Genetics and Genomics, 2015)

The Association Between Serum Levels of Selenium, Copper, and Magnesium with Thyroid Cancer: a Meta-analysis - Fei Shen; Wen-Song Cai; Jiang-Lin Li; Zhe Feng; Jie Cao; Bo Xu (Biological Trace Element Research, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Galactose supplementation enhance sialylation of recombinant Fc-fusion protein in CHO cell: an insight into the role of galactosylation in sialylation - Jintao Liu; Jie Wang; Li Fan; Xinning Chen; Dongdong Hu; Xiancun Deng; H. Fai Poon; Haibin Wang; Xuping Liu; Wen-Song Tan (World Journal of Microbiology and Biotechnology, 2015)

The F-box family genes as key elements in response to salt, heavy mental, and drought stresses in Medicago truncatula - Jian Bo Song; Yan Xiang Wang; Hai Bo Li; Bo Wen Li; Zhao Sheng Zhou; Shuai Gao; Zhi Min Yang (Functional & Integrative Genomics, 2015)

Ion-exchange method in the collection of nitrate from freshwater ecosystems for nitrogen and oxygen isotope analysis: a review - Wen-Bing Li; Yao-Bin Song; Hong-Ke Xu; Ling-Yun Chen; Wen-Hong Dai; Ming Dong (Environmental Science and Pollution Research, 2015)

Monitoring sialylation levels of Fc-fusion protein using size-exclusion chromatography as a process analytical technology tool - Jintao Liu; Xinning Chen; Li Fan; Xiancun Deng; H. Fai Poon; Wen-Song Tan; Xuping Liu (Biotechnology Letters, 2015)

Water relations and gas exchange of fan bryophytes and their adaptations to microhabitats in an Asian subtropical montane cloud forest - Liang Song; Yong-Jiang Zhang; Xi Chen; Su Li; Hua-Zheng Lu; Chuan-Sheng Wu; Zheng-Hong Tan; Wen-Yao Liu; Xian-Meng Shi (Journal of Plant Research, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

Endogenous nitric oxide in Pseudomonas fluorescens ZY2 as mediator against the combined exposure to zinc and cefradine - Yan-Bin Xu; Yan Zhou; Jing-Jing Ruan; Shi-Hui Xu; Ji-Dong Gu; Shao-Song Huang; Li Zheng; Bao-Hong Yuan; Li-Hua Wen (Ecotoxicology, 2015)

Paenibacillus wulumuqiensis sp. nov. and Paenibacillus dauci sp. nov., two novel species of the genus Paenibacillus - Jing Zhu; Wei Wang; Shan-Hui Li; Su-Qin Song; Yu-Qing Xie; Qi-Yong Tang; Ghenijan Osman; Yu-Hu Shi; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2015)

Lead accumulation and tolerance of Moso bamboo (Phyllostachys pubescens) seedlings: applications of phytoremediation - Dan Liu; Song Li; Ejazul Islam; Jun-ren Chen; Jia-sen Wu; Zheng-qian Ye; Dan-li Peng; Wen-bo Yan; Kou-ping Lu (Journal of Zhejiang University-SCIENCE B, 2015)

Geochronology and geochemistry of Grenville-aged (1063 ± 16 Ma) metabasalts in the Shennongjia district, Yangtze block: implications for tectonic evolution of the South China Craton - Xiao-Fei Qiu; Hong-Mei Yang; Shan-Song Lu; Wen-Li Ling; Li-Guo Zhang; Juan-Juan Tan; Zhi-Xian Wang (International Geology Review, 2015)

Taxonomy and molecular phylogeny of four Strombidium species, including description of S. pseudostylifer sp. nov. (Ciliophora, Oligotrichia) - Wen Song; Jiamei Li; Weiwei Liu; Khaled A. S. Al-rasheid; Xiaozhong Hu; Xiaofeng Lin (Systematics and Biodiversity, 2015)

Biochemical responses and survival of rock carp (Procypris rabaudi) to total dissolved gas supersaturated water - Xiao qing Liu; Ke feng Li; Wen Jiang; Song Wu (Ichthyological Research, 2015)

Effects of boron toxicity on root and leaf anatomy in two Citrus species differing in boron tolerance - Jing-Hao Huang; Zi-Jian Cai; Shou-Xing Wen; Peng Guo; Xin Ye; Gui-Zhu Lin; Li-Song Chen (Trees, 2014)

Up-regulation of SKIP relates to retinal ganglion cells apoptosis after optic nerve crush in vivo - Yu Wu; Fan Xu; Hui Huang; Lifei Chen; Meidan Wen; Li Jiang; Lu Lu; Li Li; Di Song; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Two HSPs gene from juvenile Amur sturgeon (Acipenser schrenckii): cloning, characterization and expression pattern to crowding and hypoxia stress - Meng Ni; Haishen Wen; Jifang Li; Meili Chi; Yuanyuan Ren; Zhifei Song; Houmeng Ding (Fish Physiology and Biochemistry, 2014)

Effects of dominant microalgae species and bacterial quantity on shrimp production in the final culture season - Yu-cheng Cao; Guo-liang Wen; Zhuo-jia Li; Xiao-zhu Liu; Xiao-juan Hu; Jia-song Zhang; Jian-guo He (Journal of Applied Phycology, 2014)

A field study of the relationship between sulfide-bound metals and bioaccumulation by Limnodrilus sp. in a heavily polluted river - Feng Li; Xiang-yun Zeng; Yun-jun Yu; Chang-hua Wu; Ge Mai; Wei-wei Song; Yan-mao Wen; Zhi-peng Duan; Jia-yu Yang (Environmental Monitoring and Assessment, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

An α-glucan isolated from root of Isatis Indigotica, its structure and adjuvant activity - Junjie Shan; Guohui Sun; Jinwei Ren; Ting Zhu; Peiyuan Jia; Wensheng Qu; Qian Li; Junhua Wu; Hao Ma; Song Wen; Yuxia Wang (Glycoconjugate Journal, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Construction and optimization of a Pseudomonas putida whole-cell bioreporter for detection of bioavailable copper - Peng-Song Li; Zhi-Wen Peng; Jie Su; Hu-Chun Tao (Biotechnology Letters, 2014)

Protection Against Cu(II)-Induced Oxidative Stress and Toxicity to Chlorella vulgaris by 2,2′-Bipyridine-5,5′-dicarboxylic Acid - Yuezhong Wen; Xiaolin Sheng; Shufang Song; Lina Li; Weiping Liu (Archives of Environmental Contamination and Toxicology, 2014)

The effect of lansoprazole, an OCT inhibitor, on metformin pharmacokinetics in healthy subjects - Yi Ding; YanYan Jia; Ying Song; ChengTao Lu; YuWen Li; MinChun Chen; MingMing Wang; AiDong Wen (European Journal of Clinical Pharmacology, 2014)

High and low latitude types of the downstream influences of the North Atlantic Oscillation - Jie Song; Chongyin Li; Wen Zhou (Climate Dynamics, 2014)

The discovery of 3-(1-aminoethylidene)quinoline-2, 4(1H,3H)-dione derivatives as novel PSII electron transport inhibitors - Yu-Xiu Liu; Hua-Ping Zhao; Zi-Wen Wang; Yong-Hong Li; Hai-Bin Song; Hannah Riches; David Beattie; Yu-Cheng Gu; Qing-Min Wang (Molecular Diversity, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

β-Ionone arrests cell cycle of gastric carcinoma cancer cells by a MAPK pathway - Hong-Wei Dong; Shuang Zhang; Wen-Guang Sun; Qian Liu; Juan C. Ibla; Sulpicio G. Soriano; Xiao-Hui Han; Lian-Xin Liu; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Abundance and diversity of archaeal accA gene in hot springs in Yunnan Province, China - Zhao-Qi Song; Li Wang; Feng-Ping Wang; Hong-Chen Jiang; Jin-Quan Chen; En-Min Zhou; Feng Liang; Xiang Xiao; Wen-Jun Li (Extremophiles, 2013)

Optimizing cadmium and mercury specificity of CadR-based E. coli biosensors by redesign of CadR - Hu-Chun Tao; Zhi-Wen Peng; Peng-Song Li; Tai-An Yu; Jie Su (Biotechnology Letters, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Protective effect of gossypol on lipopolysaccharide-induced acute lung injury in mice - Zhicheng Liu; Zhengtao Yang; Yunhe Fu; Fenyang Li; Dejie Liang; Ershun Zhou; Xiaojing Song; Wen Zhang; Xichen Zhang; Yongguo Cao; Naisheng Zhang (Inflammation Research, 2013)

Tanshinone IIA and astragaloside IV promote the migration of mesenchymal stem cells by up-regulation of CXCR4 - Juan Xie; Huan Wang; Tiebing Song; Zongren Wang; Feng Li; Jing Ma; Jun Chen; Yayun Nan; Hui Yi; Wen Wang (Protoplasma, 2013)

Bacterial and archaeal diversities in Y unnan and T ibetan hot springs, C hina - Zhao‐Qi Song; Feng‐Ping Wang; Xiao‐Yang Zhi; Jin‐Quan Chen; En‐Min Zhou; Feng Liang; Xiang Xiao; Shu‐Kun Tang; Hong‐Chen Jiang; Chuanlun L. Zhang; Hailiang Dong; Wen‐Jun Li (Environmental Microbiology, 2013)
Summary Thousands of hot springs are located in the north‐eastern part of the Y unnan– T ibet geothermal zone, which is one of the most active geothermal areas in the world. However, a comprehensive and detailed understanding of microbial diversity in these hot springs is still lacking. In this study, bacterial and archaeal diversities were investigated in 16 hot springs ( pH 3.2–8.6; temperature 47–96° C ) in Y unnan P rovince and T ibet, C hina by using a barcoded 16 S rRNA gene‐pyrosequencing approach. A quificae , P roteobacteria , F irmicutes , D einococcus‐ T hermus and B acteroidetes comprised the large portion of the bacterial communities in acidic hot springs. Non‐acidic hot springs harboured more and variable bacterial phyla than acidic springs. D esulfurococcales and unclassified C renarchaeota were the dominated groups in archaeal populations from most of the non‐acidic hot springs; whereas, the archaeal community structure in acidic hot springs was simpler and characterized by S ulfolobales and T hermoplasmata . The phylogenetic analyses showed that A quificae and C renarchaeota were predominant in the investigated springs and possessed many phylogenetic lineages that have never been detected in other hot springs in the world. Thus findings from this study significantly improve our understanding of microbial diversity in terrestrial hot springs.

Apoptosis initiation of β-ionone in SGC-7901 gastric carcinoma cancer cells via a PI3K-AKT pathway - Qian Liu; Hong-Wei Dong; Wen-Guang Sun; Ming Liu; Juan C. Ibla; Lian-Xin Liu; John W. Parry; Xiao-Hui Han; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Phylogenetic analysis of the bovine parainfluenza virus type 3 from cattle herds revealing the existence of a genotype A strain in China - Yong-Jun Wen; Xin-Chuan Shi; Feng-Xue Wang; Wei Wang; Shu-Qin Zhang; Guo Li; Ni Song; Li-Zhi Chen; Shi-Peng Cheng; Hua Wu (Virus Genes, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Thermoactinospora rubra gen. nov., sp. nov., a thermophilic actinomycete isolated from Tengchong, Yunnan province, south–west China - En-Min Zhou; Shu-Kun Tang; Carsten Sjøholm; Zhao-Qi Song; Tian-Tian Yu; Ling-Ling Yang; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Apigenin enhances the cytotoxic effects of tumor necrosis factor-related apoptosis-inducing ligand in human rheumatoid arthritis fibroblast-like synoviocytes - Qing-wen Sun; Song-min Jiang; Ke Yang; Jian-ming Zheng; Li Zhang; Wei-dong Xu (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Gene expression profiles of two intraspecific Larix lines and their reciprocal hybrids - Ai Li; Meng-Die Fang; Wen-Qin Song; Cheng-Bin Chen; Li-Wang Qi; Chun-Guo Wang (Molecular Biology Reports, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Correlation of antibody production rate with glucose and lactate metabolism in Chinese hamster ovary cells - Fei Chen; Zhaoyang Ye; Liang Zhao; Xuping Liu; Li Fan; Wen-Song Tan (Biotechnology Letters, 2012)

Construction of a high density integrated genetic map for cucumber (Cucumis sativus L.) - Wei-Wei Zhang; Jun-Song Pan; Huan-Le He; Chi Zhang; Zheng Li; Jun-Long Zhao; Xiao-Jun Yuan; Li-Huang Zhu; San-Wen Huang; Run Cai (Theoretical and Applied Genetics, 2012)

Induction of Mitogynogenetic Diploids and Identification of WW Super-female Using Sex-Specific SSR Markers in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Xiang-Shan Ji; Chang-Wei Shao; Wen-Long Li; Jing-Feng Yang; Zuo Liang; Xiao-Lin Liao; Gen-Bo Xu; Ying Xu; Wen-Tao Song (Marine Biotechnology, 2012)

Expression and purification of two alternative peptides for mechano-growth factor in Escherichia coli - Li Song; Wen-Si Zhu; Jun-Li Dong; Zhuo-Yu Li; Xiao-Hui Liu (Biotechnology Letters, 2012)

DNA Methylation in Genomes of Several Annual Herbaceous and Woody Perennial Plants of Varying Ploidy as Detected by MSAP - Ai Li; Bao-Quan Hu; Zhen-Yi Xue; Li Chen; Wei-Xing Wang; Wen-Qin Song; Cheng-Bin Chen; Chun-Guo Wang (Plant Molecular Biology Reporter, 2011)

IKKβ downregulation is critical for triggering JNKs-dependent cell apoptotic response in the human hepatoma cells under arsenite exposure - Yi Li; Yi Hao; Ming Gao; Wen Dong; Meiru Hu; Shengtao Yuan; Lun Song (Molecular and Cellular Biochemistry, 2011)

Phytotoxicity and uptake of chlorpyrifos in cabbage - Zhi-Yong Zhang; Wei-Li Shan; Wen-Cheng Song; Yong Gong; Xian-Jin Liu (Environmental Chemistry Letters, 2011)

Production of transgenic rice new germplasm with strong resistance against two isolations of Rice stripe virus by RNA interference - Jin Ma; Yunzhi Song; Bin Wu; Mingsong Jiang; Kaidong Li; Changxiang Zhu; Fujiang Wen (Transgenic Research, 2011)

Inactivation of the extracytoplasmic function sigma factor Sig6 stimulates avermectin production in Streptomyces avermitilis - Libin Jiang; Yanping Liu; Pan Wang; Ying Wen; Yuan Song; Zhi Chen; Jilun Li (Biotechnology Letters, 2011)

α-Glucosidase inhibitory and antioxidant properties and antidiabetic activity of Hypericum ascyron L. - Wen-Yi Kang; Yan-Li Song; Li Zhang (Medicinal Chemistry Research, 2011)

Mapping of quantitative trait loci for fiber and lignin contents from an interspecific cross Oryza sativa × Oryza rufipogon - Jian-kun Xie; Xiang-li Kong; Jie Chen; Biao-lin Hu; Piao Wen; Jie-yun Zhuang; Jin-song Bao (Journal of Zhejiang University-SCIENCE B, 2011)

The complete mitochondrial genome of the hard clam Meretrix meretrix - Chong-bo He; Jian Wang; Xiang-gang Gao; Wen-tao Song; Hong-jun Li; Yun-feng Li; Wei-dong Liu; Hao Su (Molecular Biology Reports, 2011)

Seismic noise attenuation using nonstationary polynomial fitting - Guo-Chang Liu; Xiao-Hong Chen; Jing-Ye Li; Jing Du; Jia-Wen Song (Applied Geophysics, 2011)

Bacillus zhanjiangensis sp. nov., isolated from an oyster in South China Sea - Yi-Guang Chen; Song-Ping Hu; Shu-Kun Tang; Jian-Wu He; Jian-Qing Xiao; Hong-Yi Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Effect of culture temperature on TNFR-Fc productivity in recombinant glutamine synthetase-chinese hamster ovary cells - Li Fan; Liang Zhao; Zhaoyang Ye; Yating Sun; Tianci Kou; Yan Zhou; Wen-Song Tan (Biotechnology Letters, 2010)

Evaluation and Structure-Activity Relationship Study of Acute Toxicity of Naphthoquinones to Photobacterium phosphoreum, Photobacterium T3B - Feng Ding; Jing Guo; Zhen Li; Li Ying Li; Jin Yang Zhang; Jin Hua Zhang; Jie Lian; Wen Hua Song; Lin Zhu (Bulletin of Environmental Contamination and Toxicology, 2010)

Dose- and time-dependent α-synuclein aggregation induced by ferric iron in SK-N-SH cells - Wen-Jing Li; Hong Jiang; Ning Song; Jun-Xia Xie (Neuroscience Bulletin, 2010)

Aligning protein sequence and analysing substitution pattern using a class-specific matrix - Hai Song Xu; Wen Ke Ren; Xiao Hui Liu; Xiao Qin Li (Journal of Biosciences, 2010)

Diversity of Crenarchaeota in terrestrial hot springs in Tengchong, China - Zhao-Qi Song; Jing-Quan Chen; Hong-Chen Jiang; En-Min Zhou; Shu-Kun Tang; Xiao-Yang Zhi; Li-Xin Zhang; Chuan-Lun L. Zhang; Wen-Jun Li (Extremophiles, 2010)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Genetic diversity and population structure of 10 Chinese indigenous egg-type duck breeds assessed by microsatellite polymorphism - Hui-Fang Li; Wei-Tao Song; Jing-Ting Shu; Kuan-Wei Chen; Wen-Qi Zhu; Wei Han; Wen-Juan Xu (Journal of Genetics, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Conserved Sequences of Replicase Gene-Mediated Resistance to Potyvirus through RNA Silencing - Li Xu; YunZhi Song; JunHua Zhu; XingQi Guo; ChangXiang Zhu; FuJiang Wen (Journal of Plant Biology, 2009)

Signature of the Antarctic oscillation in the northern hemisphere - Jie Song; Wen Zhou; Chongyin Li; Lixin Qi (Meteorology and Atmospheric Physics, 2009)

Aggregation Pheromone of the Qinghai Spruce Bark Beetle, Ips nitidus Eggers - Qing-He Zhang; Jian-Hai Ma; Feng-Yu Zhao; Li-Wen Song; Jiang-Hua Sun (Journal of Chemical Ecology, 2009)

The linkage between the Pacific-North American teleconnection pattern and the North Atlantic Oscillation - Jie Song; Chongyin Li; Wen Zhou; Jing Pan (Advances in Atmospheric Sciences, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Neurokinin-1 Receptor Antagonist (Aprepitant) Suppresses HIV-1 Infection of Microglia/Macrophages - Xu Wang; Steven D. Douglas; Li Song; Yan-Jian Wang; Wen-Zhe Ho (Journal of Neuroimmune Pharmacology, 2008)

Mutation characteristics of the PAH gene in four nationality groups in Xinjiang of China - Wu-Zhong Yu; Dong-Hui Qiu; Fang Song; Li Liu; Shao-Ming Liu; Yu-Wei Jin; Yan-Ling Zhang; Hong-Yun Zou; Jiang He; Quan Lei; Xing-Wen Liu (Journal of Genetics, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Breeding of transgenic rice restorer line for multiple resistance against bacterial blight, striped stem borer and herbicide - Yipei Wei; Fangyin Yao; Changxiang Zhu; Mingsong Jiang; Guangxian Li; Yunzhi Song; Fujiang Wen (Euphytica, 2008)

Environmental preferences of longlining for yellowfin tuna ( Thunnus albacares ) in the tropical high seas of the Indian Ocean - LI MING SONG; YU ZHANG; LIU XIONG XU; WEN XIN JIANG; JIA QIAO WANG (Fisheries Oceanography, 2008)
A survey of yellowfin tuna, Thunnus albacares , fishing ground was carried out on board of the Chinese longliners from September 15 to December 12, 2005 in the tropical high seas of the Indian Ocean. The depth at which each yellowfin tuna was hooked was estimated using a stepwise regression analysis of theoretical hook depth and observed average hook depth measured using a temperature depth recorder. Water temperature, salinity, chlorophyll a , dissolved oxygen and thermocline, which are important variables influencing yellowfin tuna habitats, were measured in the survey. Catch rates of yellowfin tuna were then analyzed with respect to depth, temperature, salinity, chlorophyll a , dissolved oxygen and thermocline. We suggest that the optimum ranges of swimming depth, water temperature, chlorophyll a and dissolved oxygen concentration for yellowfin tuna are 100.0–179.9 m, 15.0–17.9°C, 0.090–0.099 μ g L −1 , 2.50–2.99 mg L −1 , respectively; that salinity has less influence on the vertical distribution of adult yellowfin tuna; and that yellowfin tuna are mainly distributed within the thermocline in the high seas of the Indian Ocean. Our results match the yellowfin tuna’s vulnerability to deep longline fishing gear well.

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)

Crop yield, nitrogen uptake and nitrate-nitrogen accumulation in soil as affected by 23 annual applications of fertilizer and manure in the rainfed region of Northwestern China - Sheng-Mao Yang; S. S. Malhi; Jian-Rong Song; You-Cai Xiong; Wei-Yun Yue; Li Li Lu; Jian-Guo Wang; Tian-Wen Guo (Nutrient Cycling in Agroecosystems, 2006)

Effects of cypermethrin and methyl parathion mixtures on hormone levels and immune functions in Wistar rats - Ping Liu; Xiaoxiao Song; Weihong Yuan; Weihua Wen; Xinan Wu; Jian Li; Xuemin Chen (Archives of Toxicology, 2006)

Differential Gene Expression of Human CD34+ Hematopoietic Stem and Progenitor Cells Before and After Culture - Qunliang Li; Haibo Cai; Qiwei Liu; Wen-Song Tan (Biotechnology Letters, 2006)

A recombination-based strategy for assembling open-reading frames - XiuHua Chen; Yong Tao; Guo-Zhen Liu; Li-Huang Zhu; Wen-Yuan Song (Plant Molecular Biology Reporter, 2005)

Cloning and characterization of an HDZip I gene GmHZ1 from soybean - Yong-Jun Wang; Yi-Dan Li; Guang-Zuo Luo; Ai-Guo Tian; Hui-Wen Wang; Jin-Song Zhang; Shou-Yi Chen (Planta, 2005)

Down-regulation of specific gene expression by double-strand RNA induces neural stem cell differentiation in vitro - Tieqiao Wen; Hailong Li; Hongsheng Song; Fuxue Chen; Cuiping Zhao; Wei Lu; Kuiyi Bao; Ye Jin (Molecular and Cellular Biochemistry, 2005)

Evaluation of genetic diversity and germ plasm identification of 44 species, clones, and cultivars from 5 sections of the genusPopulus based on amplified fragment length polymorphism analysis - Chun Jiang Zhou; Hong Zhu Song; Jin Hua Li; Jian Wei Sun; Min De Jin; Qi Wen Zhang; Bin Wang (Plant Molecular Biology Reporter, 2005)

Enzymatic Synthesis and Antioxidant Properties of L-Ascorbyl Oleate and L-Ascorbyl Linoleate - Qing-Xun Song; Dong-Zhi Wei; Wen-Yu Zhou; Wei-Qin Xu; Sheng-Li Yang (Biotechnology Letters, 2004)

Vernalization-induced flowering in wheat is mediated by a lectin-like gene VER2 - Wei-dong Yong; Yun-yuan Xu; Wen-zhong Xu; Xin Wang; Ning Li; Jin-song Wu; Tie-bing Liang; Kang Chong; Zhi-hong Xu; Ke-hui Tan; Zhi-qing Zhu (Planta, 2003)

The effects of DNA hypomethylating drugs on androgenesis in barley (Hordeum vulgare L.) - Wen-Ze Li; Zi-Hong Song; Bao-Tai Guo; Li-Juan Xu (In Vitro Cellular & Developmental Biology - Plant, 2001)